A common high-pressure metamorphic evolution of interlayered eclogites and metasediments from the ‘ultrahigh-pressure unit’ of the Tianshan metamorphic belt in China - Li, Jilei; Klemd, Reiner; Gao, Jun; Jiang, Tuo; Song, Yun-Hui (Lithos, 2015)
Petrological and mineralogical data of interlayered eclogite, marble and quartz–mica schist from a drill core are used to constrain the metamorphic evolution of metavolcanics and intercalated metasediments in the Tianshan (ultra-)high-pressure/low-temperature [(U)HP/LT] metamorphic belt, NW China. The eclogite mainly consists of varying amounts of garnet, omphacite, quartz and zoisite, the marble of calcite (> 95 vol.%) with minor zoisite and phengite, and the schist of quartz and mica with minor calcite, chlorite, albite and garnet. Using garnet isopleth thermobarometry, pseudosection calculations for the eclogite and quartz–mica schist reveal a common metamorphic evolution under HP condition of both rock types that is also consistent with the temperature estimates for the marble using conventional thermometry. The uniform P–T paths of the interlayered eclogite and quartz–mica schist, as well as compatible temperature data of the marble, document that the whole rock suite constitutes a coherent HP unit during peak metamorphic conditions and exhumation. Thus protoliths of eclogite and associated sediments are believed to have undergone the same metamorphic evolution. In addition, the data gained by the present study of the HP rocks, which were collected in the northern part of the Chinese Tianshan (U)HP/LT belt, do not support the recently proposed tectonic scheme that this metamorphic terrane consists of a northern “coherent UHP unit” and a southern “coherent HP unit”.<br
Keywords: High pressure; Eclogite; Pseudosection; P–T evolution; Tianshan

Age constraints on high-pressure/low-temperature metamorphism and sedimentation in the Luk Ulo Complex (Java, Indonesia) - Hoffmann, J.; Broecker, M.; Setiawan, N.; Klemd, Reiner; Berndt, J.; Maulana, A.; Baier, H. (Lithos, 2019)
Pre-Cenozoic blueschist- and eclogite-facies rocks occur widely scattered in the central Indonesian region, possibly representing lateral equivalents of the same subduction zone. High-pressure/low-temperature (HP/LT) metamorphism is thought to have occurred during the Early Cretaceous, which however is only constrained by K–Ar ages. This study is part of a systematic re-investigation of the regional geochronological record of various metamorphic rocks from this belt and focuses on the Luk Ulo Complex in central Java. Rubidium–Sr multipoint isochrons of one eclogite, two epidote-glaucophane schistsand one epidote amphibolite yielded Early Cretaceous (Aptian) ages of 119–117 Ma (± 0.6–0.8 Ma). These ages are similar to previously reported K–Ar results, indicating that the existing data had not significantly been compromised by extraneous Ar contamination. Relatively low peak metamorphic temperatures (ca. 400 °C) during the HP/LT stage suggest that the Rb–Sr isotopic system was not significantly affected by diffusive loss during cooling. The Rb–Sr ages most likely constrain the time of mica growth or recrystallization during high-pressure metamorphism. The matching ages of high-pressure and lower pressure rocks are attributed to inheritance, but mixing of rocks that originally had formed at the same time at different depths of the subduction complex cannot completely be ruled out yet. Rubidium–Sr white mica ages of eclogite- and blueschist-facies rocks from central Java are younger than those of similar rocks from the Western Sulawesi tectonic province (130–120 Ma), revealing a previously unknown age difference that had been hidden by the poorer precision of the K–Ar dataset. At this point, it remains unclear whether this age difference is related to processes operating within the same or in different subduction zones. The zircon populations of clastic metasedimentary rocks from the Luk Ulo Complex are dominated by a prominent Jurassic to Carboniferouspopulation (ca. 320–180 Ma) with a distinct Permo-Triassic peak (ca. 270–200 Ma). Another less pronounced Paleozoic age signal shows up at 450–380 Ma. Proterozoic and Archean zircon grains are very rare. At least some data points at the lower end of the age spectrum (ca.135–117 Ma) most likely are related to in-situ metamorphic processes. The youngest zircon grains of unambiguous detrital origin show up at ca. 160 Ma, indicating a Late Jurassic maximum depositional age. Additional detrital zircon data for the Barru Complex (Western Sulawesi) further substantiate previous findings documenting a complex age spectrum with contributions of Mesozoic (Triassic), Paleozoic (Permian, Carboniferous, Devonian to Ordovician), Meso- to Paleoproterozoic subpopulations and rare Archean zircons. The youngest zircons indicate a maximum depositional age of ca. 255–250 Ma. New and existing U–Pb zircon data indicate that the pre-metamorphic basin histories recorded in the Luk Ulo and Barru complexes are linked to different source terrains and depositional system
CRIS-Team WoS Importer:2019-02-21
Keywords: High-pressure metamorphism; Geochronology; Rb–Sr; U–Pb; Detrital zircon; Luk Ulo complex; Indonesia

An (in-)coherent metamorphic evolution of high-P eclogites and their host rocks in the Chinese southwest Tianshan? - Meyer, Melanie; Klemd, Reiner; John, Timm; Gao, Jun; Menneken, Martina (Journal of Metamorphic Geology, 2016)
In the (ultra‐)high‐P–low‐T metamorphic terrane of the Chinese South Tianshan, discontinuous mafic blocks and boudins (former upper oceanic crust) are now embedded in voluminous (mainly metasedimentary) host rocks. Two different models were proposed and relate the occurrence of both high‐P and ultra‐high‐P mafic and metasedimentary rocks to either (i) a tectonic mélange style exhumation, with no exhumation of coherent units, but different lithologies derived from different depths juxtaposed and intermingled during exhumation in the subduction channel, or (ii) the evolution of two coherent metamorphic belts: one with high‐P and the other with ultra‐high‐P conditions. In contrast to most previous studies in the Chinese South Tianshan which focused either on single eclogites or metasedimentary rocks (assumed as representative), this study concentrates on the systematic investigation of both mafic boudins and their immediate sedimentary host rocks, because the investigation of both lithologies and the comparison of their metamorphic evolution is crucial to reconstruct the geodynamical context of the whole (ultra‐)high‐P–low‐T metamorphic complex. Several sample pairs consisting of both lithologies were geochemically investigated and their respective metamorphic evolution was reconstructed using geothermobarometry and thermodynamic modelling. The latter approach considers changes in the mineral assemblage during the metamorphic evolution, as well as changes in mineral composition, which may help to determine the metamorphic history of a rock despite the preservation of critical mineral assemblages. All samples experienced a clockwise P–Tpath with overall maximum P–T conditions of 540–550 °C and 1.9–2.25 GPa for the host rocks, and 555–575 °C and 2.2–2.5 GPa for the eclogites. Peak‐metamorphic temperatures of 525–540 °C of the metasedimentary host rocks were also confirmed by Raman spectroscopy of carbonaceous material. Results from thermobarometry and thermodynamic modelling are consistent with the observation that none of the samples contains mineral relicts indicating UHP conditions (like coesite in garnet) and neither conventional thermobarometry, nor thermodynamical modelling resulted in P–Tconditions in the stability field of coesite. Thus, no evidence of ultra‐high‐P conditions was found. Given that the whole sampled river valley lies within the proposed ‘ultra‐high‐P sub‐belt’ and considering former studies, which showed that at other places within this ‘unit’ both ultra‐high‐P and high‐P rocks are now juxtaposed on a small scale, the formation of the whole (ultra‐)high‐P–low‐T metamorphic belt in the Chinese South Tianshan as a tectonic mélange style exhumation is more convincing than the formation and juxtaposition of two coherent metamorphic units with high‐P and ultra‐high‐Pconditions respectively.<br
Keywords: (U)HP metamorphism; eclogite; P–T path; thermobarometry; Tianshan

A review of the genetic mechanisms generating igneous charnockite: CO2 flushing and crystal-melt segregation in mushy reservoirs - Zhao, Kai; Xu, Xisheng; Klemd, Reiner; He, Zhenyu; Zhang, Xisong (Earth-Science Reviews, 2023)
Igneous charnockites are high-temperature orthopyroxene-bearing granitoids, which constitute an important part of many high-grade terranes. High temperature (typically >750–800 °C) is considered to be a key factor regarding the formation of igneous charnockites, because orthopyroxene reacts with hydrous melts to form biotite and/or amphibole at low temperatures as predicted by equilibrium phase relations. Microstructural records of igneous charnockites suggest that the hydrous crystallization reaction occurs at near equilibrium conditions. Thus, it remains a puzzling question how orthopyroxene is preserved in granitoids that generally solidify at H2O-saturated solidus temperatures (<700 °C). Here, we synthesize mineralogical, petrological, and geochemical data for 32 charnockite plutons worldwide to evaluate the possible preservation mechanisms of orthopyroxene in granitoids. These igneous charnockites are classified as I-A-S types based on their mineral assemblages and whole-rock compositions. The orthopyroxene crystals in the igneous charnockites systematically have lower Al2O3 contents than those in metamorphic rocks, suggesting a magmatic origin of the former. Magmatic orthopyroxene is possibly preserved by two mechanisms, preventing back-reactions with hydrous melts: one mechanism deduced from fluid-inclusion studies highlights the importance of CO2, which can reduce the H2O activity and elevate the solidus temperature to the stability field of orthopyroxene. Physical constraints on fluid transport suggest that this mechanism is feasible when an orthopyroxene-bearing mushy reservoir is flushed by large amounts (>10–20 vol%) of CO2-rich fluids, which could form a permeable flow through bubble channels in the pore medium and significantly elevate the CO2 content (>1000 ppm at pressures of >0.2 GPa) dissolved in the interstitial melts. Available fluid-inclusion studies suggest that such a mechanism may have played an important role in the formation of some I- and A-type charnockites. Nonetheless, deducing the fluid composition solely from fluid-inclusion studies is ambiguous, since the trapping of fluid inclusions may leave a potentially non-representative record due to the different wetting characteristics of CO2 and H2O, as well as post-trapping grain-boundary migration recrystallisation, favoring the entrapment of CO2-rich inclusions. A further alternative mechanism is to extract hydrous melts from an orthopyroxene-bearing mush, thereby restricting the back-reaction of orthopyroxene during progressive crystallization. Igneous charnockites have maximum P2O5 contents of up to 1.0–1.2 wt% at 55–60 wt% SiO2 and Zr contents of up to >400–600 ppm at 60–65 wt% SiO2. The nonsynchronous variations in P2O5 and Zr contents can best be explained by melt extraction from a mush that saturates apatite earlier than zircon during magma evolution. This process produces apatite- and zircon-rich cumulate charnockites that have significantly higher P2O5 and Zr contents than global orthopyroxene-free granitoids. Many I-A-S type charnockites are believed to have formed through this mechanism and represent cumulate granitoids that had lost a significant amount (>20–40%) of hydrous interstitial melt. Our study reveals that the formation of igneous charnockite depends on extreme magmatic processes such as flushing of large amounts of CO2 or high degree of crystal-melt segregation, and not merely on the high temperature of crystallization. Further studies on igneous charnockite should shed new light on quantifying the carbon flux and understanding the differentiation of the continental crust.
CRIS-Team Scopus Importer:2023-01-20
Keywords: CO; Crystal mush; Crystal-liquid segregation; Igneous charnockite; Orthopyroxene

Arsenian pyrite and cinnabar from active submarine nearshore vents, paleochori bay, milos island, Greece - Voudouris, Panagiotis; Kati, Marianna; Magganas, Andreas; Keith, Manuel; Valsami-Jones, Eugenia; Haase, Karsten; Klemd, Reiner; Nestmeyer, Mark (Minerals, 2021)
Active, shallow-water (2–10 m below sea level) and low temperature (up to 115◦C) hydrothermal venting at Paleochori Bay, nearshore Milos Island, Greece, discharges CO2 and H2S rich vapors (e.g., low-Cl fluid) and high-salinity liquids, which leads to a diverse assemblage of sulfide and alteration phases in an area of approximately 1 km2. Volcaniclastic detritus recovered from the seafloor is cemented by hydrothermal pyrite and marcasite, while semi-massive to massive pyrite-marcasite constitute mounds and chimney-like edifices. Paragenetic relationships indicate deposition of two distinct mineralogical assemblages related to the venting of high-Cl and low-Cl fluids, respectively: (1) colloform As-and Hg-bearing pyrite (Py I), associated with marcasite, calcite, and apatite, as well as (2) porous and/or massive As-rich pyrite (Py II), associated with barite, alunite/jarosite, and late-stage hydrous ferric oxides. Mercury, in the form of cinnabar, occurs within the As-rich pyrite (Py I) layers, usually forming distinct cinnabar-enriched micro-layers. Arsenic in colloform pyrite I shows a negative correlation with S indicating that As1− dominates in the pyrite structure suggesting formation from a relatively reducing As-rich fluid at conditions similar to low-sulfidation epithermal systems. On the contrary, As3+ dominates in the structure of porous to massive pyrite II suggesting deposition from a sulfate-dominated fluid with lower pH and higher fO2. Bulk sulfide data of pyrite-bearing hydrothermal precipitates also show elevated As (up to 2587 ppm) together with various epithermal-type elements, such as Sb (up to 274 ppm), Tl (up to 513 ppm), and Hg (up to 34 ppm) suggesting an epithermal nature for the hydrothermal activity at Paleochori Bay. Textural relationships indicate a contemporaneous deposition of As and Hg, which is suggested to be the result of venting from both high-salinity, liquid-dominated, as well as CO2-and H2S-rich vapor-dominated fluids that formed during fluid boiling. The CO2-and H2S-rich vapor that physically separated during fluid boiling from the high-salinity liquid led to calcite formation upon condensation in seawater together with the precipitation of As-and Hg-bearing pyrite I. This also led to the formation of sulfuric acid, thereby causing leaching and dissolution of primary iron-rich minerals in the volcaniclastic sediments, finally resulting in pyrite II precipitation in association with alunite/jarosite. The Paleochori vents contain the first documented occurrence of cinnabar on the seafloor in the Mediterranean area and provide an important link between offshore hydrothermal activity and the onshore mercuryarsenic mineralizing system on Milos Island. The results of this study therefore demonstrate that metal and metalloid precipitation in shallow-water continental arc environments is controlled by epithermal processes known from their subaerial analogues.
Created from Fastlane, Scopus look-up
Keywords: Boiling; Cinnabar; Low-sulfidation epithermal; Shallow-water hydrothermal activity; Steam-heated alunite; Sulfide mound

Boiling effects on trace element and sulfur isotope compositions of sulfides in shallow-marine hydrothermal systems: Evidence from Milos Island, Greece - Schaarschmidt, Anna; Haase, Karsten; Klemd, Reiner; Keith, Manuel; Voudouris, Panagiotis C.; Alfieris, Dimitrios; Strauss, Harald; Wiedenbeck, Michael (Chemical Geology, 2021)
Boiling is a crucial process triggering ore formation in magmatic-hydrothermal systems and controlling the enrichment of precious and rare metal(loid)s in epithermal-porphyry mineralizations. Steep physicochemical gradients during boiling of hydrothermal fluids at shallow water depths caused metal(loid) precipitation along a 3 km long Pb-Zn-Ag vein system on Milos Island in the South Aegean Volcanic Arc. We present new trace element and Pb, Sr, and S isotope data from sulfides providing insights into the diversity of mineralization processes in shallow-marine hydrothermal systems. Lead and Sr isotope compositions of sulfides and sulfates reflect the mixing of fluids that reacted with metamorphic basement and the volcanic host rocks, whereas some of the S were derived from seawater. Investigation of mineralized samples along the Kondaros-Vani fault zone revealed distinct chemical variations that represent a vertical profile through the boiling zone of a hydrothermal system. Boiling during fluid ascent at decreasing temperatures (230–150 °C) and sulfur fugacities triggered the precipitation of sulfides rich in Zn, Pb, Fe, Cu, Ag, Sb, and As, resulting in increasing Pb, Ag, and Sb contents with decreasing depth. A pyrite group with high Tl/Cu and low As/Sb ratios, as well as δ34SVCDT values reaching as low as −6‰, is interpreted as precipitating from high-Cl liquids that underwent vigorous boiling at deeper crustal levels subsequent to tectonic faulting. Condensation of vapor (high Hg, Bi, and As contents) and mixing with seawater (high Mo contents) in the shallow-marine subseafloor sequences at Vani caused Hg-Bi-Mo-As-rich mineralization similar to the active hydrothermal system at Milos.
Keywords: Trace elements; Hydrothermal systems; Epithermal ore deposits; Boiling; Pyrite; Sulfur fugacity; Isotopes

Changes in dip of subducted slabs at depth: petrological and geochronological evidence from HP-UHP rocks (Tianshan, NW-China). - Klemd, Reiner; John, Timm; Scherer, E. E.; Rondenay, Stephane; Gao, J. (Earth and Planetary Science Letters, 2011)
High-resolution seismic imaging has previously revealed sudden changes in the dip of subducted oceanic plates. This 'kinking' feature is crucial because in many subduction zones it is thought to coincide with the disappearance of the low-velocity layers associated with subducted oceanic crust. In this study, we present petrological evidence for this phenomenon derived from oceanic blueschist- and eclogite-facies rocks from the Chinese Tianshan. The investigated samples span a large range of peak metamorphic conditions, with temperatures between 330 and 580°C at 1.5 to 2.3GPa. Such variable peak metamorphic conditions, together with the intimate interlayering of high- and ultrahigh-pressure rocks, have also been reported from other Tianshan localities. These observations suggest that the rocks were derived from varying depths within the subduction zone and then juxtaposed during exhumation in the subduction channel. Multi-point Lu-Hf isochrons from four high-pressure rocks yield consistent garnet-growth ages of 313±12, 315.8±2.9, 313.9±4.8, and 315.2±1.6Ma. These, in conjunction with the 311Ma cluster of published 40Ar-39Ar and Rb-Sr white mica ages from the same vicinities imply fast exhumation rates. The Lu-Hf ages confirm that the eclogite-facies metamorphism of the Tianshan high-pressure rocks occurred during a single subduction event in the Late Carboniferous. However, the previously reported peak metamorphic P-T estimates from UHP metasediments and eclogites all lie on a lower geothermal gradient - and thus on a colder P-T path at the slab-wedge interface - than the HP eclogites and meta-volcaniclastic rocks from this study. This suggests that the slab-subduction angle steepened sharply at a depth greater than approximately 90km, i.e., between the depths at which the HP and UHP rocks equilibrated. In addition to the negative buoyancy of mafic UHP rocks in subduction zones, the kinking may act as a geometric hindrance to the exhumation of such rocks, thereby explaining their rarity. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.c3geoc.change
Keywords: (U)HP rocks; Lu-Hf geochronology; Oceanic crust; Slab dip steepening; Subduction; Tianshan

co-As mineralization at the mining district Bou Azzer-El Graara Inlier, Anti-Atlas, Morocco. - Pätzold, Jürgen; Klemd, Reiner; Joachimski, Michael (Zeitschrift für Angewandte Geologie, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.c3geoc.coasmi

Coexisting carbonate-bearing eclogite and blueschist in SW Tianshan, China: Petrology and phase equilibria. - Li, Jilei; Klemd, Reiner; Gao, Jun; Meyer, Melanie (Journal of Asian Earth Sciences, 2012)
Carbonate-bearing eclogite and blueschist coexist in the same lithological sequence in the Tianshan (ultra-)high-pressure/low-temperature metamorphic belt, northwestern China. Both of them consist of the mineral assemblage garnet+omphacite+dolomite±magnesite+phengite±paragonite+epidote/clinozoisite+glaucophane±barroisite/(Mg-)katophorite+rutile/titanite+pyrite. The eclogite has an omphacite content of ca. 43vol.% and a glaucophane content of <1vol.%. In contrast, the blueschist has an omphacite content of <8vol.% and a glaucophane content of ca. 43vol.%. The blueschist occurs as bands or interlayers in the eclogite. Lawsonite pseudomorphs of epidote/clinozoisite+paragonite assemblages in garnet are commonly observed in the eclogite and blueschist. High carbonate contents in oceanic metabasalts suggest that the precursor basaltic crust has undergone significant hydrothermal alteration prior to subduction. Mineral assemblages and textures show that the omphacite-carbonate-bearing blueschist and the carbonate-bearing eclogite underwent an identical metamorphic evolution. Phase equilibrium modeling in the TiNCaKFMASCHO system further indicates that both the carbonate-bearing eclogite and the omphacite-bearing blueschist equilibrated at peak metamorphic conditions of 540-565°C and 21.8-23.1kbar. Under these conditions calculated X CO2 isopleths reveal the presence of a mainly aqueous fluid phase (X CO20.02) for the coexisting eclogite and omphacite-bearing blueschist. The stability of the high-pressure mineral assemblages in the eclogite and the omphacite-bearing blueschist is due to differences of the respective bulk-rock composition (the CaO content in particular). This study suggests that three different kinds of blueschist were formed during subduction and exhumation of the South Tianshan oceanic crust, including prograde blueschist formed prior to eclogitization, retrograde blueschist formed by rehydration of eclogite during exhumation in the subduction channel, and coexisting blueschist with eclogite under peak metamorphic conditions. © 2012 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.c3geoc.coexis
Keywords: Coexistence; Eclogite; Omphacite-bearing blueschist; Pseudosection; Tianshan (ultra-)high-pressure/low-temperature belt

Compositional zoning in dolomite from lawsonite-bearing eclogite (SW Tianshan, China): Evidence for prograde metamorphism during subduction of oceanic crust. - Li, Jilei; Klemd, Reiner; Gao, Jun; Meyer, Melanie (American Mineralogist, 2014)
Dolomite with compositional zoning was discovered in carbonate-lawsonite- bearing eclogites in the Tianshan (ultra-)high-pressure/low-temperature metamorphic belt, northwestern China. The eclogite-facies dolomite occurs as matrix porphyroblast and as inclusion in garnet, both of which display the same chemical zoning pattern. The dolomite contains inclusions of calcite (probably after aragonite), magnesite, glaucophane, lawsonite (and its pseudomorphs), allanite, epidote, paragonite, phengite, and omphacite. The chemical zoning in dolomite is well defined by a continuous core-to-rim Mg increase and Fe-Mn decrease. The concentrations of transition metal elements, REE, and Y also decrease from core to rim of the dolomite. Thermodynamic modeling demonstrates that the Fe-Mg zoning of dolomite is largely temperature dependent and, thus, is interpreted as prograde growth zoning, which developed during subduction of carbonate-bearing oceanic crust. It is suggested that dolomite in equilibrium with garnet formed as a result of changing matrix compositions due to increasing temperatures. In addition, thermodynamic modeling demonstrates that during subduction at high-pressure conditions prograde-formed aragonite and dolomite were transformed to dolomite and magnesite. Furthermore, Fe-rich magnesite inclusions in matrix dolomite and in dolomite inclusions in garnet are shown to have formed during high-pressure conditions prior to peak metamorphic conditions and, therefore caution is warranted using Fe-bearing magnesite occurrences in eclogite-facies rocks as an unambiguous ultrahigh pressure indicator as previously suggested. © 1997 - 2014 Mineralogical Society of America. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.compos_1
Keywords: Dolomite; Eclogite; High pressure; Magnesite; Prograde zoning; Tianshan

Constraints on the source of Cu in a submarine magmatic-hydrothermal system, Brothers volcano, Kermadec island arc - Keith, Manuel; Haase, Karsten; Klemd, Reiner; Smith, Dan; Schwarz-Schampera, Ulrich; Bach, Wolfgang (Contributions To Mineralogy and Petrology, 2018)
Most magmatic-hydrothermal Cu deposits are genetically linked to arc magmas. However, most continental or oceanic arc magmas are barren, and hence new methods have to be developed to distinguish between barren and mineralised arc systems. Source composition, melting conditions, the timing of S saturation and an initial chalcophile element-enrichment represent important parameters that control the potential of a subduction setting to host an economically valuable deposit. Brothers volcano in the Kermadec island arc is one of the best-studied examples of arc-related submarine magmatic-hydrothermal activity. This study, for the first time, compares the chemical and mineralogical composition of the Brothers seafloor massive sulphides and the associated dacitic to rhyolitic lavas that host the hydrothermal system. Incompatible trace element ratios, such as La/Sm and Ce/Pb, indicate that the basaltic melts from L'Esperance volcano may represent a parental analogue to the more evolved Brothers lavas. Copper-rich magmatic sulphides (Cu > 2 wt%) identified in fresh volcanic glass and phenocryst phases, such as clinopyroxene, plagioclase and Fe-Ti oxide suggest that the surrounding lavas that host the Brothers hydrothermal system represent a potential Cu source for the sulphide ores at the seafloor. Thermodynamic calculations reveal that the Brothers melts reached volatile saturation during their evolution. Melt inclusion data and the occurrence of sulphides along vesicle margins indicate that an exsolving volatile phase extracted Cu from the silicate melt and probably contributed it to the overlying hydrothermal system. Hence, the formation of the Cu-rich seafloor massive sulphides (up to 35.6 wt%) is probably due to the contribution of Cu from a bimodal source including wall rock leaching and magmatic degassing, in a mineralisation style that is hybrid between Cyprus-type volcanic-hosted massive sulphide and subaerial epithermal-porphyry deposits.
Keywords: Brothers volcano; Kermadec arc; Magmatic sulphides; Hydrothermal sulphides; Magmatic degassing; Melt inclusions; Epithermal-porphyry deposits; VHMS deposits

Crustal Contamination of the Mantle-Derived Liuyuan Basalts: Implications for the Permian Evolution of the Southern Central Asian Orogenic Belt - Yu, Yuanyang; Zong, Keqing; Yuan, Yu; Klemd, Reiner; Wang, Xin Shui; Guo, Jingliang; Xu, Rong; Hu, Zhaochu; Liu, Yongsheng (Journal of Earth Science, 2022)
The Permian basalts in the Central Asian Orogenic Belt (CAOB) are crucial for constraining the closure of the Paleo-Asian Ocean. However, the origin of these basalts is still under discussion. Here, we present comprehensive bulk-rock geochemical, Sr−Nd−Pb−Hf isotopic, and zircon U−Pb−Lu−Hf isotopic data of the Liuyuan basalts and coexisting gabbros, which are located in the Beishan Orogen in the southern CAOB, to constrain their emplacement setting and tectonic implications. Our new gabbro ages of ca. 288–294 Ma are interpreted to represent the formation time of the Liuyuan basaltic belt. The Liuyuan basalts show MORB-like rare earth element (REE) patterns and bulk-rock εHr(t) and εNd(t) values of 11.0–15.4 and 4.6–9.2, respectively, suggesting an origination mainly from a depleted mantle source. However, positive Pb anomalies, Nb−Ta depletions, and high Th/Yb ratios as well as evolved Sr−Nd−Pb−Hf isotopic compositions of some samples indicate variable continental crustal contribution. According to the covariation of Pb anomalies (Pb* =2×PbN/(CeN+PrN)) with Sr−Nd−Pb−Hf isotopic compositions, we speculate that parent magma of the Liuyuan basalt was contaminated by continental crustal materials during the eruption rather than having been generated from an enriched mantle source. As revealed by mixing modelling, the Liuyuan basaltic magmas would require a minor (<10%) upper continental crustal assimilation to explain the enriched trace elemental and radiogenic Sr−Nd−Pb−Hf isotopic signatures. Consequently, the Liuyuan basaltic belt is believed to have been generated in a continental extensional environment instead of an oceanic setting and does not constitute a Permian ophiolitic suture zone as previously suggested, since the Paleo-Asian Ocean was already closed in the southern Beishan Orogen in the Early Permian.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Beishan Orogen; Central Asian Orogenic Belt; crustal contamination; Liuyuan basaltic belt; Pb anomaly; tectonics

Cumulate olivine: A novel host for heavy rare earth element mineralization - Brandt, Sönke; Faßbender, Marc Lorin; Klemd, Reiner; Macauley, Chandra; Felfer, Peter; Haase, Karsten (Geology, 2020)

Deciphering protoliths of the (U)HP rocks in the Makbal metamorphic complex, Kyrgyzstan: geochemistry and SHRIMP zircon geochronology - Konopelko, Dmitry; Klemd, Reiner (European Journal of Mineralogy, 2016)
The (ultra)high-pressure (U) HP Makbal metamorphic complex (MMC) belongs to a chain of early Paleozoic (U) HP terranes to the south of the Paleo-Kazakhstan continent, a major component of the Central Asian Orogenic Belt. We present geochemical characteristics, reconstructions of geodynamic settings and constraints on the emplacement and depositional ages of metamorphosed intrusive and sedimentary rocks of the MMC. The MMC comprises variably metamorphosed juxtaposed packages of mica schists, hosting boudins of metamorphosed mafic rocks, metaquartzites and metacarbonates in a tectonic mélange. The rocks, metamorphosed under (U) HP conditions, are situated in the central part of the terrane. The UHP garnet–talc – chloritoid schists are believed to have formed from immature pelitic sediments with maximum depositional ages of 700 – 650 Ma. The (U) HP metaquartzites comprise mature sediments derived from a Paleoproterozoic continental source. They were formed in a passive-margin environment and have a maximum depositional age of ca. 1600 Ma. The chemical composition of the MMC metabasic rocks is compatible with subalkaline tholeiitic basalts with E-MORB compositions; however, some samples have N-MORB and OIB affinities. The ages of zircon xenocrysts from the metabasic rocks show that the mafic intrusions are probably younger than ca. 700 Ma. The metabasic rocks represent dikes and sills emplaced into immature pelitic sediments in a rift-related or continental-slope environment at the final stages of the Rodinia break up (700–600 Ma) when shallow mantle melting produced relatively primitive tholeiitic compositions. The whole sequence, including the quartzites, was later juxtaposed with other passive-margin sediments and metamorphosed under (U) HP conditions in a Caledonian subduction zone between 500 and 475 Ma. The ages of detrital zircon grains from the MMC rocks indicate derivation from a Paleoproterozoic continental source and match the age pattern characteristic for the Northern Tien Shan, with major peaks at 1.95–1.75 Ga and smaller peaks between 2.7 and 2.5 Ga and at ca. 1.0 Ga. The ages between 1.65 and 1.4 Ga are uncharacteristic for the Kyrgyz Northern Tien Shan, instead may be correlated with recently documented voluminous early Mesoproterozoic arc magmatism in the Central Tien Shan Arc Terrane in China. The resetting of the U– Th–Pb system and the growth of new zircon in the MMC rocks were probably defined by the permeability to aqueous fluids. An age of 456 ± 4 Ma, obtained for the rims of zircon xenocrysts from a small amphibolite boudin in the southern part of the MMC, corresponds with the age of an adjacent Ordovician granite and indicates that Paleozoic intrusions could have provided sufficient heat to cause resetting and/or growth of new zircon in the MMC rocks.<br
Keywords: tien shan (tianshan); geodynamic; eclogite; provenance; makbal (u)hp complex; geochemistry; u–pb zircon age; shrimp; setting

Desulphurisation, chromite alteration, and bulk rock PGE redistribution in massive chromitite due to hydrothermal overprint of the Panton Intrusion, east Kimberley, Western Australia - Beinlich, Andreas; von Heydebrand, Adrian; Klemd, Reiner; Martin, Laure; Hicks, John (Ore Geology Reviews, 2020)
The Central and Western Zones of the Halls Creek Orogen (HCO) of the East Kimberley region of Western Australia host various Paleoproterozoic layered mafic–ultramafic intrusions. The 1856 ± 2 Ma layered mafic–ultramafic Panton Intrusion of the Central Zone contains a reef-type platinum-group element (PGE) mineralisation associated with metamorphosed chromitite horizons. Here we investigate the compositional variation of chromite within the A chromitite layer, or Main Chromitite Layer (MCL), base metal sulphides (BMS), and the associated PGE distribution. Electron-microprobe analysis (EMPA) and laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) data reveal complex chemical zoning of the chromite reflecting post-magmatic sub-solidus re-equilibration and fluid–rock interaction during metamorphism of the host rocks. The sulphur isotopic composition of the BMS (δ34S: −1.67 to 2.89‰) suggests negligible contamination of the parental melt by crustal sulphur and thus favours BMS formation due to fractional crystallisation. Furthermore, pentlandite compositions indicate the highest ƒS2 in the centre of the MCL, which coincides with a considerably heavier sulphur isotope composition compared to pentlandite in the surrounding ultramafic host rock. Alteration of the BMS during amphibolite facies hydration of the Panton Intrusion resulted in the formation of secondary bornite and digenite from the chalcopyrite as well as desulphurisation of pyrrhotite and pentlandite to secondary magnetite. The bulk rock PGE concentrations are controlled by the distribution of platinum-group minerals (PGM) due to the low PGE concentrations in BMS. PGM are present as inclusions in chromite, suggesting that they formed under sulphur-undersaturated conditions. Additional PGM are present within the interstitial serpentine-chlorite matrix suggesting that they precipitated during fluid-rock interaction and hydration of the silicate matrix. Likely sources for the remobilised PGE include PGM inclusions in altered rim zones of magmatic chromite and PGE released due to desulphurisation of BMS despite their low PGE concentrations.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Base-metal sulphides; Chromitite reef; Desulphurisation; Hydrothermal alteration; Layered ultramafic intrusion; PGE deposit; PGE mobility; Serpentinisation

Different carbon reservoirs of auriferous fluids in African Archean and Proterozoic gold deposits? Constraints from stable carbon isotopic compositions of quartz-hosted CO2-rich fluid inclusions - Lüders, Volker; Klemd, Reiner; Oberthür, Thomas; Plessen, Birgit (Mineralium Deposita, 2015)
Stable carbon (and when present, nitrogen) isotope ratios of fluid inclusions in quartz from selected gold deposits in Ghana and Zimbabwe have been analyzed using a crushing device interfaced to an isotopic ratio mass spectrometer (IRMS) in order to constrain possible sources of the auriferous fluids. The study revealed a striking difference in stable carbon isotopic compositions of CO2 in quartz-hosted fluid inclusions from Archean and Paleoproterozoic orogenic gold deposits and points to diverse sources of CO2 in the studied deposits. Whether this finding can be generalized for other Archean and Proterozoic orogenic gold deposits worldwide remains open. However, a significant CO2 contribution by mantle degassing can be ruled out for every deposit studied. Devolatilization of greenstone belt rocks is the most likely source for CO2 in some Archean Au deposits in Zimbabwe, whereas CO2 in Proterozoic vein-type Au deposits in the West African Craton is most likely derived from Corg-bearing metasedimentary rocks. The δ13CCO2 values of high-density CO2-rich, water-poor inclusions hosted in quartz pebbles from the world-class Au-bearing conglomerate deposits at Tarkwa (Ghana) differ considerably from the δ13CCO2 values of similar high-density CO2-rich inclusions in vein quartz from the giant Ashanti deposit (Ghana) and disprove the idea of derivation of the Tarkwaian quartz (and gold?) from an older equivalent to the Ashanti vein-type gold deposit.<br
Keywords: Gold; Africa; Fluid inclusions; Carbon isotopes; Nitrogen isotopes

Different magma differentiation processes of post-onset collision adakitic rocks in the Gangdese Batholith: Evidence from zircon trace elements - Lu, Tian Yu; He, Zhen Yu; Klemd, Reiner (Chemical Geology, 2023)
The widespread adakitic magmatism in southern Tibet, which postdates the onset of the India-Eurasia collision, is usually considered to be derived from the partial melting of Lhasa thickened lower crust. However, less attention has been paid to the magma differentiation processes following the formation of the parental adakitic melts. Here, we use in situ zircon trace-element geochemistry, combined with whole-rock geochemical data, to gain insight into the magma differentiation and related mineralization of two phases of post-onset collision adakitic magmatism from the Nyemo location in the southern Lhasa subterrane. Systematic variations in zircon trace-element compositions record fractional crystallization of specific minerals (e.g., titanite, magnetite) for the ca. 30 Ma monzogranite and equilibrium crystallization for the ca. 15 Ma granodiorite. This is also supported by thermodynamic modeling, which revealed that the monzogranite and granodiorite magmas underwent weak differentiation (melt fraction up to ∼70%) or no differentiation, respectively. Progressively reduced oxygen fugacity conditions during magnetite fractionation in the monzogranitic magmas resulted in sulfide segregation, thereby removing sulfur and chalcophile elements such as Ni and Cu from the melt. Thus, we propose on the basis of in situ zircon trace-element geochemistry that magnetite fractionation within shallow to mid-continental crust may lead to the low Cu fertility of magmas, forming some of the Cu-poor post-onset collision adakitic rocks in the Gangdese magmatic belt.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Adakitic rock; Fractionation; Rhyolite-MELTS simulation; Tibet; Zircon geochemistry

Early Devonian Tectonic Conversion from Contraction to Extension in the Chinese Western Tianshan: A Response to Slab Rollback - Wang, Xin-Shui; Klemd, Reiner; Gao, Jun; Jiang, Tuo; Zhang, Xi (Geological Society of America Bulletin, 2021)
Extensive angular unconformities that occur across the Tianshan Orogen provide insight into the Paleozoic tectonic evolution of the southwestern Central Asian Orogenic Belt. This study presents new geochronological and geochemical data to unravel the age and origin of a pronounced angular unconformity in the Baluntai domain of the Chinese Western Tianshan. The angular unconformity separates a ductilely deformed metamorphic complex from overlying unmetamorphosed sequences. Detrital zircon age spectra suggest that the sedimentary samples received detritus from both the Precambrian basement and contemporaneous igneous rocks in the Central Tianshan and Yili blocks. The youngest detrital and metamorphic zircons in metasediments from the metamorphic complex reveal that their protoliths were deposited at ca. 419 Ma, and subsequently overprinted by metamorphism and ductile deformation at ca. 409 Ma. Along with ca. 532–407 Ma metavolcanics and foliated intrusions, the metamorphic complex constitutes a diachronous stratigraphic unit deposited during early Cambrian to late Silurian times, rather than a Precambrian basement as previously thought. The youngest detrital zircon age data from siliciclastic samples immediately above the angular unconformity constrain their deposition to ca. 407–397 Ma. In conjunction with a ca. 406 Ma rhyolitic tuff in the lower terrestrial siliciclastic unit and an early Carboniferous paleontological age of carbonates in the upper shallow-marine unit, it is suggested that the overlying unmetamorphosed sequences were accumulated during the early Devonian to the early Carboniferous. Thus, the angular unconformity in the Baluntai domain was formed between ca. 409 and 407 Ma. New and already published geochemical data reveal that the early Paleozoic (ca. 530–410 Ma) and late Paleozoic (ca. 410– 320 Ma) igneous rocks are mainly medium- to high-K calc-alkaline I-type granitoids, which exhibit typical subduction-related geochemical signatures despite contrasting structural features. These geochronological and geochemical results are in accordance with those of similar early Devonian angular unconformities and Paleozoic igneous rocks in the southern Yili Block. The early Paleozoic igneous rocks display highly scattered zircon εHf(t) values, while the late Paleozoic rocks show a progressively increasing trend toward more positive values, attributed to slab rollback of the northward subducting South Tianshan Ocean under the Yili and Central Tianshan blocks. Thus, we propose that the formation of the angular unconformity was caused by tectonic conversion from contraction to extension due to slab rollback during the early Devonian. This study highlights the significance of geological and geochronological investigations of angular unconformities in the context of associated episodic magmatism and slab behavior in order to unravel distinct tectonic processes in the long-lived accretionary evolution of the Chinese Western Tianshan.
CRIS-Team Scopus Importer:2021-07-30

Early Jurassic adakitic rocks in the southern Lhasa sub-terrane, southern Tibet: petrogenesis and geodynamic implications - Shui, Xinfang; He, Zhenyu; Klemd, Reiner; Zhang, Zeming; Lu, Tianyu; Yan, Lili (Geological Magazine, 2018)
Cretaceous–Miocene adakitic rocks in the southern Lhasa sub-terrane have been intensively investigated, while possible Early Jurassic adakitic rocks in this area have been largely neglected. Petrological and geochemical studies revealed adakitic affinities of an Early Jurassic quartz diorite intrusion with mafic enclaves and three tonalite bodies from the Jiacha area in the southern Lhasa sub-terrane. Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) zircon U–Pb dating suggests crystallization ages of 199–179 Ma for these rocks. Both quartz diorites and tonalites have typical adakitic geochemical characteristics such as high Al2O3 (15.14–18.22 wt.%) and Sr (363–530 ppm) contents, low Y (4.46–15.9 ppm) and Yb (0.51–1.74 ppm) contents and high Sr/Y ratios of 27–106. The adakitic quartz diorites are further characterized by high MgO (2.63–3.46 wt.%), Mg# (48–54) and ε Hf(t) (6.6–13.4) values, which were probably produced by partial melting of a subducted oceanic slab with a mantle contribution. The adakitic tonalites have very low abundances of compatible elements and relatively low ε Hf(t) values (3.5–10.3), and are interpreted to have formed by partial melting of Neoproterozoic mafic lower crust. Upwelling asthenosphere, triggered by rollback of the subducting Bangong–Nujiang (Meso-Tethys) oceanic plate, provided the necessary heat for slab and lower crust melting, resulting in the geochemical diversity of the coexisting felsic intrusive rocks. Contrary to other models, this study further demonstrates that the Bangong–Nujiang oceanic plate was subducted southward beneath the Lhasa terrane during the Early Jurassic.
Keywords: Adakitic rocks; slab melting; Early Jurassic; Bangong-Nujiang (Meso-Tethys) Ocean; southern Lhasa sub-terrane

Early Neoproterozoic granitic gneisses in the Chinese Eastern Tianshan: Petrogenesis and tectonic implications - Huang, Bo-Tao; He, Zhen-Yu; Zhang, Ze-Ming; Klemd, Reiner; Zong, Ke-Qing; Zhao, Zhi-Dan (Journal of Asian Earth Sciences, 2014)
Early Neoproterozoic granitic gneisses are known from several locations such as the Xingxingxia, Alatage and Baluntai areas in the Central Tianshan Arc Terrane of the Chinese Eastern Tianshan, which is one of several Precambrian microcontinents within the southern Central Asian Orogenic Belt (CAOB). The petrogenesis and the tectonic significance of the early Neoproterozoic granitic gneisses have not been well constrained yet, resulting in an ambiguous understanding of the early tectonothermal evolution of the Chinese Eastern Tianshan. Geochronological results suggest that the protoliths of these granitic gneisses formed during a relatively short time period between ca. 970 and 915 Ma, mainly clustering at ca. 940 Ma. These peraluminous to strongly peraluminous granitic rocks show a common geochemical S-type granite affinity, involving low CaO, Na2O, Th and Y contents. Zircon saturation thermometry and Ti-in-zircon thermometry yielded a relatively low crystallization temperature of approximately 750-800 °C for the magmatic protolith of the granitic gneisses. Zircon Hf isotopic compositions of the Xingxingxia and Alatage granitic gneisses show ε Hf(t) values of -5.4 to 4.2, with T DM2 model ages of 1.53-2.14 Ga, indicating that their protoliths were derived by the recycling of older continental crust. We suggest that the early Neoproterozoic granitic rocks in the Chinese Eastern Tianshan were formed along an active continental margin. Furthermore, we propose that the Central Tianshan Arc Terrane was located at the periphery of Rodinia and separated from the Tarim Craton terrane in the early Neoproterozoic. © 2014 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.earlyn
Keywords: CAOB; Central Tianshan Arc Terrane; Neoproterozoic; Rodinia supercontinent; S-type granite affinity

Early Neoproterozoic granitic gneisses in the Chinese Eastern Tianshan: Petrogenesis and tectonic implications - Huang, Bo-Tao; He, Zhenyu; Zhang, Zeming; Klemd, Reiner; Zong, Keqing; Zhao, Zhi-Dan (Journal of Asian Earth Sciences, 2015)
Early Neoproterozoic granitic gneisses are known from several locations such as the Xingxingxia, Alatage and Baluntai areas in the Central Tianshan Arc Terrane of the Chinese Eastern Tianshan, which is one of several Precambrian microcontinents within the southern Central Asian Orogenic Belt (CAOB). The petrogenesis and the tectonic significance of the early Neoproterozoic granitic gneisses have not been well constrained yet, resulting in an ambiguous understanding of the early tectonothermal evolution of the Chinese Eastern Tianshan. Geochronological results suggest that the protoliths of these granitic gneisses formed during a relatively short time period between ca. 970 and 915 Ma, mainly clustering at ca. 940 Ma. These peraluminous to strongly peraluminous granitic rocks show a common geochemical S-type granite affinity, involving low CaO, Na2O, Th and Y contents. Zircon saturation thermometry and Ti-in-zircon thermometry yielded a relatively low crystallization temperature of approximately 750–800 °C for the magmatic protolith of the granitic gneisses. Zircon Hf isotopic compositions of the Xingxingxia and Alatage granitic gneisses show εHf(t) values of −5.4 to 4.2, with TDM2 model ages of 1.53–2.14 Ga, indicating that their protoliths were derived by the recycling of older continental crust. We suggest that the early Neoproterozoic granitic rocks in the Chinese Eastern Tianshan were formed along an active continental margin. Furthermore, we propose that the Central Tianshan Arc Terrane was located at the periphery of Rodinia and separated from the Tarim Craton terrane in the early Neoproterozoic.<br
Keywords: CAOB; Central Tianshan Arc Terrane; Neoproterozoic; Rodinia supercontinent; S-type granite affinity

Early Palaeozoic deep subduction of continental crust in the Kyrgyz North Tianshan: Evidence from Lu-Hf garnet geochronology and petrology of mafic dikes. - Rojas-Agramonte, Yamirka; Herwartz, Daniel; Garcia-Casco, Antonio; Kroener, Alfred; Alexeiev, Dmitriy V.; Klemd, Reiner; Buhre, Stephan; Barth, Matthias (Contributions To Mineralogy and Petrology, 2013)
High-pressure and ultrahigh-pressure (UHP) eclogite-bearing metamorphic assemblages in the North Tianshan of Kyrgyzstan are known from the Aktyuz and Makbal areas, where eclogites and garnet amphibolites are associated with continental rocks such as granitoid gneisses in Aktyuz and shallow-water clastic (passive margin?) metasediments in Makbal. We present the first Lu-Hf isotope data for an eclogite and two garnet amphibolite samples from the two metamorphic terranes which, combined with petrological analysis, tightly constrain the age of high-pressure metamorphism in the Kyrgyz North Tianshan. A five-point isochron for an Aktyuz eclogite sample provides a Lu-Hf age of 474.3 ± 2.2 Ma, and a four-point isochron on a Makbal sample corresponds to 470.1 ± 2.5 Ma. A prograde, subduction-related path is inferred for both samples with peak P-T conditions ranging from 1.4 to 1.6 GPa and 610-620 °C. A further Makbal sample provided a significantly older Lu-Hf age of 486 ± 5.4 Ma, most likely due to late alteration in the sample (late addition of unradiogenic Hf). We conclude that garnet growth in all three samples occurred around ca. 474 Ma and that these rocks likely experienced UHP metamorphism contemporaneously. Our results support previous geochronological evidence for an Early Ordovician collision belt in the North Tianshan and allow refinement of a tectonic model involving subduction of thinned continental crust to considerable depth along the margin of a small microcontinent. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.c3geoc.earlyp
Keywords: Aktyuz; Kyrgyzstan; Lu-Hf; Mafic dike; Makbal; Northern Tianshan

Early Pleistocene banded iron-rich sedimentary rocks at Cape Vani, Milos Island, Greece: A modern analogue of Precambrian banded iron formations? - Sun, Si; Klemd, Reiner; Voudouris, Panagiotis (Sedimentary Geology, 2022)
The genesis of banded iron formations is commonly associated with anoxic and iron-rich (ferruginous) marine conditions throughout the Archean to Palaeoproterozoic, and occasionally in the Neoproterozoic. In recent studies, 2 million-year-old banded iron-rich sedimentary rocks with alternating Fe- and Si-rich bands occurring in the Cape Vani sedimentary basin on Milos island (Greece) were interpreted to be a modern analogue of Precambrian banded iron formations. This interpretation is mainly due to the discovery of photoferrotrophic-like filamentous fossils in massive iron-rich cherty beddings of another subbasin about 450 m to the south. In this study, we re-examined the stratigraphy and lithology of the Cape Vani basin, carried out detailed petrographic, mineralogical and geochemical investigations of the iron-rich sedimentary rocks, as well as volcaniclastic/volcanic conglomerates and banded hydrothermal veins that are in close spatial association with the iron-rich sedimentary rocks. The Fe2O3 content of the banded iron-rich sedimentary rocks ranges from 0.41 to 11.02 wt% (2.73 wt% on average), far lower than that required per definition for banded iron formations. In addition, the banded iron-rich sedimentary rocks contain substantial clastic materials. Samples with stronger silicification, however, usually contain less clastic materials. The non-clastic components occur as siliceous matrix comprising the same mineral assemblage as the banded hydrothermal veins. These components occur in the interspaces of the clastic materials, within cavities, microfractures and veins crosscutting the layers. Fe2O3, principally reflecting hematite, is intimately linked with the presence of non-clastic materials. Therefore, the non-clastic materials are interpreted as post-depositional products associated with silicification during later stage hydrothermal activities, rather than being syn-depositional as the minerals in Precambrian banded iron formations. Consequently, the Milos banded iron-rich sedimentary rocks cannot be an analogue of Precambrian banded iron formations, seeing their lithological and genetical differences. The geochemical results reveal that both the banded iron-rich sedimentary rocks and the massive iron-rich cherty beddings have the same clastic provenance as the volcaniclastics/volcanic conglomerates, but the massive iron-rich cherty beddings contain more hydrothermal contributions due to more intensive fluid-rock interaction. Thus, the two types of iron-rich sedimentary rocks are considered as clastic sedimentary rocks with varying degrees of hydrothermal overprinting. The massive iron-rich cherty beds were generally subjected to stronger hydrothermal overprinting, and, therefore, contain more siliceous matrix and Fe2O3. The enrichment of Fe is due to post-depositional hydrothermal fluid infiltration to the primary sediment piles. The primary layer planes of the banded iron-rich rocks, their interconnected pores and fractures provided preferential pathways for the hydrothermal fluids, and resulted in denser precipitation of Fe(III) (oxy)hydroxides and SiO2 cement therein. The alternating bands in the banded iron-rich sedimentary rocks, therefore, reflect cyclic permeabilities of the layers (i.e., primary sedimentary planes and porosities), rather than cyclic precipitation of Fe- and Si-minerals. This study also sheds light on an alternative formation mechanism for banded structures in Fe- and Si-rich sedimentary rocks similar to those of Precambrian banded iron formations.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Banded iron formation; Chemical sedimentary rock; Fe(III) precipitation; Hydrothermal fluids; Milos iron-rich sedimentary rock; Silicification

Effects of fluid boiling on Au and volatile element enrichment in submarine arc-related hydrothermal systems - Falkenberg, Jan; Keith, Manuel; Haase, Karsten; Bach, Wolfgang; Klemd, Reiner; Strauss, Harald; Yeo, Isobel A.; Rubin, Kenneth H.; Storch, Bettina; Anderson, Melissa O. (Geochimica Et Cosmochimica Acta, 2021)
Shallow (<1500 mbsl) submarine arc-related hydrothermal systems can host base (Cu), precious (Au) and volatile elements (As, Se, Sb, Te, Tl) in significant quantities. Their wide application in the high-tech industry, but a potential eco-toxicological footprint gives them a strategic importance. However, the processes that concentrate these elements in submarine arc-related hydrothermal systems, compared to their mid-ocean ridge counterparts are still debated, and it is unclear whether boiling-related processes and/or the contribution of magmatic volatiles are key for their enrichment. We present bulk sulfide, isotope (S and Pb), and high-resolution microanalytical data of hydrothermal sulfides from the Niua South fore-arc volcano in north Tonga, where numerous black-smoker type sulfide-sulfate chimneys emit boiling fluids with temperatures (up to 325°C) near the seawater boiling curve at ∼1170 m water depth. Hence, this system represents an ideal natural laboratory to investigate the effect of fluid boiling on base, precious, and volatile element enrichment associated with hydrothermal seafloor mineralization. At Niua South, textural and chemical variations of multiple pyrite (framboidal, euhedral and massive), chalcopyrite (linings), and sphalerite (dendrites and linings) generations are indicative for sulfide precipitation from early low-temperature (∼240°C) fluids that underwent abundant mixing with ambient seawater (low Se/Tl and Co/Ni ratios in pyrite) and from later high-temperature (up to 325°C) (high Se/Tl and Co/Ni ratios in pyrite). In addition, crustiform inclusion-rich pyrite that precipitated from high-temperature boiling fluids shows low Bi/Pb, Tl/Pb and Sb/Pb ratios due to volatile element loss (e.g., Tl and Sb) to the vapor phase compared to pyrite that formed during the low temperature stage. By contrast, late sphalerite (∼280°C) is enriched in elements with an affinity to Cl-complexes like Mn, Co, Ni, Ga, Cd, In, and Sn, and therefore precipitated from the corresponding Cl-rich liquid phase. Gold occurs in solid-solution and as boiling-induced particles of native Au, electrum, and Au-rich Bi-tellurides in pyrite (up to 144 ppm Au), sphalerite (up to 60 ppm Au), and chalcopyrite (up to 37 ppm Au). These particles (<5 – 10 µm) probably formed during fluid boiling causing an extreme Au enrichment (>30 ppm) in the mature and late stage of chimney formation. Lead isotope data indicate that the hydrothermal fluids scavenged metals not only from the deeper basement in the reaction zone (20 – 40 %), but also from young dacitic volcanic rocks near the seafloor in the upflow zone (60 – 80 %). Sulfur isotope (δ34S = -0.3 – 4.4 ‰) and Se/S*106 values (< 1500) of hydrothermal sulfides provide no evidence for a magmatic volatile influx and indicate that S, and most metals and semi-metals were likely leached from the host rocks. Hence, volatile (As, Se, Sb, Te, Tl), and precious (Au) element enrichments in arc-related submarine hydrothermal systems can be decoupled from magmatic volatiles and are instead a result of boiling-induced trace element fractionation – a hydrothermal enrichment process, which has been underestimated to date.<br

Effects of sulfate reduction processes on the trace element geochemistry of sedimentary pyrite in modern seep environments - Lin, Zhiyong; Sun, Xiaoming; Chen, Kaiyun; Strauss, Harald; Klemd, Reiner; Smrzka, Daniel; Chen, Tingting; Lu, Yang; Peckmann, Jorn (Geochimica Et Cosmochimica Acta, 2022)
Although it has been suggested that the trace element patterns of sedimentary pyrite can be affected by early diagenesis, detailed studies on modern marine environments addressing this hypothesis are scarce. Organoclastic sulfate reduction (OSR) and sulfate-driven anaerobic oxidation of methane (SD-AOM) are the dominant sulfate reduction processes in organic-rich and methane-rich marine sediments, and commonly result in the formation of authigenic pyrite. To better understand how OSR and SD-AOM affect the trace element geochemistry of pyrite, we applied laser ablation – inductively coupled plasma – mass spectrometry (LA-ICP-MS) to analyze trace element contents of pyrite from two methane-seep sites (DH-CL11 and HS148) of the South China Sea. The trace element data are complemented by the measurement of iron isotope compositions of authigenic pyrite. This new data set, supplemented by published sulfur isotope data, improves our understanding of the diagenetic processes during early diagenetic pyrite formation. High δ56Fe and δ34S values of pyrite reflect the dominance of SD-AOM within sulfate-methane transition zones (SMTZs) at both sites (i.e., from 705 to 767 cm below seafloor at site DH-CL11 and from 490 to 690 cm below seafloor at site HS148), whereas pyrite from shallow depth characterized by low δ56Fe values points to early OSR processes. Within the SMTZs, pyrite exhibits highly variable but overall high manganese (Mn) contents (12 to 732 mg/kg at site DH-CL11; 12 to 1145 mg/kg at site HS148), compared to OSR-derived pyrite from shallow depth. Similar to this pattern, pyrite formed at the SMTZ shows higher lead (Pb), zinc (Zn), copper (Cu), and vanadium (V) contents than pyrite formed at shallower depths above the SMTZ. Enrichments of these metals in pyrite forming at the SMTZ are best explained by enhanced reductive dissolution of iron and manganese (oxyhydr)oxides under sulfidic conditions induced by SD-AOM, and subsequent trace element incorporation into pyrite. Arsenic (As), molybdenum (Mo), and antimony (Sb) distributions in pyrite vary between the two study sites. Pyrite from shallow depth of site HS148 has high contents of all three elements, indicating effective immobilization of dissolved As, Mo, and Sb during pronounced OSR. In contrast, apparently less intense OSR at shallow depth of site DH-CL11 allowed for more dissolved As, Mo, and Sb to diffuse downward to greater depth, resulting in the enrichments of these elements in pyrite formed at or close to the SMTZ. Positive correlations between As and cobalt (Co), and between As and nickel (Ni) typify pyrite derived from both OSR and SD-AOM for both study sites, and As-rich pyrite from site DH-CL11 is characterized by a distinctly high Co/Ni ratio. Both patterns suggest that the presence of As affects the uptake of Co and Ni into pyrite. Our study documents that pyrite element contents in methane-rich environments are significantly influenced by different sulfate reduction processes during early diagenesis, allowing the differentiation of OSR-derived pyrite from SD-AOM-derived pyrite by means of trace element geochemistry.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Authigenic pyrite; Organoclastic sulfate reduction; Seawater geochemistry; Sulfate-driven anaerobic oxidation of methane; Trace elements

Effects of temperature, sulfur, and oxygen fugacity on the composition of sphalerite from submarine hydrothermal vents - Keith, Manuel; Haase, Karsten; Schwarz-Schampera, Ulrich; Klemd, Reiner; Petersen, Sven; Bach, Wolfgang (Geology, 2014)
Experimental studies have shown that temperature, pressure, sulfur fugacity (fS2), and oxygen fugacity (fO2) influence the Fe content of sphalerite. We present compositional in situ data on sphalerite from submarine volcanic-hosted massive sulfide (VHMS) ores of hydrothermal vents from different plate tectonic settings and with variable host-rock compositions. Sphalerite from sediment-hosted vents has systematically higher S contents and Fe/Zn ratios than those of the sediment-starved vents, reflecting an influence of fS2 and fO2 on Fe partitioning between fluid and sphalerite. The Fe/Zn ratios of sphalerite from sediment-starved vent systems apparently increase systematically with the fluid temperatures of the corresponding vents. We conclude that the composition of sphalerite can be used to (1) distinguish between sediment-hosted and sediment-starved hydrothermal processes, and (2) estimate minimum fluid temperatures of sphalerite precipitation from inactive sediment-starved hydrothermal vent sites and fossil VHMS deposits. © 2014 Geological Society of America.
UnivIS-Import:2015-04-14:Pub.2014.nat.dgeo.IGM.c3geoc.effect

Evolution of Nb-mineralization in the Chuktukon carbonatite massif, Chadobets upland (Krasnoyarsk Territory, Russia) - Chebotarev, Dmitry; Doroshkevich, Anna G.; Klemd, Reiner; Karmanov, Nikolay (Periodico Di Mineralogia, 2017)
This paper reports on new study of the niobium mineralization of the Chuktukoncarbonatites and weathering crust. The Chuktukon massif is located within the Chadobets upland in the southwestern part of the Siberian Platform. Primary Nb-minerals of carbonatites are pyrochlore group minerals (mainly fluorcalciopyrochlore),newly discovered mineral - rippite [K2(Nb,Ti)2(Si4O12)O(O,F)], and Nb-rutile.Fluorcalciopyrochlore has oscillatory zonation with variations in content of Nb2O5 (59- 67 wt%), TiO2 (2.8-5 wt%), SiO2 (up to 3.3 wt%), CaO (15.9-17.7 wt%), Na2O (7-8.2 wt%) and F (4.5-5.13 wt%). Rippite is Nb-rich silicate ( 44 wt% of Nb2O5) andcontains inclusions of primary fluorcalciopyrochlore. Nb-rutile form oscillatory and sectorial hourglass-like zoned crystals with variable content of Nb2O5 (9-14.7 wt%). The carbonatites underwent strong hydrothermal alteration and subsequent weathering, and, as a result, in the hydrothermally altered carbonatites and weathering crust the primary Nb-minerals become unstable, dissolve and decompose, and Nb-bearing goethite (up to 4.3 wt% of Nb2O5) formed. Primary fluorcalciopyrochlore is replaced by the secondary Sr-, Pb-, LREE- and Ba-rich pyrochlore group minerals.
Keywords: pyrochlore; rippite; rutile; goethite; carbonatite; carbonatite deposit; weathering crust; Krasnoyarsk territory; niobium

Final Assembly of the Southwestern Central Asian Orogenic Belt as Constrained by the Evolution of the South Tianshan Orogen: Links With Gondwana and Pangea - Wang, Xin-Shui; Klemd, Reiner; Gao, Jun; Jiang, Tuo; Li, Jilei; Xue, Shengchao (Journal of Geophysical Research. Solid Earth, 2018)
The South Tianshan Orogen marks the final assembly of the southwestern Central Asian Orogenic Belt (CAOB) and the Karakum–Tarim cratons. Here we present an integrated mineralogical, geochemical, and geochronological study of the Wuwamen ophiolitic mélange in the South Tianshan to better understand the tectonic evolution of the western CAOB and its links to Gondwana and Pangea. Mantle peridotites with mineral compositions similar to those of abyssal peridotites and basalts with N‐MORB geochemical affinities suggest that the Wuwamen ophiolite was formed in a mid‐ocean ridge setting. Arc‐related gabbro and plagiogranite stocks intruding the mantle peridotites yielded zircon U–Pb ages of 441.1 ± 4.2 and 442.8 ± 2.4 Ma, indicating that the Wuwamen ophiolite got emplaced prior to 440 Ma. Sericite‐quartz schist from the ophiolitic mélange matrix with abundant 481–319 Ma detrital zircon grains is crosscut by a two‐mica granite dike with a zircon U–Pb age of 321.3 ± 1.7 Ma, thereby constraining the formation of the Wuwamen ophiolitic mélange at 320 Ma. In conjunction with published data, we propose that the South Tianshan Ocean opened in the late Neoproterozoic and promoted the subsequent separation of microcontinents in the western CAOB from the northeast Gondwana margin during Gondwana assembly. Furthermore, the closure of the South Tianshan Ocean led to the final assembly of the southwestern CAOB and the Karakum–Tarim cratons and their incorporation into Pangea at 320 Ma.<br
Keywords: Central Asian Orogenic Belt; Tianshan; Wuwamen ophiolite; Gondwana; Pangea

Fingerprinting fluid evolution by trace elements in epithermal pyrite, Vatukoula Au-Te deposit, Fiji - Börner, Frederik; Keith, Manuel; Smith, Daniel J.; Barry, Tiffany L.; Neumann, Thomas; Klemd, Reiner (Ore Geology Reviews, 2021)
Tellurium (Te) is an important element for green technologies, including thin film photovoltaic panels. Stagnating supply caused by its by-product dependency together with an increasing demand will likely lead to a shortage in the near future. Pyrite may represent a potential target for the direct recovery of Te, since the concentrations of Te can reach weight percent levels under specific, but poorly constrained hydrothermal conditions. The Vatukoula (formerly Emperor) epithermal Au-Te deposit is currently mined for Au and 75% are recovered from Au-tellurides and pyrite. Tellurium has been processed in the past, but is now sent to tailings despite of concentrations reaching 1.4 wt. % in pyrite, which makes this system a natural laboratory to investigate key Te enrichment processes. The epithermal mineralisation at Vatukoula consists of an early low-grade disseminated host-rock and a later high-grade Ag-Au-Te vein-type stage. Pyrite occurs in both ore-types with diverse As contents including concentrations < 0.5 wt. % in pure pyrite, 0.5 to 13 wt. % in low-As and 23 to 43 wt. % in high-As pyrite, reflecting increasing fluid As with system evolution towards the high-grade mineralisation. Tellurium contents in pyrite increase from pure pyrite (up to 220 ppm) to low-As pyrite (up to 1.4 wt. %), but with a decrease towards high-As pyrite (up to 185 ppm). This is a yet unknown relation, since trace element incorporation in pyrite is usually facilitated by increasing As. Instead, the presented results suggest a threshold between 13 and 23 wt. % As, above which the incorporation of Te and related elements (e.g., Ag, Au) may be less favourable. Mineral stabilities, trace element ratios (e.g., Sb/Pb, Tl/Pb) and LA-ICP-MS mapping of texturally distinct pyrite indicate that fluid boiling was a critical process for the Ag, Au and Te enrichment in the Vatukoula epithermal system. Fluid sulphidation states decreased with proceeding evolution of the epithermal system from initially intermediate- to late low-sulphidation conditions, which led to the diverse chemical character of pyrite. Early pure pyrite primarily formed as a replacement product of magnetite in the altered host rocks, whereas low- and high-As pyrite precipitated in the direct vicinity of Ag-Au-telluride veins, from which most of the As, Ag, Te and Au hosted in pyrite was derived from. Consequently, the trace element composition of pyrite allows the fingerprinting of the fluid evolution of Te-rich ore-forming systems like Vatukoula, Fiji.
Created from Fastlane, Scopus look-up
Keywords: As-Te incorporation; Epithermal alkaline hosted; LA-ICP-MS; Pyrite; Solid-solution; Vatukoula

Fluid Inclusions and Stable Isotopic Characteristics of the Yaoling Tungsten Deposit in South China: Metallogenetic Constraints - Yang, Feng; Zhai, Wei; Sun, Xiaoming; Klemd, Reiner; Sun, Yanyan; Wu, Yunshan; Hua, Renmin; Zheng, Siqi (Resource Geology, 2019)
The Yaoling tungsten deposit is a typical wolframite quartz vein-type tungsten deposit in the South China metallogenic province. The wolframite-bearing quartz veins mainly occur in Cambrian to Ordovician host rocks or in Mesozoic granitic rocks and are controlled by the west-north-west trending extensional faults. The ore mineralization mainly comprises wolframite and variable amounts of molybdenite, chalcopyrite, pyrite, fluorite, and tourmaline. Hydrothermal alteration is well developed at the Yaoling tungsten deposit, including greisenization, silicification, fluoritization, and tourmalinization. Three types of primary/pseudosecondary fluid inclusions have been identified in vein quartz, which is intimately intergrown with wolframite. These include two-phase liquid-rich aqueous inclusions (type I), two- or three-phase CO2-rich inclusions (type II), and type III daughter mineral-bearing multiphase high-salinity aqueous inclusions. Microthermometric measurements reveal consistent moderate homogenization temperatures (peak values from 200 to 280 degrees C), and low to high salinities (1.3-39 wt % NaCl equiv.) for the type I, type II, and type III inclusions, where the CO2-rich type II inclusions display trace amounts of CH4 and N-2. The ore-forming fluids are far more saline than those of other tungsten deposits reported in South China. The estimated maximum trapping pressure of the ore-forming fluids is about 1230-1760 bar, corresponding to a lithostatic depth of 4.0-5.8 km. The delta D-H2O isotopic compositions of the inclusion fluid ranges from -66.7 to -47.8 parts per thousand, with delta O-18(H2O) values between 1.63 and 4.17 parts per thousand, delta C-13 values of -6.5-0.8 parts per thousand, and delta S-34 values between -1.98 and 1.92 parts per thousand, with an average of -0.07 parts per thousand. The stable isotope data imply that the ore-forming fluids of the Yaoling tungsten deposit were mainly derived from crustal magmatic fluids with some involvement of meteoric water. Fluid immiscibility and fluid-rock interaction are thought to have been the main mechanisms for tungsten precipitation at Yaoling.
CRIS-Team WoS Importer:2019-04-09
Keywords: fluid inclusion; immiscibility; stable isotope; Yaoling tungsten deposit

Fluid-mediated metal transport in subduction zones and its link to arc-related giant ore deposits: Constraints from a sulfide-bearing HP vein in lawsonite eclogite (Tianshan, China). - Li, Jilei; Gao, Jun; John, Timm; Klemd, Reiner; Su, Wen (Geochimica Et Cosmochimica Acta, 2013)
High-pressure (HP) veins in eclogites provide insight into element mobility during fluid-rock interaction in subduction zones. Here, we present a petrological-geochemical study of a sulfide-bearing HP vein and its massive lawsonite eclogite host rock from the Chinese Tianshan (ultra-)high-pressure/low-temperature metamorphic belt. The omphacite-dominated vein is enveloped by a garnet-poor, sulfide-bearing eclogite-facies reaction selvage. Lawsonite, garnet, omphacite, glaucophane and other HP minerals occur as inclusions in pyrite porphyroblasts of the selvage rock, indicating that the selvage formed prograde under eclogite-facies conditions. Relicts of wall-rock garnet (Grt_I) cores in recrystallized selvage garnet (Grt_II) close to the wall rock and the Ca distribution in Grt_II, which images the overgrown selvage matrix, indicate that the selvage formed due to dissolution-precipitation processes as a consequence of fluid-rock interaction of the wall rock eclogite with the vein-forming fluid. The peak metamorphic P-T conditions of the wall-rock eclogite are estimated at ca. 590. °C and 23. kbar. Mass-balance calculations indicate that the reaction selvage experienced: (1) a depletion of the large-ion lithophile elements (K-Rb-Ba) of up to 100% relative to their concentrations in the wall-rock eclogite; (2) a moderate depletion of the HREE and some transition metal elements including Fe, Cu, Ni, Zn, Co, Cr, and Mn (10-40%); (3) a significant enrichment of CaO (up to 50-80%), Sr (up to 200%), Pb (up to 170%) and S (up to 210%); (4) a slight to moderate enrichment of the LREE (10-20%) and MREE (0-40%); whereas (5) the HFSE show no significant variations.The chemical changes in the selvage suggest that the fluid, which caused the dissolution of the wall-rock and the precipitation of the selvage assemblage while the vein formed, was probably a mixture of an "internal" fluid derived from the prograde dehydration (e.g., lawsonite breakdown) of the wall rock and an "external" fluid most likely derived from dehydrating altered oceanic crust located in stratigraphically lower units of the subducting slab. The external fluid introduced Ca, S, Sr, Pb and at least parts of the LREE and the MREE into the selvage, whereas some elements, such as the remaining LREE and MREE, may have been derived from the wall rock eclogite via diffusional transport into the selvage. The enrichment of Ca and L-MREE is displayed by the abundant growth of selvage epidote. In contrast, the dissolution of garnet and phengite released significant amounts of HREE and LILE (K-Rb-Ba) into the passing fluid, because the chemical changes within the selvage prevented the formation of a mineral assemblage with sufficiently high bulk-fluid partition coefficients for these elements. Significant amounts of transitional metal elements were released into the fluid during the dissolution of white mica and the dissolution-precipitation behavior of garnet, omphacite, dolomite and sulfides. Thus the LILE and HREE along with some transition metal elements (e.g., Fe, Cu, Ni and Zn) were mobilized during the dissolution-precipitation processes that led to the selvage formation. Accordingly the slab fluids are not only strongly enriched in LILE and depleted in HFSE, but also carry significant amounts of transition metals. It is most likely that slab fluids strongly contribute to the metal flux into the arc magma systems finally resulting in giant arc-related ore deposits. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.c3geoc.fluidm

Formation conditions and REY enrichment of the 2060 Ma phosphorus mineralization at Schiel (South Africa): geochemical and geochronological constraints - Graupner, Torsten; Klemd, Reiner; Henjes-Kunst, Friedhelm; Goldmann, Simon; Behnsen, Helge; Gerdes, Axel; Dohrmann, Reiner; Barton, J. M.; Opperman, Rehan (Mineralium Deposita, 2018)
Rocks of the rare-earth element (REY)-enriched apatite deposit in the eastern part of the Schiel Alkaline Complex (SAC; Southern Marginal Zone, Limpopo Belt) were studied for their whole-rock and mineral chemistry, REY mineral distribution and geochronology. Apart from phoscorite (sensu lato), pyroxenite and various syenitic rock types with quite variable apatite contents display P-REY enrichments. Field observations, mineralogical composition as well as major and trace element chemistry of soils make it possible to constrain the distribution of the hidden P-REY-rich rock types in the apatite deposit. Uranium-lead ages of zircon from phoscorite (sensu lato) and syenite are in the range of 2.06–2.05 Ga. Samarium-neodymium (εNd(t) −8.6 to −6.0) and in part Rb-Sr (87Sr/86Sr(t) 0.70819–0.70859) isotope data for whole-rock samples and mineral separates indicate an origin from an isotopically enriched and slightly variable source. Fluorapatite, early allanite and titanite are the main REY carriers at Schiel. Fluorapatite dominates the REY budget of pyroxenite and phoscorite, whereas early allanite hosts most of the REY in syenite. Three apatite types are distinguished based on their occurrence in the rocks, REYtotal contents and colouration in cathodoluminescence microscopy. Magmatic apatite in pyroxenite and in phoscorite (sensu lato) as well as early stage type I/II apatite in syenitic rocks have moderate to high REYtotal abundances (up to 3.2 wt%) with the mineral enriched in light REE. Early ferriallanite-(Ce) is strongly enriched in light REE and shows very high REYtotal values (13.7–26.4 wt%), while late allanite has lower REYtotalconcentrations (6.9–14.9 wt%). Titanite is abundant in most syenitic rocks (REYtotal 1.7–6.4 wt%); chevkinite-(Ce) occurs locally and contributes to an REY enrichment in contact aureoles between syenite and different lithologies. Apatite-enriched rocks in the SAC in part contain significantly higher REYtotal concentrations in apatite grains compared to those in apatite-mineralized pyroxenite, phoscorite and carbonatite from Phalaborw
Keywords: Schiel Alkaline Complex; Apatite-mineralized rocks; Soil geochemistry; Rare-earth elements; U-Pb; Lu-Hf; Sm-Nd and Rb-Sr isotopic compositions; Cathodoluminescence

Formation of the Vergenoeg F-Fe-REE deposit (South Africa) by accumulation from a ferroan silicic magma - Brandt, Sönke; Klemd, Reiner; Haase, Karsten; Faßbender, Marc Lorin; Vennemann, Torsten (Journal of Petrology, 2020)

From arc accretion to continental collision in the eastern Jiangnan Orogen: Evidence from two phases of S-type granites - Wang, Xin-Shui; Gao, Jun; Klemd, Reiner; Jiang, Tuo; Zhai, Qing-Guo; Li, Ji-Lei; Liang, Xin-Quan (Precambrian Research, 2019)
The NE Jiangxi ophiolitic m lange separates the Huaiyu and Jiuling terranes in the eastern Jiangnan Orogen of the South China Block. Two phases of S-type granites, which are geochemically and mineralogically similar to the Himalayan leucogranites, are newly recognized in mantle peridotites of the NE Jiangxi ophiolite. The first phase, a tourmaline-bearing granite porphyry, has a SIMS zircon U-Pb age of 904.4 +/- 4.8 Ma and is strongly enriched in K2O (4.00-4.26 wt%) and strongly peraluminous (A/CNK = 2.94-3.24). It further shows high Rb/Sr ratios and highly fractionated REE patterns, indicating an origin due to fluid-absent melting of metapelites at relatively high temperatures. The granite porphyry exhibits highly evolved zircon Hf ( -6.0 to -1.0) and whole rock Nd ( -4.2 to -5.1) isotopes, which is in contrast to juvenile-derived magmatic rocks in the Huaiyu Terrane. We thus propose that the granite porphyry was formed by melting of the metapelites sourced from the Yangtze Block subsequent to the accretion of the Huaiyu arc to the Jiuling Terrane (the continental margin of the Yangtze Block). The second phase, a muscovite-bearing quartz porphyry, is strongly peraluminous (A/CNK = 1.29-1.34) with low CaO/Na2O ratios (0.11-0.14) and low FeOt + MgO + TiO2 contents (2.39-2.75 wt%), similar to melts derived from fluid-fluxed melting of metapelites. Zircon grains from the quartz porphyry yielded U-Pb ages of ca. 803-801 Ma with mainly positive epsilon(tif)(t) values ( + 1.9 to + 8.7), which are younger than the depositional ages of the basement sequences and nearly identical to the accumulation of the overlying unmetamorphosed cover in the Jiangnan Orogen. Therefore, it is suggested that the quartz porphyry was formed in a post-collisional extensional setting subsequent to the final assembly of the Yangtze and Cathaysia blocks. In conjunction with published data, we conclude that multiple subduction-accretion events may have been involved in the formation of the South China Block during Neoproterozoic times.
CRIS-Team WoS Importer:2019-02-21

Genetically and geochronologically contrasting plagiogranites in Sotu Central Tianshan ophiolitic melanges: Implications fort he breakup of Rodinia and subduction zone processes - Jiang, Tuo; Gao, Jun; Klemd, Reiner; Qian, Qing; Zhang, Xi; Wang, Xinshui; Tan, Zhou; Zhu, Zhixin (Journal of Asian Earth Sciences, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.geneti

Genetically and geochronologically contrasting plagiogranites in South Central Tianshan ophiolitic mélange: Implications for the breakup of Rodinia and subduction zone processes - Jiang, Tuo; Gao, Jun; Klemd, Reiner; Qian, Qing; Zhang, Xi; Wang, Xin-Shui; Tan, Zhou; Zhu, Zhixin (Journal of Asian Earth Sciences, 2015)
Plagiogranites are exposed as exotic blocks at two localities (Wuwamen and Guluogou) in the South Central Tianshan ophiolitic mélange and have U–Pb zircon ages of 775 ± 11 Ma and 416 ± 4 Ma, respectively. The Wuwamen plagiogranites have low-K tholeiitic to medium-K calc-alkaline and weakly peraluminous compositions. They further display relatively low concentrations of total rare earth elements (REEs), pronounced positive Eu anomalies and distinct depletions of P and Ti. The trace element characteristics, whole-rock initial 87Sr/86Sr ratios from 0.708812 to 0.708839 and negative εNd(t) values from −6.4 to −6.2 suggest that the granitic magma was derived from low degree partial melting of amphibolites at middle to lower crustal levels with hornblende as the dominant residual phase. In contrast, the Guluogou plagiogranites are strongly peraluminous and are characterized by an enrichment of both large ion lithophile elements (LILEs) and light rare earth elements (LREEs). Negative anomalies of Nb, Ta, P and Ti are in accordance with the geochemical signature of Andean arc-type granites. The zircon εHf(t) values from −6.1 to +2.4, the corresponding two-stage Hf model ages (TDMC = 1259–1798 Ma) and the εNd(t) values from −5.0 to −2.9 favor partial melting of ancient continental crust, which was contaminated by some juvenile material from a depleted-mantle wedge, for the origin of the Guluogou plagiogranites. Thus, we conclude that the Wuwamen and Guluogou plagiogranites have no direct genetic relationship with the ophiolites and occur as exotic blocks in the ophiolitic mélanges. It is further suggested that the 775 Ma Wuwamen plagiogranites originated during the breakup of Rodinia, whereas the 416 Ma Guluogou plagiogranites were generated in an Andean-type active continental margin environment related to the northward subduction of the South Tianshan Ocean.<br
Keywords: Geochemistry; Geochronology; Plagiogranite; South Central Tianshan ophiolitic mélange; Subduction; Rodinia

Geochemical and geochronological evidence for a former early Neoproterozoic microcontinent in the South Beishan Orogenic Belt, southernmost Central Asian Orogenic Belt - Yuan, Yu; Zong, Keqing; He, Zhenyu; Klemd, Reiner; Liu, Yongsheng; Hu, Zhaochu; Guo, Jingliang; Zhang, Zeming (Precambrian Research, 2015)
The South Beishan Orogenic Belt (SBOB) in the southwestern Central Asian Orogenic Belt (CAOB) is thought to be an eastern extension of the Eastern Tianshan Orogen. Up to now, it has been suggested to consist of a well-preserved Paleozoic magmatic and sedimentary sequence with a possible former Neoproterozoic microcontinent. We provide new geochemical and geochronological data for gneissic granites of the SBOB in order to constrain its tectonic evolution and setting. The gneissic granitoids belong to the high-K, calc-alkaline series and are characterized by an enrichment of light rare earth elements (LREE) and large ion lithophile elements (LILE), a depletion of Nb, Ta, Ti, Sr, and Ba and a positive Pb anomaly. The petrography and geochemical signatures reveal a possible I-type granite affinity and are in accordance with typical Andean Arc granites. Zircon grains, yielding 206Pb/238U magmatic crystallization ages of 933 ± 2 Ma and 900–890 Ma for the Shibanshan and Huaniushan arc granites, respectively, manifest the former presence of an early Neoproterozoic Precambrian microcontinent in the SBOB. Zircon ɛHf(t) values range from −16.1 to 10.2, indicating that juvenile material and reworked ancient crust were involved in the source of the gneissic granites. Furthermore, in conjunction with studies of the adjacent regions, the results of the present study suggest that the former Precambrian microcontinent in the SBOB neither belonged to the nearby Dunhuang Block nor the Tarim Craton, but has a common affinity with the Central Tianshan Arc Terrane. It is also suggested that the 900–890 Ma plutons originated from the mixing of juvenile material with older crust in an Andean-type active continental arc setting during the assembly of Rodinia. Thus the SBOB plays a key role in understanding the tectonic evolution of the CAOB.
Keywords: South Beishan Orogenic Belt (SBOB); Central Asian Orogenic Belt (CAOB); Neoproterozoic microcontinent; Zircon U-Pb dating; Assembly of Rodinia

Geochemical and geochronological studies of granitoid rocks from the Western Tianshan Orogen: Implications for continental growth in the southwestern Central Asian Orogenic Belt. - Long, Lingli; Gao, Jun; Klemd, Reiner; Beier, Christoph; Qian, Qing; Zhang, Xi; Wang, Jingbin; Jiang, Tuo (Lithos, 2011)
The Western Tianshan Orogen in northwestern China is part of the southwestern margin of the Central Asian Orogenic Belt (CAOB), which represents the largest tectonic assembly of accretionary complexes and the most significant area of Phanerozoic continental growth in the world. Granitoid rocks have a widespread occurrence and occupy about 30% of the whole exposure of the orogen. Ages obtained for the granitoids vary from 896Ma to 247Ma, while initial 87Sr/86Sr ratios vary from 0.70329 to 0.72070 and εNd values from -14.1 to +7.3. The occurrence of Neoproterozoic granitic gneisses implies the presence of Precambrian basement in this area. During oceanic subduction, continental growth occurred as a result of several combined processes, i.e. by addition of oceanic crustal melts (adakites), the intrusion of basaltic magmas derived by partial melting of the metasomatized depleted mantle wedge and the upwelling of granitic magma derived from a mixed source of basaltic magmas and old continental basement. However, during the post-collisional period, vertical accretion of underplated juvenile mantle material may have been accomplished during 'slab breakoff' delamination. This study suggests a two stage model of continental growth of 'syn-subduction lateral accretion of arc complexes' and 'post-collisional vertical accretion of underplated mantle material', which may also be relevant for the western segment of the CAOB in the Phanerozoic. The reworking and involvement of old crust are more obvious in the Western Tianshan Orogen compared to other parts of the CAOB comprising the Western Junggar, Eastern Junggar, Alataw and Altay terranes. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.c3geoc.geoche
Keywords: Continental growth; Granitoid rocks; Sr-Nd isotope; Tianshan; Zircon U-Pb age

Geochemical constraints on the link between volcanism and plutonism at the Yunshan caldera complex, SE China - Yan, Lili; He, Zhenyu; Beier, Christoph; Klemd, Reiner (Contributions To Mineralogy and Petrology, 2018)
Keywords: Crystal mush; Magma differentiation; Peralkaline rhyolite; Quartz monzonite; Yunshan caldera complex; Zircon Hf–O isotopes

Geochemical evidence for Paleozoic crustal growth and tectonic conversion in the Northern Beishan Orogenic Belt, southern Central Asian Orogenic Belt - Yuan, Yu; Zong, Keqing; He, Zhenyu; Klemd, Reiner; Jiang, Hongying; Zhang, Wen; Liu, Yongsheng; Hu, Zhaochu; Zhang, Zeming (Lithos, 2018)
The Beishan Orogenic Belt is located in the central southernmost part of the Central Asian Orogenic Belt (CAOB), which plays a key role in understanding the formation and evolution of the CAOB. Granitoids are the documents of crustal and tectonic evolution in orogenic belts. However, little is known regarding the petrogenesis and geodynamic setting of the widely distributed Paleozoic granitoids in the Northern Beishan Orogenic Belt (NBOB). The present study reveals significant differences concerning the petrogenesis and tectonic setting of early and late Paleozoic granitoids from the NBOB. The early Paleozoic granitoids from the 446–430 Ma Hongliuxia granite complex of the Mazongshan unit and the 466–428 Ma Shibanjing complex of the Hanshan unit show classic I-type granite affinities as revealed by the relative enrichment of LILEs and LREEs, pronounced depletions of Nb, Ta and Ti and the abundant presence of hornblende. Furthermore, they are characterized by strongly variable zirconεHf(t) values between − 16.7 and + 12.8 and evolved plagioclase Sr isotopic compositions of 0.7145–0.7253, indicating the involvement of both juvenileand ancient continental crust in the magma source. Thus, we propose that the early Paleozoic granitoids in the NBOB were generated in a subduction-related continental arc setting. In contrast, the late Paleozoic 330–281 Ma granitoids from the Shuangjingzi complex of the Hanshan unit exhibit positive zircon εHf(t) values between + 5.8 and + 13.2 and relatively depleted plagioclase Sr isotopic compositions of 0.7037–0.7072, indicating that they were mainly formed by remelting of juvenile crust. Thus, an intra-plate extensional setting is proposed to have occurred during formation of the late Paleozoic granitoids. Therefore, between the early and late Paleozoic, the magma sources of the NBOB granitoids converted from the reworking of both juvenile and ancient crusts during a subduction-induced compressional setting to the remelting of juvenile crust during an intra-plate extensional setting, respectively. The corresponding crustal growth in the southern CAOB is dominated by early Paleozoic lateral accretion of arc complexes and late Paleozoic vertical addition of juvenile material from the mantle.
Keywords: Paleozoic granitoids; Crustal growth; Tectonic conversion; Northern Beishan Orogenic Belt; Central Asian Orogenic Belt (CAOB)

Geochemistry and geochronology of a Precambrian high-grade metamorphic complex in an ophiolitic mélange of the Central Tianshan Arc Terrane, NW China - Wang, Xin-Shui; Gao, Jun; Klemd, Reiner; Jiang, Tuo; Li, Ji-Lei; Zhang, Xi; Tan, Zhou; Li, Le; Zhu, Zhixin (Precambrian Research, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.geoche

Geochemistry and geochronology of the Precambrian high-grade metamorphic complex in the Southern Central Tianshan ophiolitic mélange, NW China - Wang, Xin-Shui; Gao, Jun; Klemd, Reiner; Jiang, Tuo; Li, Ji-Lei; Zhang, Xi; Tan, Zhou; Li, Le; Zhu, Zhixin (Precambrian Research, 2014)
The Central Tianshan Arc Terrane is one of the major constituents of the Tianshan orogen in the southwestern Altaids. Thus its Precambrian evolution is important for unravelling the geodynamic and continental evolution of the Altaids. Biotite-plagioclase-hornblende orthogneisses intruded by leucogranite dykes are exposed as exotic blocks within the Southern Central Tianshan ophiolitic mélange. Zircon U–Pb age dating of one orthogneiss sample yields an upper intercept age of 2466 ± 51 Ma and a weighted mean 207Pb/206Pb age of 1812 ± 19 Ma around the lower intercept. These ages are interpreted as protolith crystallization age and subsequent metamorphic overprint age, respectively. The orthogneisses have moderate SiO2 contents, high MgO and Na2O contents, high Sr/Y ratios (32–43) and moderately fractionated REE patterns ([La/Yb]N = 7.59–13.64) with negligible Eu anomalies, enriched Sr contents and pronounced negative Th–U, Nb–Ta, Zr–Hf and Ti anomalies resembling high-SiO2 TTGs derived from subducted basaltic slab-melts. Positive ɛHf(t) values (+3.4 to +9.2) and low (176Hf/177Hf)i ratios (0.281304–0.281469) with Neoarchaean to early Paleoproterozoic single-stage Hf model ages (TDM1 = 2431–2652 Ma) suggest that the orthogneisses probably originated from partial melting of juvenile subducted oceanic crust. The orthogneisses were subsequently also affected by collisional orogenic events associated with the assembly of the supercontinent Columbia. In contrast, the zircon U–Pb age of 785 ± 15 Ma obtained for the intrusive leucogranite dykes is consistent with the timing of rifting events associated with the breakup of Rodinia. The leucogranites have a high-Al trondhjemitic composition characterized by extremely low MgO and K2O contents as well as high SiO2, Al2O3 and Na2O contents, dramatically low ∑REE abundances and REE patterns with moderate LREE enrichments ([La/Yb]N = 3.55–8.4) and pronounced positive Eu anomalies (Eu/Eu* = 1.29–2.61). The high zircon initial Hf compositions (0.281670–0.281841) and negative ɛHf(t) values (−21.7 to −15.4), in conjunction with high whole-rock initial 87Sr/86Sr ratios (0.70737–0.70751) and negative ɛNd(t) values (−4.7 to −5.1) suggest that the leucogranite resulted from reworking of ancient lower crust. Based on the presented data we conclude that the Central Tianshan Arc Terrane has undergone three tectonothermal events, namely ∼2.5 Ga continental crustal growth, ∼1.8 Ga collision related to the Columbia assembly and ∼785 Ma crustal reworking due to the Rodinia breakup. The Central Tianshan Arc Terrane, which experienced the same tectonic events as the Tarim Craton during the Precambrian, is considered to be a micro-Precambrian block that separated from the Tarim Craton during the Rodinia breakup.
Keywords: Central Tianshan; Wuwamen Complex; Supercontinent; Tarim Craton; Tectonic evolution

Geochronological evidence for Archaean and Palaeoproterozoic polymetamorphism in the Central Zone of the Limpopo Belt, South Africa - Kröner, Alfred; Brandl, Guenther; Brandt, Sönke; Klemd, Reiner; Xie, Hangqiang (Precambrian Research, 2018)
The Central Zone of Limpopo Belt is a polymetamorphic and complexly deformed Precambrian terrane whose tectonic evolution is still uncertain because details on the timing of its evolution are not well established. We report zircon ages for newly discovered rocks in the Central Zone which document three distinct high-grade tectono-metamorphic events at 3.22, 2.62 and 2.02 Ga. The youngest of these has been well established, but the older two events were so far largely based only on rare zircon overgrowth rims. Most of our samples were collected from a large enclave in the 2.61 Ga Bulai pluton and constitute a strongly deformed, brecciated high-grade assemblage of supracrustal rocks, meta-anorthosite and granitoid gneisses, some of which are most likely equivalents of the pre-3.33 Ga Beit Bridge Complex. Magmatic zircon ages of 3.34–3.33 Ga for anorthositic and tonalitic gneisses in the enclave breccia support this correlation. Ca. 3.22 Ga metamorphic zircons, possibly reflecting the D1/M1 event, were only found in one felsic granulite sample, and their regional significance remains uncertain. Abundant metamorphic zircons grew at ca. 2.62 Ga under granulite-facies conditions (D2/M2), and some of these experienced variable degrees of recrystallization and/or Pb-loss during the third granulite-facies event at ca. 2.0 Ga (D3/M3). Rocks outside the Bulai enclave contain abundant newly-formed ca. 2.02 Ga metamorphic zircons but only rarely preserve evidence for the ca. 2.62 Ga event since these late Archaean zircons show strong recrystallization and/or Pb-loss at ca. 2.0 Ga. We suggest that the Bulai pluton “protected” the rocks inside the enclave from severe overprinting at ca. 2.0 Ga because these rocks remained dry, whereas the assemblages outside the Bulai pluton experienced fluid-assisted metamorphic overprinting at ca. 2.0 Ga. Our new data sugggest that the tectonic evolution of the Central Zone was more complex than previously thought. We favour a scenario where collision involving the Limpopo Belt occurred in the Neoarchaean, whereas the high-grade Palaeoproterozoic event was most likely intracontinental and records far-field effects of plate movements elsewhere. The tectonic setting controlling the early Archaean D1/M1 event remains unknown, largely because of insufficient data and extensive overprinting during later time

Geochronology and geochemistry of granitoid rocks from the Zhibo syngenetic volcanogenic iron ore deposit in the Western Tianshan mountains (NW-China): Constraints on the age of mineralization and tectonic setting. - Zhang, Xi; Tian, Jingquan; Gao, Jun; Klemd, Reiner; Dong, Lianhui; Fan, Junjia; Jiang, Tuo; Hu, Chengjian; Qian, Qing (Gondwana Research, 2012)
Several large syngenetic volcanogenic iron ore deposits including the Chagangnuoer Fe-Cu, the Zhibo Fe and the Beizhan Fe deposits occur in the Awulale Fe-Cu Metallogenetic Belt (AMB) which is located in the southeastern corner of the Yili block in the Western Tianshan Mountains (NW-China). In the present study, we report geochronological and geochemical data for granitoid rocks associated with the Zhibo iron ore deposit in order to constrain the age of the stratiform Fe mineralization and tectonic setting of this deposit. Laser ablation-ICPMS (LA-ICPMS) U-Pb zircon ages of 318.9±1.5Ma and 304.1±1.8Ma were obtained for a diorite and a granite pluton, respectively, both of which intruded the volcanic-volcaniclastic rocks of the Early Carboniferous Dahalajunshan Formation. Additional LA-ICPMS U-Pb zircon ages of 320.3±2.5Ma and 294.5±1.6Ma were obtained for two crosscutting granite dikes, respectively. The ca. 319Ma diorite has a high-potassium calc-alkaline, weakly peraluminous composition and is characterized by large ion lithophile element (LILE) and light rare earth element (LREE) enrichment and flat heavy rare earth element (HREE) patterns. It further shows distinct negative anomalies of Nb, Ta and Ti. In contrast, the ca. 304Ma granite classifies as A 2 type granite and is characterized by an enrichment of LILE and LREE, flat HREEs and distinct negative anomalies of Ba, Nb, Ta and Ti. The ca. 320Ma granite dike has a low-potassium and weakly peraluminous composition and is characterized by LILE and LREE enrichment and a distinct depletion of Nb, Ta, Ti and HREE. The ca. 295Ma granite displays a high-potassium calc-alkaline and weakly peraluminous composition and is characterized by a slight enrichment of LILE and LREE, flat HREEs and a distinct depletion of Nb, Ta and Ti. The data presented here in conjunction with previously published data suggest a submarine, syngenetic volcanogenic mineralization age of ca. 320Ma for the Zhibo iron ore deposit. The Zhibo and other submarine volcanogenic iron ore deposits of the AMB are inferred to have formed in a continental arc-setting related to subduction tectonics. Furthermore, post-collisional granitic magmatism from 304 to 295Ma was superimposed on the entire AMB. © 2011 .
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.c3geoc.geochr
Keywords: Granitoid rocks; The Zhibo iron ore deposit; Tianshan; U-Pb zircon ages

Geochronology and petrogenesis of Eocene gabbros and granitic rocks of the eastern Gangdese belt, southern Tibet: Implications for the timing of India-Asia collision - Shui, Xin Fang; Klemd, Reiner; He, Zhen Yu; Mao, Jing Wen; Zhao, Yuan Yi (Gondwana Research, 2021)
The Palaeocene-Eocene (66–41 Ma) hosts the most intense stage of extensive magmatism in the Gangdese belt of southern Tibet. However, the magma sources and tectonic setting of this magmatic belt have been a matter of discussion for decades. In this study, we conducted zircon geochronological and geochemical studies on Eocene gabbroic rocks and granitic rocks from the Jiacha area in the eastern Gangdese belt. Laser ablation-ICP-MS zircon U–Pb dating suggests almost synchronous crystallization ages of 50–47 Ma for both rock types. Geochemically, the gabbroic rocks have low total rare earth elements and high positive zircon εHf(t) values (from +8.4 to +15.0), indicating that the parental magma was derived from an isotopically depleted mantle. The granitic rocks are magnesian calc-alkalic to calcic granites that are characterized by variable zircon εHf(t) values (from +3.0 to +10.8), indicating that the magmas were generated by differentiation of a mantle-derived magma with variable contributions from ancient crustal materials. Furthermore, an enlarged database of 66–41 Ma plutonic rocks and coexisting Linzizong volcanic rocks reveals an evolutionary trend from mafic to silicic rocks. The zircon Hf and Nd isotopic compositions become more evolved with increasing whole-rock SiO2. The whole-rock and isotope geochemistry of the 66–41 Ma plutonic rocks and the Linzizong volcanic rocks indicate an origin and evolution of these rocks in an active continental margin setting. Therefore, we argue that the Gangdese belt was associated with the subduction of the Neo-Tethyan Oceanic plate throughout the Early Eocene, thereby implying that the initial India-Asia collision occurred after 41 Ma.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Gangdese belt; Neo-Tethyan Oceanic subduction; Palaeocene-Eocene; Volcanism–Plutonism link

Geochronology and Zr-in-rutile thermometry of high-pressure/low temperature metamorphic rocks from the Bantimala complex, SW Sulawesi, Indonesia - Boehnke, Mischa; Broecker, Michael; Maulana, Adi; Klemd, Reiner; Berndt, Jasper; Baier, Heidi (Lithos, 2019)
The timeframe of eclogite- and blueschist-facies metamophism in the central Indonesian region is poorly defined. Relative to its geographic extent, the regional coverage of isotopic age data is insufficient for an unambiguous interpretation of the geologic evolution of the Central Indonesian Accretionary Collision Complex. This study reports new geochronological constraints for high-pressure/low-temperature (HP/LT) rocks from the Bantimala Complex, SW Sulawesi, which further substantiate the importance of Cretaceous HP/LT metamorphism for the larger region. Multipoint Rb–Sr mineral isochrons of eclogites and glaucophane-rich rocks display a narrow range of white mica ages (130–120 Ma), interpreted to postdate peak-HP conditions, which is considerably smaller and more precise than the previously published K–Ar age spectrum (137–113 Ma). The close similarity with K–Ar ages suggests that these analyses were only slightly contaminated, if at all, with an extraneous Ar component, which did not significantly compromise the geological relevance of the existing dataset. An important result of this study is the emerging evidence for regional age differences between HP/LT rocks from SW Sulawesi (130–120 Ma) and Java (ca. 118 Ma). The existence of different subduction zones cannot be excluded but P–T and age differences between these occurrences can be reconciled with a model suggesting formation in the same subduction complex. Zircon is very rare in the studied HP/LT rock suite, but two glaucophane-rich rocks were suitable for U–Pb zircon dating and indicate Late Triassic–Early Jurassic protolith ages (ca. 205–185 Ma). The zircon population of a retrogressed eclogite records a more complex history including evidence for igneous crystallization, metamorphic recrystallization or growth, inheritance and variable degrees of Pb-loss. Metamorphic zircon rims mostly yielded U–Pb ages in the 135–110 Ma range that broadly confirm metamorphic ages determined by K–Ar and Rb–Sr white mica geochronology. Zircons that are significantly older (2.55–1.4 Ga and 400–260 Ma) than the protolith age are interpreted to represent detrital grains from subducted sediments that had been incorporated in mafic melts directly derived from a contaminated mantle source. The presence of continentally-derived detrital zircons that have presumably been included during melt formation in the mantle have not yet been described for any eclogite- and/or blueschist-facies rock of basaltic or gabbroic parentage.<br
CRIS-Team WoS Importer:2019-02-21
Keywords: Bantimala complex; Indonesia; Eclogite; Blueschist; Geochronology

Geodynamic evolution of the south Tianshan orogen: Geochronological and geochemical constraints from granitic and mafic dikes - Jiang, Tuo; Gao, Jun; Klemd, Reiner; Wang, Xinshui; Li, Jilei; Tong, Xirun (Lithos, 2025)
Giant mafic and granitic dike swarms can provide invaluable insight into the paleo-geographic reconstruction of supercontinents and the identification of mantle plumes. Although some case studies of orogeny-related dikes have been undertaken, rare systematic information is available concerning the relationship between the formation mechanism of the dikes and orogenesis. In this study, we conducted a detailed geological, geochronological and geochemical study on recently identified granitic and mafic dikes close to the Wuwamen ophiolite complex in the Chinese South Tianshan, aiming to reveal the link between the formation of the dikes and the orogenic evolution. A dike swarm comprising 456 Ma biotite granite dikes, 423 Ma alkali feldspar granite dikes and a 301 Ma diabase dike crosscuts the Xieliwancaikai gneissic diorite with a zircon U[sbnd]Pb age of 475 Ma. In addition, a 301 Ma granite porphyry dike extends across the middle Devonian meta-sedimentary strata in the Tianqiao area. The geochemical characteristics of the biotite granite and the alkali feldspar granite dikes and their gneissic diorite host suggest that the granitic magma was produced by lower crustal melting. However, the granite porphyry dike has chemical characteristics resembling those of S-type granites commonly produced by partial melting of overthickened crust in collisional orogenic belts. Furthermore, the mafic magma source of the diabase dike resulted from low-degree partial melting of a fertilized sub-continental lithospheric mantle. In conjunction with previously published data on the Wuwamen ophiolite Complex, we propose that the 456 Ma metaluminous granite dike reflects the subduction onset of the South Tianshan Ocean, while the 423 Ma metaluminous granite dike represents the felsic arc melts generated during the subsequent subduction. The 321–313 Ma peraluminous mica granite dikes are thought to have formed during the collision between the Tarim and Kazakhstan–Yili–Central Tianshan blocks. In addition, the peraluminous granite, the strongly peraluminous granite porphyry and the diabase dikes that formed between 307 and 301 Ma were generated in a post-collisional extensional environment. Therefore, bimodal dike swarms provide crucial constraints on the geodynamic evolution of orogens.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Diabase; Dike; Granite; Orogenic tectonics; South Tianshan

High-pressure mafic oceanic rocks from the Makbal Complex, Tianshan Mountains (Kazakhstan & Kyrgyzstan): Implications for the metamorphic evolution of a fossil subduction zone. - Meyer, Melanie; Klemd, Reiner; Konopelko, Dmitry (Lithos, 2013)
The Makbal Complex in the western Tianshan Mountains of Kazakhstan and Kyrgyzstan consists of HP/UHP metasedimentary host rocks which enclose various HP mafic blocks or boudins. These mafic rocks comprise rare eclogites (sensu stricto and sensu lato), garnet amphibolites (retrograded eclogites) and a newly discovered glaucophanite (glaucophane-garnet-omphacite bearing rock).So far the Makbal Complex has been interpreted to predominantly consist of continental lithologies and the mafic rocks were considered as dismembered dikes intruding continental metasediments. This interpretation is mainly based on the geological relationship and bulk rock chemistry of the different rock types. It was further suggested that the continental lithologies of the Makbal Complex underwent eclogite-facies metamorphism in a former subduction zone.In the present study we combined conventional geothermometry, P-T pseudosection modeling and major and trace element whole rock geochemistry for different mafic samples (glaucophanite and eclogites (sensu lato)) in order to shed light on both the metamorphic evolution and the protoliths of the mafic HP rocks in the Makbal Complex.Prograde to peak-pressure clockwise P-T paths of glaucophanite and eclogites (sensu lato) were modeled using garnet isopleth thermobarometry. The results show that the glaucophanite and eclogite (sensu lato) samples experienced similar prograde P-T paths and slightly different peak metamorphic conditions at . 560. °C at 2.4. GPa for the former and between . 520. °C at 2.2. GPa and . 555. °C at . 2.5. GPa for the latter, corresponding to burial depths between 70 and 85. km.Whole rock major and trace element analyses and petrological evidence imply that the various rock types at the Makbal Complex most likely originated from different precursor rocks. Eclogites (sensu lato) are believed to represent strongly retrogressed former eclogite-facies rocks that had never been eclogites (sensu stricto, i.e. >70 vol.% garnet and omphacite) due to an unfavorable alkali-poor bulk composition (Na2O <1wt.%). The four high-pressure mafic samples investigated in this study originated from oceanic crust (Zr/Hf ratio of 33 to 35) which contradicts all previous studies suggesting a continental protolith for all mafic HP/UHP rocks at Makbal.The present study indicates that the mafic high-pressure rocks represent incoherent segments of exhumed oceanic crust. Juxtaposition of different mafic oceanic (this study) and continental rocks is suggested to be due to buoyancy-driven exhumation of the metasedimentary host rock in the subduction channel where dismembered fragments of the subducted oceanic crust were captured in different depths. © 2013 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.c3geoc.highpr
Keywords: Garnet isopleth thermobarometry; Makbal HP/UHP Complex; P-T pseudosection; Thermobarometry; Tianshan Mountains

Hydrothermal controls on iron and lead mineralization on the farms Leeuwbosch and Cornwall, Thabazimbi District, South Africa - Moeller, V.; Klemd, Reiner; Joachimski, Michael; Barton, J. M. (Ore Geology Reviews, 2014)
The Paleoproterozoic Malmani Subgroup and Penge Formation (Transvaal Supergroup) exposed on the farms Leeuwbosch and Cornwall north of Thabazimbi (Limpopo Province, South Africa) host hydrothermal Pb-Ag-Cu-Zn and high-grade hematite iron ore deposits which include the historic Leeuwbosch lead mine. Based on ore petrography, fluid inclusion and stable isotope analyses and geochemical modeling, the structurally controlled, stratabound Leeuwbosch Pb-Ag-Cu-Zn-Fe deposits formed from high salinity NaCl-CaCl2-rich basinal brines with total salinities from 18 to 24wt.% NaCl equivalent which are similar to those found in the Mississippi Valley Type (MVT) Pb-Zn deposits. The minimum formation temperatures (homogenization temperatures) for the lead deposits range between 120 and 185°C and the estimated formation conditions are 200°C at 1kbar pressure. Stable isotope analyses of gangue siderite and calcite indicate that the deposits formed from base metal-enriched brines derived from recycled seawater with δ13Cvs. PDB from 0.46 to 3.17‰ and δ18Ovs. SMOW from -2.95 to -1.79‰. Hydrothermal transport of lead and silver as PbCl3 - and AgCl2 - respectively took place at mildly acidic pH and elevated fO2 in the SO4 2- predominance field. Extensive host rock interaction neutralized and reduced the ore fluid to precipitate galena hosting Ag with chalcopyrite and sphalerite. Fluid inclusions in gangue quartz and calcite in the extensive structurally controlled and pervasive stratabound hydrothermal iron ore deposits on the farms Leeuwbosch and Cornwall, chiefly consisting of high-grade hematite with rare relict magnetite, show a wide compositional variability due to episodic fluid mixing and successive hydrothermal activity in the presence of several distinct fluid end members. Total salinities of fluid inclusions in quartz from the hematite deposits range from 9.2 to 39.9wt.% NaCl eq. with highly variable proportions of NaCl and CaCl2 and minimum formation temperatures are between 100 and 190°C. The estimated formation conditions for the iron ore deposits are 175°C and 1kbar. Stable isotopes of gangue calcite indicate that diagenetic fluids with δ13Cvs. PDB from -3.33 to -2.09 and δ18Ovs. SMOW from 2.52 to 5.60‰ and a second fluid with δ13Cvs. PDB of -7.45 and δ13Cvs. PDB of 17.45 were controlling the formation of the hematite deposits. In agreement with oxidized conditions during hematite formation and characteristic host rock alteration patterns traced by carbon and oxygen isotopes, the second low salinity fluid was derived from the overlying Waterberg Group sandstones and played an important role in the formation of the iron ore deposits, in addition to high salinity diagenetic brines. Iron was leached from the BIFs of the Penge Formation, transported as FeCl+ under mildly acidic conditions and likely deposited in response to the oxidation of the iron-bearing fluids. The lead and iron ore deposits formed by combinations of structural controls which influenced the regional fluid flow patterns and fluid compositions, and fluid-rock interaction with reactive carbonate lithologies of the Malmani Subgroup which acted as a sink for metals transported in acidic hydrothermal solutions. © 2014 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LG.hydrot
Keywords: Fluid inclusions; Galena; Hematite; Leeuwbosch; Stable isotopes; Thabazimbi

Identifying crystal accumulation and melt extraction during formation of high-silica granite - Lu, Tianyu; He, Zhen-Yu; Klemd, Reiner (Geology, 2022)
High-silica (>70 wt% SiO2) magmas are usually believed to form via shallow crustal-level fractional crystallization of intermediate magmas. However, the broad applicability of this model is controversial, because the required crystal-melt separation processes have rarely been documented globally up to now. The ca. 50 Ma Nyemo composite pluton of the Gangdese batholith belt in southern Tibet, which comprises intrusive rocks with intermediate-to high-silica compositions (65-78 wt%), offers a unique opportunity for substantiating the coexistence of extracted melts and complementary silicic cumulates in one of Earth's most complete transcrustal silicic magmatic systems. The Nyemo pluton intrusive rocks exhibit similar zircon Hf isotopic compositional ranges (mean epsilon(Hf(t)) = +5.7 to +8.3), suggesting a common, non-radiogenic magma source with crustal assimilation in the deep crust. Yet, these rocks have distinct geochemical characteristics. High-silica miarolitic and rapakivi granites are strongly depleted in Ba, Sr, and Eu, and their zircon trace elements show extremely low Eu/Eu* and Dy/Yb. In contrast, monzogranite is relatively enriched in Ba and Sr with minor Eu anomalies, and the zircon trace elements are characterized by relatively high Eu/Eu* and Dy/Yb. Therefore, we propose that the high-silica granites represent highly fractionated melt extracted from a mush reservoir at unusually low storage pressure (similar to 99-119 MPa), and that the monzogranite constitutes the complementary residual silicic cumulates.
CRIS-Team WoS Importer:2022-02-11

Insights into fluid evolution and Re enrichment by mineral micro-analysis and fluid inclusion constraints: Evidence from the Maronia Cu-Mo ± Re ± Au porphyry system in NE Greece - Falkenberg, Jan; Keith, Manuel; Melfos, Vasilios; Hohl, Max; Haase, Karsten; Voudouris, Panagiotis; Höß, Alica; Wenske, Julia; Klemd, Reiner; Beier, Christoph; Kutzschbach, Martin; Strauss, Harald (Mineralium Deposita, 2024)
Porphyry-epithermal veins hosting Re-rich molybdenite and rheniite (ReS2) from the Maronia Cu-Mo ± Re ± Au porphyry in Thrace, NE Greece, provide new insights into the hydrothermal processes causing extreme Re enrichment. Quartz trace element chemistry (Al/Ti, Ge/Ti), Ti-in-quartz thermometry, and cathodoluminescence imaging reveal multiple quartz generations in consecutive hydrothermal quartz-sulfide veins associated with potassic, sericitic, and argillic alteration. Fluid inclusions in different quartz generations indicate that phase separation and fluid cooling are the main ore-forming processes in the porphyry stage ( 500 – 350 °C), whereas mixing of a vapor-rich fluid with metalliferous (e.g., Pb, Zn, Au) meteoric water forms the epithermal veins ( 280 °C). These processes are recorded by trace element ratios in pyrite that are sensitive to changes in fluid temperature (Se/Te), fluid salinity (As/Sb, Co/As), and mixing between fluids of magmatic and meteoric origin (Se/Ge). Highly variable intra-grain δ34S values in pyrite record S isotope fractionation during SO2 disproportionation and phase separation, emphasizing the importance of in situ δ34S analysis to unravel ore-forming processes. High δ34S ( 4.5‰) values of sulfides are indicative of low SO42−/H2S fluid ratios buffered by the local host rocks and mixing of the magma-derived fluid with meteoric water. The formation of Re-rich molybdenite ( 6600 ppm) is favored by cooling and reduction of a magma-derived, high-temperature ( 400 °C), oxidized, and Re-rich fluid triggering efficient Re precipitation in early veins in the potassic alteration zone. The systematic temporal fluid evolution therefore reveals that coeval cooling and reduction of oxidized Re-rich fluids cause extreme Re enrichment at the Maronia porphyry system.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Fluid inclusion microthermometry; In situ S isotopes; LA-ICP-MS; Molybdenite trace elements; Porphyry-epithermal evolution; Pyrite; Quartz; Rheniite; Rhenium

In situ chalcophile and siderophile element behavior in sulfides from moroccan middle atlas spinel peridotite xenoliths during metasomatism and weathering - Westner, Katrin; Beier, Christoph; Klemd, Reiner; Osbahr, Inga; Brooks, Nadine (Minerals, 2019)
In situ chalcophile and siderophile major and trace elements were analyzed in sulfides from eight Moroccan Middle Atlas lherzolite xenoliths using electron microprobe and laser ablation inductively coupled plasma mass spectrometry. The sulfides occur enclosed in primary silicates, interstitial in the peridotite matrix, and associated with glass-bearing melt pockets. Monosulfide solid solutions are enriched in these xenoliths relative to pentlandite and intermediate solid solutions. Regardless of the textural occurrence, sulfide platinum-group element (PGE) patterns are distinguished into residual ([Pd/Ir]N < 1 and [Pt/Pd]N > 1 or [Pt/Pd]N < 1), melt-like ([Pd/Ir]N > 1), and unfractionated patterns. The coexistence of both residual and melt-like PGE signatures on a cm scale in a single sample implies that sulfides may record initial depletion and subsequent re-enrichment more effectively than constituent silicates do. Chalcophile and siderophile trace elements other than the PGEs are fractionated between the precipitated sulfide phases, but do not vary systematically with the PGE signatures, suggesting that the PGEs are comparatively sensitive to melting and depletion. In addition, Fe-rich hydroxides generated by sulfide breakdown due to atmospheric weathering display PGE systematics almost identical to their precursor sulfides, implying that they may be reliable tracers of mantle processes even after extensive weathering.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Metasomatism; Middle atlas; Platinum-group elements; Subcontinental lithospheric mantle; Sulfides; Xenoliths

In-situ trace element and Fe-isotope studies on magnetite of the volcanic-hosted iron ore deposits in the Western Tianshan, NW China - Günther, Thomas; Klemd, Reiner; Horn, Ingo; Zhang, Xi (DMG-Jahrestagung2016, 2016)

In-situ trace element and Fe-isotope studies on magnetite of the volcanic-hosted Zhibo and Chagangnuoer iron ore deposits in the Western Tianshan, NW China - Günther, Thomas; Klemd, Reiner; Zhang, Xi; Horn, Ingo; Weyer, Stefan (Chemical Geology, 2017)
Keywords: Fe-isotopes; IOCG-Kiruna type; Magnetite trace elements; Skarn; Tianshan; Zhibo & Chagangnuoer iron ore deposit

In-situ trace element and S isotope systematics in pyrite from three porphyry-epithermal prospects, Limnos Island, Greece - Börner, Frederik; Keith, Manuel; Bücker, Jonas; Voudouris, Panagiotis; Klemd, Reiner; Haase, Karsten; Kutzschbach, Martin; Schiperski, Ferry (Frontiers in Earth Science, 2022)
Porphyry-epithermal systems associated with high-K calc-alkaline to alkaline igneous host rocks may be prospective for the recovery of Te among related elements like Cu, Ag, and Au. Limnos Island, as part of the Tethyan magmatic belt, is such an example, where (telescoped) porphyry-epithermal mineralization is accompanied by different alteration-styles reflecting various hydrothermal processes. Here, we present in-situ S isotope and trace element data of pyrite, which records the fluid evolution from the early porphyry to the late epithermal stage in three distinct prospects (Fakos, Kaspakas, Sardes) on Limnos Island. Pyrite in the sericitic alteration of Fakos mainly formed from single-phase magma-derived fluids lacking evidence for phase separation, as reflected by relatively constant δ34S (about −4‰) and Co/Ni (0.1-1) values. By contrast, in the sericitic alteration of Kaspakas and the following epithermal stages, an influence of boiling is implied by negative δ34S values to −15‰, significant intergrain δ34S variations (>3‰), highly variable Co/Ni (100-0.01) and As/Co (10-0.001) in pyrite. Higher δ34S values (above −4‰) in porphyry pyrite from Sardes and partly in the other two hydrothermal systems are related to mixing between magmatic S, and S which was transported through deeply circulated seawater and/or meteoric water. We propose that fluid-rock interaction buffered the pH to higher values, which enhanced the solubility of Au and Te. Subsequent boiling processes caused the Au deposition, whereas Te partitioned into the vapor and finally precipitated upon condensation into meteoric water. This process is accompanied by continuous cooling during fluid ascent from 780°C to <300°C, as indicated by increasing Sb, Tl, and Pb in pyrite from the porphyry to the epithermal stage. Consequently, the in situ δ34S and trace element analysis allows to constrain the depositional environment of economic metals like Au and Te in porphyry-epithermal prospects.
CRIS-Team Scopus Importer:2022-11-04
Keywords: in-situ d34S analysis; LA-ICP-MS; Limnos Island; pyrite; telescoped porphyry-epithermal; tellurium–Te

Iron isotope compositions of subduction-derived rocks: Insights from eclogites and metasediments of the Münchberg Massif (Germany) - Pohlner, Johannes E.; El Korh, Afifé; Chiaradia, Massimo; Klemd, Reiner; Grobéty, Bernard; Pettke, Thomas (Chemical Geology, 2022)
The Fe isotope systematics of subducted lithologies are crucial for the understanding of redox-dependent mass transfer in subducting slabs, with consequences for the compositions of arc magmas and of the deep mantle. We investigated eclogites, metagabbros, and paragneisses from the Variscan Münchberg Massif to unravel whether their Fe isotope compositions are dominated by the igneous/sedimentary protolith signature, by low-temperature seawater alteration, or by later fluid-rock interactions during the subduction-exhumation cycle. Although the eclogites are thought to be derived from a continental rather than oceanic setting (possibly a rift-drift transition stage), they have mid-ocean ridge basalt (MORB)-like major and trace element compositions. They are often moderately oxidized compared to MORB (Fe3+/ΣFe = 0.06 to 0.30). Their δ56Fe values (+0.00 to +0.17‰; mean + 0.08 ± 0.01‰) mostly resemble those of MORB (+0.07 to +0.17‰). The metagabbros, which are derived from a more enriched mantle source than the eclogites, yielded heavier δ56Fe values (+0.09 to +0.22‰) similar to ocean island basalts, whereas those of the paragneisses (+0.03 to +0.10‰) are typical for pelitic sediments. It appears that the Fe isotope compositions of the igneous protoliths are largely preserved and little if any Fe was mobilized during the diverse fluid-rock interaction stages. The parental magma of the eclogites was probably somewhat isotopically lighter than similarly differentiated MORB magmas, perhaps due to the presence of metasomatized, isotopically light peridotites in the subcontinental lithospheric mantle (SCLM) source. Although it is possible that δ56Fe values were slightly modified during seawater alteration and/or metamorphic fluid-rock interactions in some of the eclogites, the impact of fluid-rock interactions on the major element compositions of the eclogites appears to be small. Furthermore, the scarcity of metamorphic veins in the Münchberg Massif argues against significant Fe mobilization in the slab. We suggest that continental eclogites tend to retain their magmatic δ56Fe values throughout the subduction-exhumation cycle, whereas δ56Fe values of oceanic eclogites may often be dominated by seafloor alteration with potential local modifications in the slab close to fluid channels. The remarkable robustness of the Fe isotope compositions of continental eclogites suggests that they may be used to reconstruct protolith mantle source properties despite the complex post-magmatic history.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Eclogites; Fe isotopes; Fluid-rock interactions; Subduction

Isotopic and trace element geochemistry of the Seligdar magnesiocarbonatites (South Yakutia, Russia): Insights regarding the mantle evolution beneath the Aldan-Stanovoy shield - Doroshkevich, Anna G.; Prokopyev, Ilya R.; Izokh, Andrey E.; Klemd, Reiner; Ponomarchuk, Anton V.; Nikolaeva, Irina V.; Vladykin, Nikolay V. (Journal of Asian Earth Sciences, 2018)
The Paleoproterozoic Seligdar magnesiocarbonatite intrusion of the Aldan-Stanovoy shield in Russia underwent extensive postmagmatic hydrothermal alteration and metamorphic events. This study comprises new isotopic (Sr, Nd, C and O) data, whole-rock major and trace element compositions and trace element characteristics of the major minerals to gain a better understanding of the source and the formation process of the carbonatites. The Seligdar carbonatites have high concentrations of P2O5 (up to 18 wt%) and low concentrations of Na, K, Sr and Ba. The chondrite-normalized REE patterns of these carbonatites display significant enrichments of LREE relative to HREE with an average La/Ybcn ratio of 95. Hydrothermal and metamorphic overprints changed the trace element characteristics of the carbonatites and their minerals. These alteration processes were responsible for Sr loss and the shifting of the Sr isotopic compositions towards more radiogenic values. The altered carbonatites are further characterized by distinct 18O- and 13C-enrichments compared to the primary igneous carbonatites. The alteration most likely resulted from both the percolation of crustal-derived hydrothermal fluids and subsequent metamorphic processes accompanied by interaction with limestone-derived CO2. The narrow range of negative εNd(T) values indicates that the Seligdar carbonatites are dominated by a homogenous enriched mantle source component that was separated from the depleted mantle during the Archean.<br
Keywords: Magnesiocarbonatites; Trace element composition and isotopic data; Hydrothermal processes; Enriched source; Aldan-Stanovoy shield

Large-scale porphyry-type mineralization in the Central Asian metallogenic domain: A review - Gao, Jun; Klemd, Reiner; Zhu, Mingtian; Wang, Xin-Shui; Li, Jilei; Wan, Bo; Xiao, Wenjiao; Zeng, Qingdong; Shen, Ping; Sun, Jinggui; Qin, Kezhang; Campos, Eduardo (Journal of Asian Earth Sciences, 2017)
A series of porphyry-type Cu-(Mo)-(Au) deposits including some giant world-class deposits such as Kounrad, Aktogai, Kal’makyr, Oyu Tolgoi and Chalukou occur in the Central Asian metallogenic domain (CAMD). The outline of the CAMD almost overlaps with that of the Central Asian orogenic belt (CAOB), which is located between the East Europe, Siberia, Tarim and North China cratons. The CAMD comprises sparsely exposed tectonic slices of Precambrian high-grade metamorphic basement rocks that are sandwiched between Phanerozoic accretionary complexes and arc rocks. According to geological, metallogenic, geochronological and tectonic setting characteristics, the CAMD comprises three metallogenic provinces: (1) the Kazakhstan Cu-Au-Mo, (2) the Mongolia Cu-Au and (3) the Northeast China Mo-Cu metallogenic provinces. Early Paleozoic (∼490 to 440 Ma) and Late Paleozoic (∼330 to 295 Ma) large scale porphyry-type mineralization in the Kazakhstan metallogenic province is intimately associated with the evolution of the Central Tianshan–Yili–Northern Tianshan–Kokchetav–Chingiz Paleozoic arc system which was terminated by the late Permian closure of the western segment of the Paleo-Asian Ocean. In contrast, the ∼370 Ma and ∼240 Ma porphyry-type mineralization of the Mongolia metallogenic province is related to the Tuva–Mongolia arc collage system that was formed during the evolution of the Paleo-Asian Ocean in the Paleozoic and the Mongol–Okhotsk Ocean in the early Mesozoic. Furthermore, the Northeast China metallogenic province was affected by three distinct geodynamic processes that were associated with the Paleo-Asian, Mongol–Okhotsk and Paleo-Pacific Oceans during the Paleozoic (>250 Ma), the early Mesozoic (>200 Ma) and the late Mesozoic (200–90 Ma), respectively. Except for the Early Paleozoic Cu mineralization at Duobaoshan (∼480 Ma) and Bainaimiao (440 Ma), the porphyry-type mineralization of this metallogenic province is predominantly characterized by widespread Mesozoic Mo mineralization. In general, porphyry-type deposits of the CAMD have geological, structural, metallogenic, alteration and fluid characteristics, which are consistent either with those related to the oceanic subductional arc settings of the Circum-Pacific metallogenic domain or with those of the continental collisional environment in the Tethyan metallogenic domain. The involvement of highly oxidized intermediate to felsic magmas is fundamental for the formation of porphyry deposits. Even though the prevalent MASH and slab melting models can be employed to interpret the genesis of some porphyry Cu deposits in the CAMD, a here newly suggested model, which is based on ‘pre-enriched mafic lower crust and the subduction of a relictic mid-oceanic ridge’, is thought to explain the large scale copper mineralization in the Balkhash–West Junggar metallogenic belt of the Kazakhstan metallogenic province. Nevertheless, most of the porphyritic suites associated with the Mo deposits in the Northeast China metallogenic province have relatively depleted mantle-like neodymium and hafnium isotopic compositions, suggesting that the ore-forming granitic magma may have predominantly been derived from juvenile lower crust. Upwelling of asthenosphere may have triggered the melting of the lower crust during post-collisional extension subsequent to the closure of the Paleo-Asian Ocean in the Triassic, the subduction of the Paleo-Pacific ocean in the Jurassic and the thinning of the lithosphere caused by rollback of the Paleo-Pacific plate in the Cretaceous. Ancient crustal components were only locally found to have been involved in the magma source of several medium-large Mo deposits.
Keywords: Porphyry-type deposits; Porphyry-type mineralization; Central Asian metallogenic domain; Central Asian Orogenic Belt

Laser Ablation ICP-MS - Klemd, Reiner; Brätz, Helene (Process Mineralogy – JKMRC Monograph Series in Mining and Mineral Processing: No. 6, 2017)

Late Carboniferous high-pressure metamorphism of the Kassan Metamorphic Complex (Kyrgyz Tianshan) and assembly of the SW Central Asian Orogenic Belt - Mühlberg, Moritz; Hegner, E.; Klemd, Reiner; Pfänder, J. A.; Kaliwoda, Melanie; Biske, Y. S. (Lithos, 2016)
High-pressure (HP) metamorphism of the Kassan Metamorphic Complex (KMC) in the western Kyrgyz Tianshan has been related to either late Ordovician or late Carboniferous-Permian subduction processes. We report Sm-Nd ages for retrogressed eclogite samples and 40Ar/39Ar cooling ages for enclosing garnet-muscovite samples from the KMC as new age constraints on HP metamorphism and rock exhumation. These data will be used for an upgraded paleogeographic model for late Paleozoic crustal consolidation in the southwestern Central Asian Orogenic Belt. The retrogressed eclogite samples have transitional alkaline to tholeiitic affinity and trace-elementpatterns consistent with protoliths derived from garnet-bearing mantle sources at rifting plate margins. Geothermobarometric data for a retrogressed eclogite sample indicate peak-metamorphic conditions of 540 ± 30 °C at 1.6 ± 0.1 GPa. Samples from different lithotectonic units of the KMC provide coherent Sm-Nd garnet-whole rock ages of 317 ± 4 Ma and 316 ± 3 Ma (2σ). The prograde major-element zoning in the mm-sized garnets in combination with the moderate peak-metamorphic temperature, support our interpretation of the Sm-Nd garnet ages as unambiguous evidence for late Carboniferous HP metamorphism. The Sm-Nd garnet growth ages overlap within-error with the 40Ar/39Ar mica cooling ages of 314 ± 2 Ma and 313 ± 2 Ma (2σ) indicating rapid uplift of the subduction complex after peak metamorphism. The ca. 317-313 Ma HP-exhumation event of the KMC is contemporaneous with those of the Atbashi and Akeyazi (ca. 500 km east in NW China) HP complexes and implies similar collision histories at the South Tianshan Suture to the east and west of the Talas-Fergana Fault (TFF). The exhumation of the KMC and Atbashi HP complexes overlaps with the initiation of the TFF (Rolland et al., 2013) suggesting incipient separation of the Chatkal and Atbashi complexes during rock exhumation and early plate collision.<br
Keywords: Tianshan; eclogite; Sm-Nd garnet ages; 40Ar/39Ar mica ages; Talas-Fergana Fault; Central Asian Orogenic Belt

Late cretaceous magmatism in the Northern Lhasa subterrane, central Tibet: geodynamic implications - Sun, Miao; Chen, Wei; Klemd, Reiner; Tang, Ju-Xing; Ma, Xu-Dong; Liu, Qing-Ping (International Geology Review, 2022)
Compositional changes of successively emplaced magmatites can be used to infer changes in their petrogenetic evolution and geodynamic setting. The central-northern Lhasa terrane hosts extensive Late Cretaceous magmatism, however, the mechanism that triggered the magmatism and its relationship to the directly preceding Late Cretaceous tectonic transition in the central Tibetan Plateau is still unresolved. Therefore, we conducted a detailed petrological, geochronological, geochemical, and isotopic study on recently identified Late Cretaceous doleritic and granodioritic rocks in the Xiongmei area, northern Lhasa subterrane. The potassic (K2O/Na2O ratios >1) dolerites (ca. 80 Ma) display a post-collisional basaltic shoshonitic signature with uniform moderately enriched whole-rock Sr-Nd and zircon-Hf isotopic compositions ((Sr-87/Sr-86)(t) = 0.7070 to 0.7095, whole-rock epsilon(Nd)(t) = - 2.4 to - 1.3, and zircon epsilon(Hf)(t) = - 5.9 to +1.9), suggesting that they evolved from a similar parental magma and were likely derived by partial melting of an enriched lithospheric mantle metasomatized by hydrous fluids. The granodiorites are geochemically divided into medium-K and high-K calc-alkaline rocks. The medium-K samples (ca. 80 Ma) are generally characterized by low K2O/Na2O ratios <1, whereas the high-K samples (78-76 Ma) display high K2O/Na2O ratios >1. The medium-K samples have positive zircon epsilon(Hf)(t) values from +4.8 to +6.5 and uniform whole-rock e(Nd)(t) values from - 2.4 to - 1.3, which significantly differ from those of the high-K samples that have negative to positive zircon epsilon(Hf)(t) values from - 1.9 to +2.8 and negative whole-rock e(Nd)(t) values from - 8.4 to - 5.1. The medium-K samples are characterized by high Sr contents and Sr/Y ratios, coupled with low Y and HREE contents, similar to adakitic compositions, and were interpreted to have been derived from deep partial melting of the foundering juvenile garnet-bearing mafic lower crust at relatively low temperatures. Compared to the medium-K samples, the high-K samples have lower Sr/Y and (La/Yb)(N) ratios, coupled with flat HREE patterns and distinct negative Eu, Sr and Ti anomalies and are most likely derived from shallower partial melting of the K-rich juvenile lower crust at relatively high temperatures. Considering the occurrence of variable magmatism in the central-northern Lhasa subterrane during the Late Cretaceous, the change in magma composition and lower crustal melting conditions (cold-deep vs. hot-shallow) suggest that the lithospheric mantle keel was partially detached by small-scale mantle convection in response to the low-angle Neo-Tethys-associated subduction between 85 and 70 Ma.
CRIS-Team WoS Importer:2022-07-29

Late Cretaceous tectonothermal evolution of the southern Lhasa terrane, South Tibet: Consequence of a Mesozoic Andean-type orogeny - Dong, Xin; Zhang, Zeming; Klemd, Reiner; He, Zhenyu; Tian, Zuolin (Tectonophysics, 2018)
The Lhasa terrane of the southern Tibetan Plateau participated in a MesozoicAndean-type orogeny caused by the northward subduction of the Neo-Tethyan oceanic lithosphere. However, metamorphic rocks, which can unravel details of the geodynamic evolution, are rare and only exposed in the south-eastern part of the Lhasa terrane. Therefore, we conducted a detailed petrological, geochemical and U–Pb zircon geochronological study of the late Cretaceousmetamorphic rocks and associated gabbros from the Nyemo inlier of the southern Lhasa terrane. The Nyemo metamorphic rocks including gneisses, schists, marbles and calc-silicate rocks, experienced peak amphibolite-faciescontact metamorphism under P–T conditions of 3.5–4.0 kbar and 642–657 °C with a very high geothermal gradient of 45–50 °C/km, revealing a distinct deflection from the steady-state geotherm during low-pressure metamorphism. Inherited magmatic zircon cores from the metamorphic rocks yielded protolithages of 197–194 Ma, while overgrowth zircon rims yielded metamorphic ages of ca. 86 Ma. Whole-rock chemistry and zircon Hf isotopes suggest that the protoliths of the gneisses and schists are andesites and tuffs of the early JurassicSangri Group, which were derived from a depleted mantle source of a continental arc affinity. The coeval intimately-associated gabbro (ca. 86 Ma) crystallized under P–T conditions of 3.5–5.3 kbar and 914–970 °C, supplying the heat flux high enough to cause the contact metamorphism of the Sangri Group rock types. We propose that the intrusion of the gabbro and a simultaneous pressure increase of up to 4.0 kbar, which is related to crustal thickening due to crustal overthrusting and the intrusion of mafic material, resulted in the late Cretaceous metamorphism of the early Jurassic Sangri Group during an Andean-type orogeny. Furthermore the Nyemo metamorphic rocks, which have previously been considered to represent slivers of the Precambrianmetamorphic basement of the Lhasa terrane, are late Cretaceous metamorphic supracrustal rocks.
Keywords: Late Cretaceous contact metamorphism; Gabbroic intrusion; Intrusion-related perturbed geothermal gradient; Andean-type orogeny; Southern Lhasa terrane

LATE PERMIAN PLUME AND NEOPROTEROZOIC SUBDUCTION-MODIFIED MANTLE INTERACTION: INSIGHTS FROM GEOCHRONOLOGY AND Sr-Nd-O ISOTOPES OF MAFIC DIKES OF THE WESTERN EMEISHAN LARGE IGNEOUS PROVINCE br - Wang, Yanning; Xue, Shengchao; Klemd, Reiner; Yang, Lin; Zhao, Feng; Wang, Qingfei (American Journal of Science, 2022)
Geochronological investigations of mafic dikes along the southwest-ern margin of the Emeishan large igneous province (ELIP) in the South China block display a restricted range of U-Pb zircon, baddeleyite, and apatite isotopic ages rang -ing from 263 to 257 Ma, which overlaps with that of previously studied ELIP basalts and mafic intrusions. The dikes are divided into high-Ti and low-Ti groups, whereby the latter is further divided into two subgroups (low-Ti group-1 and-2). The high-Ti group rocks (Ti/Y > 500) are characterized by ocean island basalt-like trace element patterns with mantle-like zircon 4318O of 5.0 +/- 0.10 parts per thousand and slightly enriched sNd(t) val-ues of -1.0 to +1.0. The low-Ti group-1 rocks (Ti/Y < 500) have trace element pat-terns similar to those of the high-Ti group, yet generally with weak negative Nb-Ta anomalies, lower (Sm/Yb)N ratios, elevated zircon 4318O (6.6 +/- 0.33 parts per thousand), and highly variable sNd(t) values (-3.9 to +3.2). The low-Ti group-2 rocks (Ti/Y < 500) are characterized by pronounced negative Nb-Ta anomalies, more negative sNd(t) (-8.4 to -6.6) values, and higher initial 87Sr/86Sr ratios than those of the other two groups. The compositional variations of the high-Ti group and the low-Ti group-1 rocks, in conjunction with the negative correlation between the sNd(t) values and the (Th/ Nb)N ratios, suggest that the two groups were generated from an isotopically hetero-geneous mantle plume at different depths, and experienced varying degrees of crustal contamination (but < 20 wt.%). The high-Ti group rocks are considered to have originated from a deeper garnet-stable source, and the low-Ti group-1 rocks from a shallower source. Mixing calculations indicate that the highly enriched Sr-Nd isotopes of the low-Ti group-2 rocks cannot be explained by crustal contamination. A subduction-modified mantle source is required to account for the arc-like geochemi-cal characteristics of this group. This is consistent with the spatial overlap of the low-Ti group-2 rocks and previously studied geochemically similar samples with rocks from the Neoproterozoic subduction zone along the western margin of the South China block. Furthermore, a fertilized mantle is also consistent with the variable 4318O values of various mafic-ultramafic rocks of the western and central ELIP due to the involvement of recycled oceanic crustal materials. Our results are in accordance with the model that the western ELIP late Permian magmatism was generated by the interaction of two distinct sources, that is, an isotopically heterogenous mantle plume and a Neoproterozoic subduction-modified, Nd isotope-enriched litho-spheric mantle with distinct heterogenous oxygen isotope characteristics.
CRIS-Team WoS Importer:2022-11-18

Lattice preferred orientation of talc and implications for seismic anisotropy in subduction zones - Lee, Jungjin; Jung, Haemyeong; Klemd, Reiner; Tarling, Matthew S.; Konopelko, Dmitry (Earth and Planetary Science Letters, 2020)
Strong seismic anisotropy is generally observed in subduction zones. Lattice preferred orientation (LPO) of olivine and elastically anisotropic hydrous minerals has been considered to be an important factor causing anomalous seismic anisotropy. For the first time, we report on measured LPOs of polycrystalline talc. The study comprises subduction-related ultrahigh-pressure metamorphic schists from the Makbal Complex in Kyrgyzstan-Kazakhstan and amphibolite-facies metasomatic schists from the Valla Field Block in Unst, Scotland. The here studied talc revealed a strong alignment of (001) planes (sub)parallel to the foliation and a girdle distribution of [100] axes and (010) poles (sub)parallel to the foliation. The LPOs of polycrystalline talc produced a significant P-wave anisotropy (AVp = 72%) and a high maximum S-wave anisotropy (max AVs = 24%). The results imply that the LPO of talc influence both the strong trench-parallel azimuthal anisotropy and positive/negative radial anisotropy of P-waves, and the trench-parallel seismic anisotropy of S-waves in subduction zones.
CRIS-Team Scopus Importer:2020-03-10
Keywords: lattice preferred orientation; seismic anisotropy; subduction zone; talc

LREE rich perovskite in antiskarn reactions - REE transfer from pyroxenites to carbonatites? - Voropaeva, Daria; Arzamastsev, Andrei A.; Botcharnikov, Roman; Buhre, Stephan; Gilbricht, Sabine; Götze, Jens; Klemd, Reiner; Schulz, Bernhard; Tichomirowa, Marion (Lithos, 2024)
We study three ultrabasic-alkaline carbonatite complexes (UACCs: Afrikanda, Vuorijarvi, Kovdor) from the Kola Alkaline Province to focus on the comparison of REE contents from pyroxenites and carbonatites and the fate of perovskite. Pyroxenites and carbonatites have large REE variations and similar contents in all three complexes. Afrikanda and Vuorijarvi pyroxenites and carbonatites have higher REE contents compared to all Kovdor rocks. Despite their comparable LREE contents, pyroxenites and carbonatites have different REE-carrier minerals. In most studied pyroxenites, perovskite is the main REE-bearing mineral and its abundance controls the LREE enrichment of the whole rock. When perovskite is absent or in low abundance, apatite is the main REE carrier. Instead, in carbonatites and phoscorites, apatite and calcite control REE contents. REE‑carbonates - found in several carbonatite samples - do not play a substantial role in the overall REE budget because of their very low abundance and tiny grain sizes. We found large LREE variations at very low local scales (< 1 mm) in several thin sections. These large variations are related to carbonatite infiltration and associated antiskarn reactions. Perovskite near calcite is replaced by titanite that has much lower LREE contents. Most LREE released from the breakdown of perovskite were probably dissolved in the carbonatite melt because apatite and calcite that crystallized from this melt are highly enriched in LREE. Newly formed apatites and calcites show large LREE variations that probably are controlled by local factors (e.g. variations of Si, Ca, Mg activities). Y/Ho ratios are strongly fractionated in most minerals and often show large variations at local scales (mm) in these antiskarn reactions. The potential of REE remobilization from such perovskite replacement reactions is very high as perovskite contributes about 70% to the REE budget for these three UACCs. Therefore, more attention should be given to perovskite replacement reactions and its role for LREE enrichment of carbonatite melts.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Antiskarn reactions; Apatite; Carbonatite; Kola alkaline province; Perovskite; Rare earth elements

Magmatic and hydrothermal evolution of the Skouries Au-Cu porphyry deposit, northern Greece - Höß, Alica; Haase, Karsten; Keith, Manuel; Klemd, Reiner; Melfos, Vasilios; Gerlach, Lisa; Pelloth, Fabian; Falkenberg, Jan; Voudouris, Panagiotis; Strauss, Harald; Baker, Tim; Tarantola, Alexandre (Ore Geology Reviews, 2024)
The Skouries Au-Cu porphyry deposit is located in northern Greece and hosted by quartz monzonites and monzogranites of early Miocene age (∼20 Myr). The host rocks show geochemical similarities to other mafic to felsic intrusions in the district that have a similar strike direction, but which are 6 Myr older and lack evidence of economic mineralization. The Skouries magmas probably formed by fractional crystallization of mafic mantle-derived melts, from which the ore-forming fluids were released during second boiling accompanied by massive feldspar crystallization at ∼65 wt% SiO2. Drill core samples record the dominant potassic alteration with A- and B-type veins, which are locally overprinted by chlorite-sericite alteration and related C-type veins, transitioning into sericitic alteration assemblages and D-type veins. The ore mineralization is characterized by chalcopyrite, bornite, pyrite, magnetite and accessory minerals, such as tellurides and PGE minerals. Incompatible trace element ratios of the host rocks, that are commonly used as tracers of magma fertility (e.g., Sr/Y, La/Sm), vary between the alteration-types and may therefore not generally provide a record of magmatic processes. Fluid inclusion and Ti-in-quartz thermometry yielded a temperature range of 520 to >600 °C for the A-type veins and 420 to 500 °C for the B-type veins. Decreasing fluid inclusion entrapment pressures suggest relatively rapid uplift of the hydrothermal system during the early- to main porphyry stage. Fluid inclusion compositions indicate that early K- and Cl-rich fluids caused the potassic alteration resulting in a strong mobilization of REEs, following a decrease in fluid salinity and temperature with proceeding porphyry evolution. Systematic variations in trace element contents (e.g., As, Ag, Pb) and ratios (e.g., As/Sb, Zn/Pb) of pyrite record fluid temperature changes and suggest early phase separation as a major ore-forming process. The common occurrence of native Au as inclusions in pyrite and chalcopyrite are indicative of early Au oversaturation in the fluid, which we relate to sulfide precipitation and phase separation, destabilizing the AuHS0 or Au(HS)2- complex, leading to the accumulation of Au particles. The formation of such Au colloids in fluids may thus reflect an important step towards the hydrothermal enrichment of Au in porphyry environments.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Au nanoparticles; Fluid inclusion microthermometry; LA-ICP-MS; Porphyry deposit; Pyrite chemistry; Trace element systematics

Magmatic evolution of the Schiel Alkaline Complex, Bushveld large igneous province, South Africa - Höß, Alica; Klemd, Reiner; Bolhar, Robert; Haase, Karsten; Ramos, Joshua; Geiger, Elena; Brandt, Sönke; Graupner, Torsten (Lithos, 2024)
The Paleoproterozoic Schiel Alkaline Complex (SAC) in the Limpopo Belt is a composite pluton that coevally formed with the layered intrusion of the Bushveld large igneous province. The SAC is mainly composed of alkaline felsic rocks, pyroxenite, gabbro, syenodiorite/−gabbro, and minor carbonatite and gabbroic dikes. Here we present a new geochemical, geochronological, and isotopic study of the felsic and (ultra)mafic rock suites of the western SAC. The whole rock Sm[sbnd]Nd isotope study of the felsic rocks revealed εNd2059 Ma values between −6.5 and − 3.8, while those of the syenodiorite/−gabbros and gabbros vary from −7.9 to −8.8, and − 4.3 to +1.1, respectively. The pyroxenites have εNd2059 Ma values of +7.4 to +2.7. The Lu[sbnd]Hf isotope study displays εHf2059 Ma values of −15.9 to −9.0 for the syenites, alkali granites and syenodiorite/−gabbros, and significantly higher εHf2059 Ma of −3.1 to +3.4 for the gabbros. LA-SF-ICPMS U[sbnd]Pb zircon dating yields 2079 ± 10 Ma and 2088 ± 30 Ma for the syenodiorite/−gabbros, and 2086 ± 51 Ma and 2107 ± 30 Ma for the gabbros. In conjunction with published data from the eastern SAC, we propose a close petrogenetic link between the mafic and felsic rocks of the SAC. The positive εNd and εHf values of the pyroxenite and gabbro favor a depleted mantle source, while variable εNd and εHf values, and trace element ratios of the gabbros are ascribed to crustal contamination during magma ascent. The felsic rocks, however, mainly formed by fractional crystallization from the gabbros as revealed by major and trace element correlation trends, isotopic data and thermodynamic modelling.
CRIS-Team Scopus Importer:2024-01-05
Keywords: Alkaline complex; Bushveld LIP; Crustal assimilation; Fractional crystallization; Nd-Hf isotope compositions; Rare earth elements

Magmatic PGE sulphide mineralization in clinopyroxenite from the platreef, bushveld complex, South Africa - Klemd, Reiner; Beinlich, Andreas; Kern, Matti; Junge, Malte; Martin, Laure; Regelous, Marcel; Schouwstra, Robert (Minerals, 2020)
The Platreef, at the base of the northern limb of the Bushveld Complex in South Africa, hosts platinum-group element (PGE) mineralization in association with base-metal sulphides (BMS) and platinum-group minerals (PGM). However, whilst a magmatic origin of the stratiform mineralization of the upper Platreef has been widely confirmed, the processes responsible for the PGE and BMS mineralization and metasomatism of the host rocks in the Platreef are still under discussion. In order to contribute to the present discussion, we present an integrated petrographical, mineral-chemical, whole-rock trace-and major-element, sulphur-and neodymium-isotope, study of Platreef footwall clinopyroxenite drill core samples from Overysel, which is located in the northern sector of the northern Bushveld limb. A metasomatic transformation of magmatic pyroxenite units to non-magmatic clinopyroxenite is in accordance with the petrography and whole-rock chemical analysis. The whole-rock data display lower SiO2, FeO, Na2O and Cr (<1700 ppm), and higher CaO, concentrations in the here-studied footwall Platreef clinopyroxenite samples than primary magmatic Platreef pyroxenite and norite. The presence of capped globular sulphides in some samples, which display differentiation into pyrrhotite and pentlandite in the lower, and chalcopyrite in the upper part, is attributed to the fractional crystallization of a sulphide liquid, and a downward transport of the blebs. In situ sulphur (V-CDT) isotope BMS data show isotopic signatures (δ34S = 0.9 to 3.1 ‰; ∆33S = 0.09 to 0.32‰) close to or within the pristine magmatic range. Elevated (non-zero) ∆33S values are common for Bushveld magmas, indicating contamination by older, presumably crustal sulphur in an early stage chamber, whereas magmatic δ34S values suggest the absence of local crustal contamination during emplacement. This is in accordance with the εNd (2.06 Ga) (chondritic uniform reservoir (CHUR)) values, of −6.16 to −6.94, which are similar to those of the magmatic pyroxenite and norite of the Main Zone and the Platreef in the northern sector of the northern Bushveld limb. Base-metal sulphide textures and S–Se-ratios give evidence for a secondary S-loss during late-to post-magmatic hydrothermal alteration. The textural evidence, as well as the bulk S/Se ratios and sulphide S isotopes studies, suggest that the mineralization in both the less and the pervasively hydrothermally altered clinopyroxenite samples of Overysel are of magmatic origin. This is further supported by the PPGE (Rh, Pt, Pd) concentrations in the BMS and mass-balance calculations, in both of which large proportions of the whole-rock Pd and Rh are hosted by pentlandite, whereas Pt and the IPGE (Os, Ir, Ru) were interpreted to mainly occur in discrete PGM. However, the presence of pentlandite with variable PGE concentrations on the thin section scale may be related to variations in the S content, already at S-saturation during magmatic formation, and/or post-solidification mobilization and redistribution.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Bushveld Complex; Clinopyroxenite; Fluid–rock interaction; Metasomatism; Platreef

Mantle sources and magma evolution of the Rooiberg lavas, Bushveld Large Igneous Province, South Africa - Günther, Thomas; Haase, Karsten; Klemd, Reiner; Teschner, Claudia (Contributions To Mineralogy and Petrology, 2018)
We report a new whole-rock dataset of major and trace element abundances and Sr-87/Sr-86-Nd-143/Nd-144 isotope ratios for basaltic to rhyolitic lavas from the Rooiberg continental large igneous province (LIP). The formation of the Paleoproterozoic Rooiberg Group is contemporaneous with and spatially related to the layered intrusion of the Bushveld Complex, which stratigraphically separates the volcanic succession. Our new data confirm the presence of low- and high-Ti mafic and intermediate lavas (basaltic-andesitic compositions) with > 4 wt% MgO, as well as evolved rocks (andesitic-rhyolitic compositions), characterized by MgO contents of < 4 wt%. The high- and low-Ti basaltic lavas have different incompatible trace element ratios (e.g. (La/Sm)(N), Nb/Y and Ti/Y), indicating a different petrogenesis. MELTS modelling shows that the evolved lavas are formed by fractional crystallization from the mafic low-Ti lavas at low-to-moderate pressures ( 4 kbar). Primitive mantle-normalized trace element patterns of the Rooiberg rocks show an enrichment of large ion lithophile elements (LILE), rare-earth elements (REE) and pronounced negative anomalies of Nb, Ta, P, Ti and a positive Pb anomaly. Unaltered Rooiberg lavas have negative epsilon Nd-i (- 5.2 to - 9.4) and radiogenic epsilon Sr-i (6.6 to 105) ratios (at 2061 Ma). These data overlap with isotope and trace element compositions of purported parental melts to the Bushveld Complex, especially for the lower zone. We suggest that the Rooiberg suite originated from a source similar to the composition of the B1-magma suggested as parental to the Bushveld Lower Zone, or that the lavas represent eruptive successions of fractional crystallization products related to the ultramafic cumulates that were forming at depth. The Rooiberg magmas may have formed by 10-20% crustal assimilation by the fractionation of a very primitive mantle-derived melt within the upper crust of the Kaapvaal Craton. Alternatively, the magmas represent mixtures of melts from a primitive, sub-lithospheric mantle plume and an enriched sub-continental lithospheric mantle (SCLM) component with harzburgitic composition. Regardless of which of the two scenarios is invoked, the lavas of the Rooiberg Group show geochemical similarities to the Jurassic Karoo flood basalts, implying that the Archean lithosphere strongly affected both of these large-scale melting events.
Keywords: Bushveld Complex; Large igneous province (LIP); Sub-continental lithospheric mantle (SCLM); Assimilation fractional crystallization; Kaapvaal craton

Mantle sources and magma evolution of the Rooiberg lavas, Bushveld Large Igneous Province, South Africa - Günther, Thomas; Haase, Karsten; Klemd, Reiner; Teschner, Claudia (Contributions To Mineralogy and Petrology, 2018)
Keywords: Assimilation fractional crystallization; Kaapvaal craton; Bushveld Complex; Sub-continental lithospheric mantle (SCLM); Large igneous province (LIP)

Mesoproterozoic continental arc magmatism and crustal growth in the eastern Central Tianshan Arc Terrane of the southern Central Asian Orogenic Belt: Geochronological and geochemical evidence - He, Zhenyu; Klemd, Reiner; Zhang, Zeming; Zong, Keqing; Sun, Li-Xin; Tian, Zuolin; Huang, Bo-Tao (Lithos, 2015)
Numerous microcontinents are known to occur in the Central Asian Orogenic Belt (CAOB), one of the largest accretionary orogens and the most significant area of Paleozoic crustal growth in the world. The evolution of the Precambrian crust in these microcontinents is central to understanding the accretionary and collisional tectonics of the CAOB. Here, we present systematic zircon U–Pb dating and Hf isotope studies of Mesoproterozoic gneissic granitoids from the eastern Central Tianshan Arc Terrane (CTA) of the southern CAOB. The investigated intermediate to felsic (SiO2 = 60.48–78.92 wt.%) granitoids belong to the calcic- to calc-alkaline series and usually have pronounced negative Nb, Ta and Ti anomalies, relative enrichments of light rare earth elements (LREEs) and large ion lithophile elements (LILEs) while heavy rare earth elements (HREEs) and high field strength elements (HFSEs) are depleted, revealing typical active continental margin magmatic arc geochemical characteristics. These spatially-distant rocks show consistent zircon U–Pb crystallization ages from ca. 1.45 to 1.40 Ga and thus constitute a previously unknown Mesoproterozoic continental magmatic arc covering hundreds of kilometers in the eastern segment of the CTA. Furthermore the high and mainly positive zircon εHf(t) values between − 1.0 and + 8.6 and the zircon Hf model ages of 1.95 to 1.55 Ga, which are slightly older than their crystallization ages, suggest that they were mainly derived from rapid reworking of juvenile material with a limited input of an ancient crustal component. Therefore, the formation of these granitoids defines an extensive Mesoproterozoic intermediate to felsic, subduction-related intrusive magmatic arc activity that was active from at least 1.45 to 1.40 Ga, involving significant juvenile continental growth in the eastern segment of the CTA. Furthermore the zircon U–Pb and Hf isotopic data challenge the common belief that the CTA was part of the Tarim Craton during Paleo- to Mesoproterozoic times. However, the southern Beishan microcontinents and the CTA have similar zircon U–Pb and Hf isotopic signatures, indicating a similar Precambrian tectonothermal evolution for both. This finding provides new and important constraints on the Precambrian crustal evolution of the microcontinents in the southern CAOB.<br
Keywords: Zircon U–Pb geochronology and Hf isotopes; Crustal growth; Mesoproterozoic continental magmatic arc; Chinese Eastern Tianshan; Central Asian Orogenic Belt

Mesoproterozoic juvenile crust in microcontinents of the Central Asian Orogenic Belt: evidence from oxygen and hafnium isotopes in zircon - He, Zhenyu; Klemd, Reiner; Yan, Li-Li; Lu, Tianyu; Zhang, Zeming (Scientific Reports, 2018)
We report in situ O and Hf isotope data of zircon grains from coeval Mesoproterozoic (ca. 1.4 Ga) igneous metamafic (amphibolite) and granitic rocks of the Chinese Central Tianshan microcontinent (CTM) in the southern Central Asian Orogenic Belt (CAOB). Zircon grains from amphibolite have mantle-like δ18OVSMOW values of 4.7–5.6‰ and juvenile Hf isotopic compositions (εHf(t) = 8.4–15.3; TDMC = 1.57–1.22 Ga), whereas those from granitic rocks have δ18OVSMOW values of 5.6–7.0‰ and evolved Hf isotopic compositions (εHf(t) = −1.0–8.2; TDMC = 2.09–1.62 Ga). Zircon O–Hf isotopic compositions of the metamafic and granitic rocks provide evidence for Mesoproterozoic (ca. 1.4 Ga) crustal growth and a substantial Palaeoproterozoic supracrustal component in the CTM. These findings and previous studies, reporting ca. 1.4 Ga magmatic rocks from other microcontinents of the CAOB, suggest that a large belt of Mesoproterozoic (ca. 1.4 Ga) juvenile continental crust formed in a continental terrane, fragments of which now occur over a distance of more than a thousand kilometres in the southern CAOB.<br
Keywords: Geochemistry; Petrology; Precambrian geology

Metallogenesis of the Zhibo and Chagangnuoer volcanic iron oxide deposits in the Awulale Iron Metallogenic Belt, Western Tianshan orogen, China - Zhang, Xi; Klemd, Reiner; Gao, Jun; Dong, Lian-Hui; Wang, Xin-Shui; Haase, Karsten; Jiang, Tuo; Qian, Qing (Journal of Asian Earth Sciences, 2014)
The Zhibo and Chagangnuoer iron ore deposits occur at the same volcanic edifice and are situated along the eastern segment of the Awulale Iron Metallogenic Belt in the Western Tianshan orogen of China. The former deposit is exposed near the caldera and the latter lies on the northwestern flank of the volcanic structure. The ore mineralization, the ore texture, the ore bodies structures, the trachytic to trachy andesitic host rocks and the geological characteristics of the Zhibo and Chagangnuoer deposits indicate a magmatic source for the iron oxide mineralization. This is supported by the observation that the vast majority of the Zhibo and Chagangnuoer magnetites have δ18O values between >+0.9‰ and <+4.00‰ consistent with a precipitation from 'normal' subduction type intermediate to felsic magmas or high-temperature magmatic fluids. However some magnetites with low δ18O values (<+0.9‰) are thought to have formed in equilibrium with a low to moderate temperature hydrothermal fluid as is evidenced by pervasive and vein-type controlled (skarn-type) alteration of the ore and host volcanic rocks. Furthermore, the trace element composition of the equilibrium ortho-magmatic magnetites was reset during this hydrothermal alteration event. Major and trace element characteristics indicate that the volcanic rocks, the granitoids and the iron ore bodies were formed in a continental arc setting during the Early Carboniferous. The ore-hosting volcanic rocks probably originated from melting of a mantle wedge that was metasomatized during subduction. Laser ablation-ICPMS (LA-ICPMS) U-Pb zircon ages of 350 ± 2 Ma and 361 ± 7 Ma were obtained for zircon from the trachy andesitic host rock of the iron ore exposed near the caldera of the volcano and the highly altered fine grained garnet-dominated host rock on the flank of the volcano, respectively. A U-Pb zircon age of 321 ± 2 Ma was gained for the rhyolite overlying the ore bodies at the Chagangnuoer deposit, which were intruded by a granitic pluton with a U-Pb zircon age of 319 ± 2 Ma. Furthermore, the minerals of the skarn-type alteration zone at the Chagangnuoer deposit yield an Sm-Nd isochron age of 313 ± 7 Ma (Grt-Act-Epi-whole rock). Considering previous geochronological studies, a 350-330 Ma age range as observed in the host rocks of the Zhibo mine is believed to display a period of continuous volcanic activity and associated ortho-magmatic, high-temperature iron oxide mineralization during subduction. The iron oxide mineralization in both deposits is thought to have been derived from the same magma source, as the ore-hosting volcanic rocks are similar to 'Kiruna-type' iron oxide ores. Subsequently, the volcanic host rocks and the iron ore bodies were variably hydrothermally altered during subduction (ca. 319-313 Ma). The alteration zones were probably facilitated by the infiltration of hydrothermal fluids along faults, which were created by the intrusion of a granitic pluton. © 2014 Elsevier Ltd. All rights reserve
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.metall
Keywords: Magmatic iron oxide ore deposits; Magnetite trace elements and O-isotopes; Metallogenesis; Tianshan; U-Pb zircon ages

Metallogenesis of the Zhibo and Chagangnuoer volcanic iron oxide deposits in the Awulale Iron Metallogenic Belt, Western Tianshan orogen, China - Zhang, Xi; Klemd, Reiner; Gao, Jun; Dong, Lian-Hui; Wang, Xin-Shui; Haase, Karsten; Jiang, Tuo; Qian, Qing (Journal of Asian Earth Sciences, 2015)
The Zhibo and Chagangnuoer iron ore deposits occur at the same volcanic edifice and are situated along the eastern segment of the Awulale Iron Metallogenic Belt in the Western Tianshan orogen of China. The former deposit is exposed near the caldera and the latter lies on the northwestern flank of the volcanic structure. The ore mineralization, the ore texture, the ore bodies structures, the trachytic to trachy andesitic host rocks and the geological characteristics of the Zhibo and Chagangnuoer deposits indicate a magmatic source for the iron oxide mineralization. This is supported by the observation that the vast majority of the Zhibo and Chagangnuoer magnetites have δ18O values between >+0.9‰ and <+4.00‰ consistent with a precipitation from ‘normal’ subduction type intermediate to felsic magmas or high-temperature magmatic fluids. However some magnetites with low δ18O values (<+0.9‰) are thought to have formed in equilibrium with a low to moderate temperature hydrothermal fluid as is evidenced by pervasive and vein-type controlled (skarn-type) alteration of the ore and host volcanic rocks. Furthermore, the trace element composition of the equilibrium ortho-magmatic magnetites was reset during this hydrothermal alteration event. Major and trace element characteristics indicate that the volcanic rocks, the granitoids and the iron ore bodies were formed in a continental arc setting during the Early Carboniferous. The ore-hosting volcanic rocks probably originated from melting of a mantle wedge that was metasomatized during subduction. Laser ablation-ICPMS (LA-ICPMS) U–Pb zircon ages of 350 ± 2 Ma and 361 ± 7 Ma were obtained for zircon from the trachy andesitic host rock of the iron ore exposed near the caldera of the volcano and the highly altered fine grained garnet-dominated host rock on the flank of the volcano, respectively. A U–Pb zircon age of 321 ± 2 Ma was gained for the rhyolite overlying the ore bodies at the Chagangnuoer deposit, which were intruded by a granitic pluton with a U–Pb zircon age of 319 ± 2 Ma. Furthermore, the minerals of the skarn-type alteration zone at the Chagangnuoer deposit yield an Sm-Nd isochron age of 313 ± 7 Ma (Grt-Act-Epi-whole rock). Considering previous geochronological studies, a 350–330 Ma age range as observed in the host rocks of the Zhibo mine is believed to display a period of continuous volcanic activity and associated ortho-magmatic, high-temperature iron oxide mineralization during subduction. The iron oxide mineralization in both deposits is thought to have been derived from the same magma source, as the ore-hosting volcanic rocks are similar to ‘Kiruna-type’ iron oxide ores. Subsequently, the volcanic host rocks and the iron ore bodies were variably hydrothermally altered during subduction (ca. 319–313 Ma). The alteration zones were probably facilitated by the infiltration of hydrothermal fluids along faults, which were created by the intrusion of a granitic pluton.<br
Keywords: Metallogenesis; Magmatic iron oxide ore deposits; Magnetite trace elements and O-isotopes; U–Pb zircon ages; Tianshan

Metamorphic evolution of (ultra)-high-pressure subduction-related transient crust in the South Tianshan Orogen (Central Asian Orogenic Belt): Geodynamic implications - Klemd, Reiner; Gao, Jun; Li, Jilei; Meyer, Melanie (Gondwana Research, 2015)
The study of subduction-related high-pressure- and ultra-high-pressure metamorphic rocks exposed in orogenic belts is critical for unraveling the tectonothermal evolution of an orogen. The South Tianshan Orogen of the southwestern Central Asian Orogenic Belt, one of the world's largest accretionary orogens, contains several Paleozoic (ultra-)high-pressure ((U)HP) metamorphic terranes. (U)HP eclogites, blueschists and associated (U)HP metasedimentary rocks of continental and oceanic origin were reported from two localities in the Northern Tianshan (NTS) of Kazakhstanand Kyrgyzstan, namely from the Ordovician Aktyuz and Makbal metamorphic terranes. Furthermore Lower Carboniferous (U)HP eclogites and blueschists of oceanic origin are located in the Southern Tianshan Accretionary Complex (STAC) of southern Kyrgyzstan (Atbashi) and northwestern China (Akeyazi). The continentally-derived Aktyuz eclogite is considered to have experienced a continuous clockwise prograde P–T path with peak metamorphic conditions of ca. 1.6–2.1 GPa at 610–670 °C, corresponding to a burial depth of about 70 km. A peak metamorphic Lu–Hf garnet isochron age of 474 ± 2 Ma for the retrogressed eclogite of continental origin is in accordance with a Sm–Nd garnet isochron age of 462 ± 7 Ma interpreted as time of cooling and decompression of the metamorphic rock assemblage below 650 to 600 °C. Quantitative P–T pseudosection modeling for peripheral Makbal HP garnet amphibolites of continental origin also revealed a continuous clockwise P–T path with peak-metamorphic conditions of ca. 1.4 GPa at ca. 620 °C followed by an isothermal uplift to ca. 0.7 GPa. Furthermore, prograde P–T paths of oceanically-derived central Makbal high-pressure metabasic rocks revealed peak metamorphic conditions between 520 °C and 560 °C at 2.2 GPa to 2.5 GPa with subsequent isothermal decompressions. The metamorphic (P–T) evolution of a garnet–chloritoid–talc schist is exhibited by a P–T trajectory starting ca. 480 °C at 2.5 GPa, followed by peak pressures of ca. 2.85 GPa at 525 °C and peak temperatures of ca. 580 °C at 2.4 GPa. A Lu–Hf peak metamorphic age of 470.1 ± 2.5 Ma for a peripheral garnet amphibolite is in accordance with a garnet-growth Sm–Nd age of 475 ± 4 Ma of the UHP garnet–chloritoid–talc schist. Different and variable P–T paths show that former oceanic and continental crust at Makbal was subducted to different maximum depths (HP versus UHP conditions). The (U)HP metamorphism of oceanic and continental mafic rocks from the Aktyuz and Makbal metamorphic terranes is assumed to have occurred in a similar time frame of between 500 and 460 Ma. The proposed geodynamic model for the HP Aktyuz metamorphic terrane incorporates the deep northeast-directed subduction of NTS continental crust under the Ankrakhai block of Paleo-Kazakhstan subsequent to the closure of the Djalair–Naiman Basin. At Makbal the final consumption of the oceanic crust of the Terskey Ocean to the northeast was immediately followed by the deep subduction of a (thinned) passive continental margin of the Central Tianshan Arc Terrane (CTA). Both scenarios are in accordance with continental-type subduction geodynamics producing the subduction-related (U)HP rocks during continental–continental collision processes. The exhumation of detached oceanic material by channel flow may have been initiated by the transient subduction of oceanic and subsequent continental crust. The Lower Carboniferous (U)HP metamorphic terranes (Atbashi and Akeyazi) in the Southern Tianshan Accretionary Complex are mainly composed of metasediments which host some lenses and boudins of oceanically-derived blueschists and eclogites. Most eclogites, blueschists and metasediments have experienced peak high-pressure metamorphism (480–580 °C at 1.4–2.1 GPa), while some slices display UHP-conditions (2.7–3.3 GPa at 570–630 °C). Multi-point Lu–Hf and Sm–Nd isochrons from several eclogite and blueschist samples from the Atbashi and Akeyazi metamorphic terranes revealed consistent ages of ca. 320–315 Ma for the peak of metamorphism, thereby confirming that (U)HP metamorphism occurred during a single subduction event. The highly variable peak metamorphic conditions displayed by the (U)HP rocks imply that metamorphism of the metasediments and the various metabasic rocks occurred in different depths of the subduction zone. (U)HP metabasites and metasediments exhibit different P–T paths, which is consistent with the chaotic incorporation in a subduction channel resulting in the eventual exhumation as a mélange. This scenario is much in agreement with initial subduction of oceanic crust and accretionary wedge sediment removal by subduction erosion and thus is similar to accretionary-type subduction terranes, although, with higher peak P–T conditions than previously recorded. The absence of significant melting, in combination with the variable peak pressure metamorphic conditions and the intimate interlayering of high- and ultrahigh-pressure rocks, suggests that the (U)HP rocks were derived from varying depths within the subduction zone and then juxtaposed during exhumation in the subduction channel. This is in accordance with exhumation of the (U)HP rocks by channel flo
Keywords: South Tianshan Orogen; (Ultra-)high-pressure metamorphism; Geochronology; Accretionary- and continental-type subductions; Channel flow exhumation

Metamorphic evolution of (ultra)-high-pressure subduction-related transient crust in the South Tianshan Orogen (Central Asian Orogenic Belt): Geodynamic implications - Klemd, Reiner; Gao, Jun; Li, Ji-Lei; Meyer, Melanie (Gondwana Research, 2015)
UnivIS-Import:2015-03-09:Pub.2015.nat.dgeo.IGM.c3geoc.metamo

Metamorphic P–T–t evolution of mafic HP granulites in the northeastern segment of the Tarim Craton (Dunhuang block): Evidence for early Paleozoic continental subduction - He, Zhenyu; Zhang, Zeming; Zong, Keqing; Xiang, Hua; Klemd, Reiner (Lithos, 2014)
The Dunhuang block, which constitutes the northeastern segment of the Tarim Craton, is located between the Central Asian Orogenic Belt (CAOB) to the north and the Altyn-Qilian Orogenic Belt to the south. The present study reveals that the early Paleozoic HP mafic granulites from the Dunhuang block underwent four stages of metamorphism: prograde amphibolite-facies (M1), peak high-pressure (HP) granulite-facies (M2) and two late stages of amphibolite-facies retrograde metamorphism. Based on phase equilibrium modeling, P-T conditions of the four stages of metamorphism are estimated at 720-750. °C and 11-13. kbar, 760-800. °C and 14-16. kbar, 690-720. °C and 8-8.5. kbar, and at <. 6. kbar and <. 640. °C respectively. Peak granulite-facies metamorphism is characterized by a low geothermal gradient of ca. 16. °C/km. Zircon U-Pb dating shows that the HP granulite-facies metamorphism occurred at ca. 431. Ma and the early retrograde amphibolite-facies overprint at ca. 403. Ma. Thus the investigated mafic rocks here reveal a clockwise P-T-t path involving burial heating before peak granulite-facies metamorphism and subsequent decompression-cooling with an uplift rate of ca. 0.8. km/Ma. This, together with a continental affinity of the HP metamorphic rocks, indicates that the Dunhuang block experienced a collisional orogenesis during the early Paleozoic. © 2014 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.metamo
Keywords: Beishan orogenic collage; CAOB; Dunhuang block; Early Paleozoic; HP granulite; P-T-t path

Migration of Arc Magmatism Above Mantle Wedge Diapirs With Variable Sediment Contribution in the Aegean - Schaarschmidt, Anna; Haase, Karsten; Voudouris, Panagiotis C.; Melfos, Vasilios; Klemd, Reiner (Geochemistry Geophysics Geosystems, 2021)

Mineralogical constraints on the potassic and sodic-calcic hydrothermal alteration and vein-type mineralization of the maronia porphyry cu-mo ± re ± au deposit in NE greece - Melfos, Vasilios; Voudouris, Panagiotis; Melfou, Margarita; Sánchez, Matías G.; Papadopoulou, Lambrini; Filippidis, Anestis; Spry, Paul G.; Schaarschmidt, Anna; Klemd, Reiner; Haase, Karsten; Tarantola, Alexandre; Mavrogonatos, Constantinos (Minerals, 2020)
The Maronia Cu-Mo ± Re ± Au deposit is spatially related to a microgranite porphyry that intruded an Oligocene monzonite along the Mesozoic Circum-Rhodope belt in Thrace, NE Greece. The magmatic rocks and associated metallic mineralization show plastic and cataclastic features at the south-eastern margin of the deposit that implies emplacement at the ductile-brittle transition, adjacent to a shear zone at the footwall of the Maronia detachment fault. The conversion from ductile to brittle deformation caused a rapid upward magmatic fluid flow and increased the volume of water that interacted with the host rocks through high permeable zones, which produced extensive zones of potassic and sodic-calcic alteration. Potassic alteration is characterized by secondary biotite + K-feldspar (orthoclase) + magnetite + rutile + quartz ± apatite and commonly contains sulfides (pyrite, chalcopyrite, pyrrhotite). Sodic-calcic alteration consists of actinolite + sodic-calcic plagioclase (albite/oligoclase/andesine) + titanite + magnetite + chlorite + quartz ± calcite ± epidote-allanite. The high-oxidation state of the magmas and the hydrothermal fluid circulation were responsible for the metal and sulfur enrichments of the aqueous fluid phase, an increase in O2 gas content, the breakdown of the magmatic silicates and the production of the extensive potassic and sodic-calcic alterations. Brittle deformation also promoted the rapid upward fluid flow and caused interactions with the surrounding host rocks along the high temperature M-, EB-, A-and B-type veins.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Greece; Maronia; Porphyry deposit; Potassic alteration; Sodic-calcic alteration; Vein-types

Multistage fluorite mineralization in the southern Black Forest, Germany: Evidence from rare earth element (REE) geochemistry - Hintzen, Robin; Werner, Wolfgang; Hauck, Michael; Klemd, Reiner; Fischer, Lennart A. (European Journal of Mineralogy, 2023)
The Black Forest hosts a wide range of hydrothermal mineralization, including fluorite-barite vein deposits. In a detailed investigation of the Finstergrund and Tannenboden deposits in the Wieden mining district (southern Black Forest), the diversity, geochemical evolution and relative chronology of multistage fluorite precipitation is tracked on the basis of rare earth element (REE) geochemistry, geologic field relationships and crystal zoning. Geochemical discrimination and mathematical λ coefficients suggest a total of seven fluorite REE groups, at least three distinguishable post-Variscan fluid mobilization events and independent formation histories for the deposits despite their spatial proximity. Fluorite vein mineralization at the Finstergrund deposit evolved over three fluid generations, was derived from gneissic source aquifers and comprises five distinct fluorite REE groups: the first fluid generation is characterized by fluorite precipitation above 200°C ("group III"), below 200°C ("group I") and after fractional crystallization ("group IV"); the second generation comprises remobilized fluorite ("group II"); and the third generation revealed fluorite precipitation by meteoric water mixing ("group V"). Fluorite vein formation at the Tannenboden deposit is associated with two distinct fluorite REE patterns derived from the same fluid generation: fluorite precipitation above 200°C ("group VII") and after cooling below 200°C ("group VI"). Its fluid source aquifer lithology best matches migmatites contrary to previous models that suggest either gneissic or granitic aquifer rocks for fluorite vein precipitation in the Black Forest. The decoupled formation history between the deposits is tectonically controlled as suggested by a new genetic model for the Wieden mining district. The model argues for a change in the local fluid percolation network and the termination of hydrothermal activity at the Tannenboden deposit after the first fluid mobilization event. The geochemical evolution of multistage fluorite mineralization, as exemplified by the Tannenboden and Finstergrund deposits in combination with other fluorite mineralizations in the Black Forest, provides unique insights into the lithospheric origin and precipitation behaviour of fluorite by various fluid-rock interaction processes occurring in large hydrothermal systems. The local diversity of REE patterns emphasizes the need for detailed investigations of individual hydrothermal vein deposits.
CRIS-Team Scopus Importer:2023-07-21

Multi-system geochronology of North Dabie eclogite: Ineffective garnet ‘shielding’ on rutile inclusions under multi-thermal conditions - Zhou, Tian; Li, Qiuli; Klemd, Reiner; Shi, Yonghong; Tang, Xu; Li, Chaofeng; Liu, Yu (Lithos, 2020)
It has been shown that certain host minerals can robustly shield mineral inclusions and prevent loss of petrochronological information during subsequent thermal events. Rutile inclusions in garnet may crystallize under a wide range of metamorphic conditions and thus rutile is expected to be a useful geochronometer for constraining different stages of a metamorphic P-T path. Hence, it is important to ascertain whether rutile inclusions shielded by garnet retain the original crystallization age information despite later retrograde cooling or subsequent new thermal events. In this study, we test the “shielding effect” of garnet on rutile inclusions from the Baizhangya eclogite in the North Dabie Zone (China), which underwent a multi-stage thermal evolution. Secondary ion mass spectrometry (SIMS) U[sbnd]Pb dating of inherited zircon core domains constrains a Neoproterozoic formation age ( 770 Ma) of the eclogite protolith. SIMS U[sbnd]Pb dating of metamorphic zircon and complementary thermal-ionization mass spectrometry (TIMS) Sm[sbnd]Nd isochron dating of garnet revealed Triassic eclogite-facies metamorphic ages (245–210 Ma). An Early Cretaceous SIMS U[sbnd]Pb age of ca. 130 Ma, yielded by matrix rutile grains and rutile inclusions, suggests significant isotopic alteration since crystallization. This indicates that shielding was ineffective, since the U[sbnd]Pb ages derived from the rutile inclusions, although hermetically armored by garnet, were influenced by a subsequent Early Cretaceous tectono-thermal event. Further transmission electron microscope (TEM) analysis revealed the presence of hematite microlites along the garnet-rutile boundaries, which may have acted as a potential reservoir to store the expelled radiogenic Pb from rutile. This study suggests that newly formed minerals located along mineral boundaries seem to be crucial for understanding the shielding effect.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Rutile inclusions; Secondary ion mass spectrometry; Shielding effect; Transmission electron microscope; U-Pb dating

Nb–Ta fractionation by partial melting at the titanite–rutile transition - John, Timm; Klemd, Reiner; Klemme, Stephan; Pfaender, Joerg A.; Hoffmann, J. Elis; Gao, Jun (Contributions To Mineralogy and Petrology, 2011)
During the evolution of the Earth, distinct geochemical reservoirs with different Nb/Ta ratios have developed. Archean granitoids of the tonalite-trondhjemite-granodiorite (TTG) suite, which represent the Earth's early continental crust, show larger Nb/Ta variations than any other Earth reservoir. This implies that significant Nb-Ta fractionation must have occurred during early crust formation, while the underlying mechanism behind is still unclear. Here, we present a new model on how Nb may be fractionated from Ta during partial melting of subducted oceanic crust. Our data show that Nb/Ta ratios in melts derived from rutile- and titanite-bearing eclogite are largely controlled by the modal relative abundances of rutile and titanite in the source. High modal ratios of titanite over rutile generate melts with very high Nb/Ta (>60), whereas low modal titanite/rutile produces melts with much lower Nb/Ta (≤30). Very low Nb/Ta (<16) occur when all Ti-phases are consumed at very high degrees of melting. As the modal ratio of titanite to rutile is a function of pressure, the Nb/Ta of melts is a function of melting depth. Our new model helps to explain the extreme variation of Nb/Ta observed in many TTGs and thus how Nb and Ta were fractionated during the early evolution of the Earth. Furthermore, the model also indicates that simple one-stage melting models for mafic crust are not sufficient to explain the formation of TTGs. © 2010 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.c3geoc.nbtafr
Keywords: Crustal evolution; Eclogite; Nb-Ta; Partial melting; Rutile; Subduction zone; Titanite

New magmatic record of Indian continental subduction at ca. 50 Ma: Evidence from ultrapotassic–potassic lamprophyre dikes in the Gangdese Batholith, Southern Tibet - Deng, Yulin; Lang, Xinghai; Klemd, Reiner; Wang, Xuhui; Tang, Juxing; He, Qing; Zhou, You; Zuo, Yinhui; Tang, Xiaoqian; Zunzhu, Sangmu (Lithos, 2025)
Geophysical and geochemical evidence confirmed the northward-directed Indian continental lithosphere subduction beneath the Gangdese orogen, however, the geodynamic processes responsible for the transition from the Neo-Tethyan subduction to the Indian continental subduction, particularly magma generation mechanisms regarding the 53–42 Ma magmatic flare-up events, remain poorly constrained. Here we have conducted a comprehensive investigation combining geochemical and geochronological studies of newly discovered Early Eocene (ca. 50–47 Ma) ultrapotassic–potassic lamprophyre dikes in the Lhasa terrane, Tibet. The ultrapotassic lamprophyres revealed highly evolved Sr–Nd–Pb isotopes and high concentrations of incompatible elements, and are thought to have originated from the Indian lithospheric mantle. In contrast, the potassic lamprophyres, displaying relatively depleted Sr–Nd–Pb isotopes and lower MgO contents and K2O/Na2O ratios than the ultrapotassic lamprophyres, show high Sr/Y and low Y geochemical signatures, thereby demonstrating that they formed due to contamination of the ultrapotassic lamprophyre magma by adakitic melts. We, therefore, propose that the lamprophyres represent a new magmatic record of the Indian lithosphere, suggesting that the subduction of Indian plate beneath the Lhasa terrane was already operating at ca. 50 Ma. The data gained here in conjunction with published data further suggest that the upwelling asthenosphere associated with the Neo-Tethyan slab breakoff caused the significant melting of both mantle and crust.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Indian continental subduction; Lhasa terrane; Slab breakoff; Ultrapotassic-potassic lamprophyre dikes

Okorusu tailings – Part II: REE mineralisation, and oxygen and carbon isotope variations - Lohmeier, S.; Machleidt, Jakob; Klemd, Reiner; Ellmies, R. (South African Journal of Geology, 2023)
The Okorusu carbonatite complex and the mine’s tailings dump constitute a potential resource of rare earth elements meaning lanthanides and yttrium (REY). Small (≤100 μm), hydrothermal REE fluorcarbonates (bastnäsite, parisite, röntgenite and synchysite) are the principal light REE carriers while the heavy REE and Y are primarily hosted in magmatic apatite, magmatic-hydrothermal carbonates (calcite, dolomite, ankerite) and hydrothermal fluorite. Bastnäsite and röntgenite occur as individual, liberated crystals in the tailings albeit syntaxial intergrowths of acicular parisite-synchysite-röntgenite are more common. There is a clear trend of decreasing REY contents in the magmatic carbonates over the early hydrothermal carbonates to the late hydrothermal carbonates. The lower total REY abundance in the hydrothermal carbonates is interpreted to be mainly a consequence of their limited redistribution during hydrothermal activity following the breakdown of the primary magmatic minerals and precipitation of REE fluorcarbonates. During this process hydrothermal fluids changed the isotopic composition of the Okorusu carbonatites by shifting δ13C-δ18O pairs of magmatic carbonatite (δ13C:-6.5‰ to-5.4‰; δ18O: +6.4‰ to +11.2‰) to higher values of hydrothermally modified carbonatite (δ13C:-4.2 to-2.2; δ18O: +12.0‰ to +17.5‰). The preferential presence of REY in the magmatic carbonates and to a minor degree in the hydrothermal carbonates in the Okorusu carbonatite and tailings is an important exploration tool for primary magmatic REY mineralisations. The recovery of REE fluorcarbonates can be considered in the development of the flowsheet for the planned recycling of the tailings material as a potential REY by-product.
CRIS-Team Scopus Importer:2023-11-03

Origin and geodynamic significance of the early Mesozoic Weiya LP and HT granulites from the Chinese Eastern Tianshan - Mao, Ling-Juan; He, Zhenyu; Zhang, Zeming; Klemd, Reiner; Xiang, Hua; Tian, Zuolin; Zong, Keqing (Lithos, 2015)
The Chinese Tianshan in the southwestern part of the Central Asian Orogenic Belt (CAOB) is characterized by a variety of high-grade metamorphic rocks, which provide critical constraints for understanding the geodynamic evolution of the CAOB. In this paper, we present detailed petrological and zircon U–Pb geochronological studies of the Weiya low-pressure and high-temperature (LP-HT) granulites of the Chinese Eastern Tianshan. These granulites were previously considered to be a product of a regional metamorphic orogenic event. Due to different bulk-rock chemistries the Weiya granulites, which occur as lenses within the contact metamorphic aureole of the Weiya granitic ring complex, have a variety of felsic–pelitic and mafic granulites with different textural equilibrium mineral assemblages including garnet–cordierite–sillimanite-bearing granulites, cordierite–sillimanite-bearing granulites, cordierite–orthopyroxene-bearing granulites, and orthopyroxene–clinopyroxene-bearing granulites. Average P–T thermobarometric calculations and conventional geothermobarometry indicates that the Weiya granulites underwent early prograde metamorphism under conditions of 600–650 °C at 3.2–4.2 kbar and peak metamorphism of 750–840 °C at 2.9–6.3 kbar, indicating a rather high geothermal gradient of ca. 60 °C/km. Zircon U–Pb LA–ICP–MS dating revealed metamorphic ages between 244 ± 1 to 237 ± 3 Ma, which are in accordance with the crystallization age of the Weiya granitic ring complex. We suggest that the formation of the Weiya granulites was related to contemporaneous granitic magmatism instead of a regional metamorphic orogenic event. In addition, a Late Devonian metamorphic age of ca. 380 Ma was recorded in zircon mantle domains from two pelitic samples which is consistent with the metamorphic age of the Xingxingxia metamorphic complex in the Chinese Eastern Tianshan. This suggests that the mantle domains of the zircon grains of the Weiya granulites probably formed during the Late Devonian regional metamorphism and were overprinted by the Early Triassic contact metamorphism. Therefore, Early Triassic geodynamic models for the southwestern part of the CAOB, which are based on a previously suggested regional metamorphic orogenic event of the Weiya granulites, need to be viewed with caution.<br
Keywords: Central Asian Orogenic Belt; Chinese Eastern Tianshan; Weiya granulites; Early Triassic; Contact metamorphism; Geodynamic setting

Origin of discordant ultramafic pegmatites in the Bushveld Complex from externally-derived magmas - Cawthorn, Grant; Latypov, Rais; Klemd, Reiner; Vuthuza, Andisiwe (South African Journal of Geology, 2018)
Coarse-grained, discordant, mainly ultramafic, bodies cut the layered succession of the Bushveld Complex. Previous models have subdivided them into magnesian dunite, considered to have been emplaced upward, and more ironrich wehrlite (± oxides), referred to as iron-rich ultramafic pegmatites (IRUP), emplaced downward. We have studied a number of these IRUP bodies in an open pit on Marikana Mining Operations platinum mines property, near Rustenburg, as well as other samples from different levels in the intrusion. A compilation of our and previously published compositions for olivine and clinopyroxene suggests that there are not two discrete suites and processes, but that all bodies originated from multiple magmas with a similar source, resulting in formation of magnesian olivine followed by progressively more iron-rich olivine and clinopyroxene in a fractionating system. In fact, more evolved compositions of discordant pegmatitic gabbro mineralogy exist that have been largely ignored in the past, but are considered here to be cogenetic with the ultramafic bodies. These rocks are all cumulates, based on their simple mineralogy and extreme deficiency in incompatible trace elements in whole-rock compositions. We question the previous models. The first involved fluid replacement. We question from where the high TiO2 content of these bodies originated and to where the high Al2O3 (from the replaced plagioclase) went, noting that TiO2 and Al2O3 are typically the most refractory of oxides. The second involved highly evolved or immiscible liquids or products of disequilibrium melting, generated within the intrusion, considered to have penetrated downward (kms) displacing a succession of cumulate rocks. We question the mechanism by which a downward penetrating magma could displace pre-existing cumulates, presumably returning them back up the same conduit without any interaction between the two. We suggest that initial upward penetration of magmas, not generated within the layered succession, replaced the existing cumulates initially by infiltration. Subsequently, vertical central channels developed and large volumes of magma flowed through, precipitating cumulus minerals. The removed components and the residual liquids from formation of these discordant cumulate bodies were expelled upward. The composition of the proposed liquid for these bodies is considered to have affinities with sub-alkaline basalt (ankaramite), which occurs in many large igneous provinces, and whose distinctive features are the dominance of olivine and clinopyroxene and absence of plagioclase, and have a high CaO/Al2O3compared to tholeiitic magmas. Support for this conclusion is based in part on the clinopyroxene compositions in IRUP, which are enriched in the wollastonite component and do not plot near to the tholeiite or Bushveld trend in the pyroxenite quadrilateral. They contain no exsolution which is abundant in all layered rocks in the Bushveld Complex. Examples of such sub-alkaline rocks related to the Bushveld Complex have been previously reported. One (Schoongezicht intrusion), distal from, and at a much deeper stratigraphic level (base of the Ventersdorp Supergroup) than, the complex, is dominated by dunite, wehrlite and magnetitite, comparable to the IRU
Keywords: Africa; Bushveld Complex; chain silicates; clinopyroxene; dunite; feldspar group; framework silicates; granites; ICP mass spectra; igneous rocks; magmas; magnetite; mass spectra; mineral composition; nesosilicates; olivine group; oxides pegmatite; plutonic rocks; peridotites; plagioclase; pyroxene group; silicates; South Africa; Southern Africa; trace metals; ultramafics; wehrlite

Origin of Early Eocene diabase dikes in the southern Lhasa terrane: Implications for the Neo-Tethyan slab breakoff - Deng, Yulin; Lang, Xinghai; Klemd, Reiner; Wang, Xuhui; He, Qing; Zhou, You; Yin, Qing; Zhan, Hongyu (Lithos, 2024)
The geodynamic evolution of the Himalayan–Tibetan orogen during the transition from Neo-Tethyan oceanic to Indian continental subduction remains unclear. Therefore, we conducted a new geochronological, geochemical, and Sr–Nd–Pb–Hf isotopic study of post-collisional diabase dikes in the central segment of the southern Lhasa subterrane. The diabase dike samples yield zircon U–Pb ages of 51–49 Myr, consistent with the timing of the Gangdese magmatic flare-up (ca. 53–50 Myr). In addition, the diabase dikes exhibit a geochemical intraplate affinity and depleted Sr–Nd–Pb isotopic compositions. Their variable Nb contents allow, the dikes to be divided into low-Nb (<8 ppm) and high-Nb (>9 ppm) types, which represent the melting products of slab fluid-modified Gangdese lithospheric mantle and a mixed mantle source comprising Gangdese lithospheric and deep asthenospheric mantle, respectively. In addition, the wide variation in εHf(t) values (−10.0 to +12.3) of zircons from these diabase dikes is consistent with the Gangdese zircon Hf isotopic ‘pull-down’ at ca. 50 Ma. Integrating our new data with published results suggests that the zircon Hf isotopic ‘pull-down’ was a direct consequence of the involvement of subducted Indian continental components in the formation of the Gangdese continental lithosphere. The combined data further suggest that upwelling of the asthenosphere, triggered by breakoff of the Neo-Tethyan oceanic slab, resulted in extensive mantle and crustal melting in the Lhasa terrane and the Tethyan Himalaya in southern Tibet.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Diabase dikes; Indian continental subduction; Lhasa Terrane; Slab breakoff

Paleoproterozoic (2.01 Ga) high-pressure granulite facies metamorphism and isothermal decompression of garnet-orthopyroxene-cordierite-orthoamphibole gneisses from the Central Zone of the Limpopo Belt in eastern Botswana - Brandt, Sönke; Klemd, Reiner; Ramos, Joshua; Drueppel, Kirsten; Xie, Hanqiang (Lithos, 2023)
The Central Zone (CZ) of the Limpopo Belt in southern Africa is a complex high-grade metamorphic zone that experienced a, in part, poorly understood poly-metamorphic history. To address this, we present petrological and SHRIMP U-Pb zircon age data for samples of a garnet-and orthopyroxene-bearing cordierite-orthoamphibole (Grt-Opx-Crd-Oam) paragneiss and a charnockite from the Baines Drift and the Phikwe Complexes, respectively. The two complexes are the north-western segments of the CZ in which the metamorphic history is poorly con-strained. High-pressure (HP) granulite facies metamorphism and a clockwise P-T evolution for the feldspar-free Grt-Opx-Crd-Oam gneiss of the Baines Drift Complex are constrained by the application of pseudosection modelling, Grt-Opx thermometry, and quartz in-garnet (QinG) elastic barometry. Our results show that the peak-metamorphic garnet-orthopyroxene-rutile-ilmenite-quartz assemblage formed at HP granulite facies conditions of >900 degrees C and 14 kbar, followed by significant decompression at granulite facies conditions, as recorded by conspicuous orthopyroxene-cordierite coronas around garnet. The widespread formation of orthoamphibole documents subsequent near-isobaric cooling into the amphibolite facies. Based on the formation of metamorphic zircon in the Grt-Opx-Crd-Oam gneiss we precisely determined an age of 2014 +/- 8 Ma for HP granulite facies metamorphism in the Baines Drift Complex. Rare detrital zircons document a possible deposition of the sedi-mentary protolith later than ca. 2.55 Ga, as part of a poorly documented Paleoproterozoic sediment sequence of the Central Zone. The clockwise P-T path and the age of HP granulite facies metamorphism in the Baines Drift Complex as constrained here, are consistent with constraints from 2.02 Ga metamorphism in the Beit Bridge Complex, the major segment of the CZ. The HP metamorphism is interpreted to reflect intracontinental Paleo-proterozoic transpressional orogeny within the consolidated Kaapvaal-Zimbabwe Craton. The association of lower-crustal HP granulite facies rocks of the Baines Drift Complex next to mid-crustal upper-amphibolite facies rocks of the Phikwe Complex may reflect progress of nappe tectonics during the Paleoproterozoic orogeny. SHRIMP U-Pb zircon data indicate that the granite protolith of the charnockite from the Phikwe Complex intruded at 2586 +/- 27 Ma, broadly synchronously with major granitoid emplacement in the Beit Bridge Com-plex. The similar P-T evolution of ca. 2.02 Ga metamorphism and comparable voluminous granite emplacement at ca. 2.6 Ga indicate a common evolution of the Baines Drift, the Phikwe and the Beit Bridge Complexes in the CZ of the Limpopo Belt.
CRIS-Team WoS Importer:2023-03-03

Paleozoic ophiolitic mélanges from the South Tianshan Orogen, NW China: Geological, geochemical and geochronological implications for the geodynamic setting. - Jiang, Tuo; Gao, Jun; Klemd, Reiner; Qian, Qing; Zhang, Xi; Xiong, Xianming; Wang, Xinshui; Tan, Zhou; Chen, Bangxue (Tectonophysics, 2014)
Two ophiolitic mélange belts, the South Central Tianshan Ophiolite Belt (SCTOB) and the South Tianshan Ophiolite Belt (STOB), extend almost parallel to the Chinese South Tianshan Orogen - the southernmost part of the Central Asian Orogenic Belt (CAOB). The SCTOB occurs interlayered in the South Central Tianshan Suture Zone, the STOB as exotic blocks in Palaeozoic sedimentary strata. However, their tectonic settings and ages, which are crucial for understanding the formation of the CAOB, are still controversially discussed. In order to better understand these geological problems, geological, geochemical and geochronological investigations were conducted on the Guluogou (SCTOB) as well as on the Serikeyayilake and Aertengkesi ophiolitic mélanges (STOB). The ophiolitic suites are composed of basalts, gabbros and mantle peridotites. Laser ablation ICP-MS (LA-ICP-MS) U-Pb zircon ages of 334. ±. 5. Ma and 332. ±. 7. Ma were obtained for the Guluogou gabbros, while SHRIMP U-Pb zircon ages of 423. ±. 10. Ma and 423. ±. 4. Ma were determined for the Serikeyayilake and Aertengkesi gabbros. The mineral composition of the mantle peridotites and the geochemical characteristics of the basalts suggest a mid-ocean ridge (MOR) type affinity for the Guluogou ophiolite and a SSZ type affinity for the Serikeyayilake and Aertengkesi ophiolites. The present data, combined with previously published results, indicate that the STOB may have been derived from a forearc rifting setting that existed during the early Silurian to the early Carboniferous (ca. 439-356. Ma), whereas the SCTOB may represent fragments of a normal wide ocean that lasted to the early Carboniferous (ca. 332. Ma). © 2013 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.paleoz
Keywords: Geochemistry; Geochronology; Ophiolitic mélange; Palaeozoic tectonic evolution; South Tianshan Orogen

Paleozoic Subduction-Accretion in the Southern Central Asian Orogenic Belt: Insights From the Wuwamen Accretionary Complex of the Chinese South Tianshan - Wang, Xin Shui; Klemd, Reiner; Li, Ji Lei; Gao, Jun; Jiang, Tuo; Zong, Ke Qing; Xue, Sheng Chao (Tectonics, 2022)
Accretionary complexes are a major component of the Central Asian Orogenic Belt (CAOB) and are important for understanding its architecture and evolution. The Wuwamen accretionary complex in the Chinese South Tianshan contains a tectonic mélange that witnessed the dynamic evolution from early accretion to final collision of the western CAOB with the Tarim Craton. We present geochronological and geochemical studies on the exotic blocks and metasedimentary matrix of the tectonic mélange in order to refine the subduction-accretion processes in the CAOB. Geochemical and age data reveal that the exotic blocks are of diverse origins, including arc-related granite and arc basalt-like garnet amphibolite from the upper plate, and MORB-like amphibolite from the subducting slab. The blocks underwent subduction-related high-temperature metamorphism between ca. 397 and 340 Ma. Detrital zircons in the metasedimentary matrix are dominated by Paleozoic ages corresponding to the continuous arc magmatism in the Yili-Central Tianshan Block. This finding is consistent with the accretion of the Wuwamen complex on the southern margin of the Yili-Central Tianshan Block above the northward subducting South Tianshan Ocean. A ca. 307 Ma post-accretion granite dyke intruded the Wuwamen complex, thereby providing a minimum age limit for its terminal accretion. In conjunction with subduction-related magmatism, metamorphism, and sedimentation, the accretion of the Wuwamen accretionary complex was active during the early Ordovician to the late Carboniferous. Our new results reiterate that long-lasting accretionary processes in the South Tianshan Ocean and the terminal collision due to its closure exert a major control on the architecture of the southwestern CAOB.
CRIS-Team Scopus Importer:2022-03-04
Keywords: accretionary complex; Central Asian Orogenic Belt; metamorphism; subduction; Tianshan; zircon U–Pb

Permian age of orogenic thickening and crustal melting in the Garm Block, South Tien Shan, Tajikistan - Konopelko, Dmitry; Klemd, Reiner; Mamadjanov, Y.; Hegner, E.; Knorsch, Manuel; Fidaev, D.; Kern, Matti; Sergeev, S. (Journal of Asian Earth Sciences, 2015)
In this paper we present new data for the metamorphic Garm Block (150 × 40 km) that was traditionally shown on regional maps as fragment of a Precambrian basement. The Garm Block comprises migmatized gneisses and schists for some of which peak metamorphic conditions (600–660 °C at 7–9 kbar) characteristic for medium P/T series metamorphic belts were determined. U–Pb ages of overgrown rims of zircon grains and newly grown magmatic zircon grains from four migmatitic samples indicate that melting occurred during peak metamorphic conditions between 299 and 290 Ma. Thus the Garm Block is the first Early Permian regional metamorphic terrane established in the southern part of the Central Asian Orogenic Belt. A crosscutting granite intrusion yields a concordia age of 290 Ma identical to the age of metamorphism and similar to ages of post-collisional intrusions elsewhere in the Tien Shan. Detrital zircon grains from the Garm samples yield an age spectrum with major peaks at 700–550 Ma and 1150–700 Ma, and smaller ones at ca. 2.7–2.4 Ga and 3.5–3.3 Ga. The youngest grains define an Ediacarian maximum depositional age of the sedimentary protoliths. The presence of Grenvillian ages of 1150–800 Ma, which are characteristic for the Tarim Craton, and the lack of ca. 1.6–1.2 Ga ages, characteristic for the Northern Tien Shan, suggest an origin of the Precambrian zircon grains from southern continental blocks similar to the Tarim Craton. Six granitoid samples yield negative εNd values of −10.6 to −3.7 consistent with the reworking of crustal material with 1.8–1.1 Ga average crustal residence times and the formation of the South Tien Shan belt on a continental basement with Paleoproterozoic or older crust. The Garm Block formed as a consequence of lithospheric thickening during the Late Carboniferous collision of two continental blocks that created the South Tien Shan fold belt. Lateral crustal melt flow coupled with extension may have resulted in exhumation of the Permian metamorphic rocks.<br
Keywords: Tajikistan; South Tien Shan (Tianshan); Garm Block; Permian metamorphism; Zircon ages; Nd isotopes

Petrogenesis of the early Permian Hongliujing granite complex in the Chinese Eastern Tianshan orogen: Evidence for crustal growth in the Central Tianshan microcontinent - He, Zhen Yu; Klemd, Reiner; Lu, Tian Yu; Yan, Li Li; Xiang, Hua (Geological Society of America Bulletin, 2024)
The generation and modification of silicic magma systems are essential processes in resolving the differentiation of continental crust. This understanding motivated the geochronological and geochemical study of the early Permian Hongliujing granite complex, consisting of quartz monzonite, granite, and leucogranite in the Central Tianshan microcontinent of the southern Central Asian Orogenic Belt. Laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) zircon U-Pb dating of the Hongliujing complex rock units revealed almost identical ages (279 ± 2 Ma to 270 ± 2 Ma). The high-silica leucogranite and granite are characterized by positive Rb and negative Eu anomalies and Ba, Sr, P, and Ti depletions. The zircon trace elements are characterized by relatively low Ti and Th/U and high Yb/Gd. In contrast, the quartz monzonite and its mafic microgranular enclaves display minor negative Ba, Sr, P, Ti, and Eu anomalies, while the zircon trace elements are characterized by relatively high Ti and Th/U and low Yb/Gd. The complex has similar zircon Hf and whole-rock Nd isotopic compositions, with Hf and Nd model ages younger than 1.4 Ga, suggesting that their magmas were derived from an isotopically depleted mantle, with some contributions from crustal melts. The leucogranites further showed relatively large variations of εHf(t) and lower εNd(t) values, implying that their magma was affected by higher amounts of crustal contamination. We suggest that crystal-melt segregation was the major mechanism responsible for the evolution of the magmatic system, and that the early Permian magmatism represents a crust-forming episode triggered by slab rollback of the subducting South Tianshan oceanic plate beneath the eastern Central Tianshan microcontinent. Thus, our study reveals that microcontinents with Precambrian crustal basement were major sites of juvenile continental growth during the accretionary evolution of the Central Asian Orogenic Belt.
CRIS-Team Scopus Importer:2024-08-16

Phase separation and fluid mixing revealed by trace element signatures in pyrite from porphyry systems - Keith, Manuel; Haase, Karsten; Chivas, Allan R.; Klemd, Reiner (Geochimica Et Cosmochimica Acta, 2022)
Porphyry deposits host various trace elements in economic amounts, but the hydrothermal processes causing their fractionation and enrichment are still not fully understood, but vital to target the most prospective mineralisation. We present the first micro-analytical study on the trace element composition of pyrite from the Koloula Cu-Au porphyry in the young and thin (<25 km) Solomon Islands arc. A statistical evaluation of the trace element data of pyrite indicates that mineral inclusions obscure the chemical signature of the mineralisation processes. The filtered pyrite data, from which the inclusions were excluded, correlate with variations in temperature and salinity, as defined by fluid inclusions from several alteration zones. Trace element ratios in pyrite show systematic variations with fluid temperature and salinity (Co/Ni, Se/Te), phase separation (Co/Ni, Co/As) and mixing of magmatic fluids and meteoric waters (Se/Ge). The mineralisation in the potassic alteration zone was controlled by the formation of a hypersaline liquid (Co/As > 1, Co/Ni > 50) from a magma-derived fluid (Se/Ge 100) at lithostatic pressure conditions and temperatures of up to 700 °C (Se/Te > 50). This was followed by a transition to hydrostatic pressure conditions due to open-fracture continuity towards the paleo-surface, marking the onset of boiling in the chlorite-sericite to sericitic alteration zone (Co/As < 1), where minor proportions of meteoric water were involved (Se/Ge < 100). The shallowest part of the mineralisation is controlled by lower temperature (<300 °C, Se/Te < 50) vapour-rich fluids (Co/As < 1) that condensed into meteoric waters in an epithermal transition zone (Co/Ni < 50, Se/Ge < 100). Trace element systematics in pyrite from progressive alteration zones therefore preserve the time-space evolution of porphyry (-epithermal) systems in young and thin oceanic island arcs.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Fluid inclusions; Porphyry alteration; Porphyry systems in oceanic island arcs; Solomon Islands; western Pacific porphyry deposits; Sulfide chemistry; laser ablation ICP-MS

Platinum-group element concentrations in base-metal sulphides from the Platreef, Mogalakwena Platinum Mine, Bushveld Complex, South Africa - Klemd, Reiner; Junge, Malte; Oberthür, Thomas; Herderich, Tobias; Schouwstra, R. P.; Roberts, Jaques (South African Journal of Geology, 2016)
Base-metal sulphides (BMS) are important host minerals for platinum-group elements (PGE) in orthomagmatic Ni-Cu-PGE deposits. The PGE distribution and concentration in the BMS provide important genetic, exploration and mineral processing information. Therefore, detailed mineralogical work and an in situ laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS) analysis of trace elements were conducted on the BMS of mineralised samples from the Overysel and Sandsloot localities of the Mogalakwena Platinum Mine. These localities access the Platreef of the northern Bushveld Complex. Platinum-group element enrichment trends in the BMS are similar in the Overysel and Sandsloot samples, although the overall PGE concentrations in the Overysel BMS are lower than those in the Sandsloot BMS. A general decoupling of the PGE from the BMS due to fluid activity, as advocated by other authors for the Sandsloot reef lithologies, was not observed in the samples studied. A major portion of the PGE mineralisation is associated with BMS as is indicated by the ‘moderate’ (Overysel r = +0.62) to ‘very good’ (Sandsloot r = +0.79) PPGE-S bulk-rock correlation, whereas an excellent PPGE-Ni correlation (especially at Overysel) indicates that pentlandite is a major PGE- carrier. These results are corroborated by the trace element contents of the BMS and by mass balance calculations. For instance, the LA-ICP-MS BMS study revealed average concentrations of 65 to 165 ppm Pd and 0.17 to 13 ppm Rh at Overysel, and 156 to 412 ppm Pd and 18 to 57 ppm Rh at Sandsloot in pentlandite of both the mineralized pyroxenites. In contrast, chalcopyrite and pyrrhotite are almost devoid of PGE. Platinum and the IPGE (Ir, Os, Ru) are very low in the BMS and, therefore, are thought to be hosted in discrete PGM grains. This conclusion is supported by the mass balance calculations for Pt and by the actual presence of PGM grains in both sample suites. The presence of discrete PGM grains explains the calculated gap between the whole-rock PPGE concentrations and the PPGE concentration in the mineral phases as revealed by the mass balance calculations. The PPGE concentrations in the BMS and the complementary mass balance calculations are in general agreement with those of the Merensky Reef and the UG-2, in both of which large proportions of the whole-rock Pd and Rh are hosted by pentlandite, whereas Pt and the IPGE mainly occur in discrete PGM rather than being hosted by BMS. However, comparison of our results with those of the Merensky Reef and the UG-2 indicates that the average maximum Pd and Rh concentrations in pentlandite are distinctly lower in the Platree
Keywords: Africa; base metals; Bushveld Complex; copper ores; geochemical methods; ICP mass spectra; igneous rocks; Malmani Subgroup; mass spectra; metal ores; metals; mineral exploration; nickel ores; platinum group; platinum ores; plutonic rocks; pyroxenite; South Africa; Southern Africa; spectra; sulfides; ultramafics; whole rock; Sandsloot Mine; Mogalakwena Mine; Platreef Mine

Platinum-group element distribution in base-metal sulfides of the Merensky Reef from the eastern and western Bushveld Complex, South Africa. - Osbahr, Inga; Klemd, Reiner; Oberthuer, Thomas; Brätz, Helene; Schouwstra, Robert (Mineralium Deposita, 2013)
Base-metal sulfides in magmatic Ni-Cu-PGE deposits are important carriers of platinum-group elements (PGE). The distribution and concentrations of PGE in pentlandite, pyrrhotite, chalcopyrite, and pyrite were determined in samples from the mineralized portion of four Merensky Reef intersections from the eastern and western Bushveld Complex. Electron microprobe analysis was used for major elements, and in situ laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS) for trace elements (PGE, Ag, and Au). Whole rock trace element analyses were performed on representative samples to obtain mineralogical balances. In Merensky Reef samples from the western Bushveld, both Pt and Pd are mainly concentrated in the upper chromitite stringer and its immediate vicinity. Samples from the eastern Bushveld reveal more complex distribution patterns. In situ LA-ICP-MS analyses of PGE in sulfides reveal that pentlandite carries distinctly elevated PGE contents, whereas pyrrhotite and chalcopyrite only contain very low PGE concentrations. Pentlandite is the principal host of Pd and Rh in the ores. Palladium and Rh concentrations in pentlandite reach up to 700 and 130 ppm, respectively, in the samples from the eastern Bushveld, and up to 1,750 ppm Pd and up to 1,000 ppm Rh in samples from the western Bushveld. Only traces of Pt are present in the base-metal sulfides (BMS). Pyrrhotite contains significant though generally low amounts of Ru, Os, and Ir, but hardly any Pd or Rh. Chalcopyrite contains most of the Ag but carries only extremely low PGE concentrations. Mass balance calculations performed on the Merensky Reef samples reveal that in general, pentlandite in the feldspathic pyroxenite and the pegmatoidal feldspathic pyroxenite hosts up to 100 % of the Pd and Rh and smaller amounts (10-40 %) of the Os, Ir, and Ru. Chalcopyrite and pyrrhotite usually contain less than 10 % of the whole rock PGE. The remaining PGE concentrations, and especially most of the Pt (up to 100 %), are present in the form of discrete platinum-group minerals such as cooperite/braggite, sperrylite, moncheite, and isoferroplatinum. Distribution patterns of whole rock Cu, Ni, and S versus whole rock Pd and Pt show commonly distinct offsets. The general sequence of "offset patterns" of PGE and BMS maxima, in the order from bottom to top, is Pd in pentlandite → Pd in whole rock → (Cu, Ni, and S). The relationship is not that straightforward in general; some of the reef sequences studied only partially show similar trends or are more complex. In general, however, the highest Pd concentrations in pentlandite appear to be related to the earliest, volumetrically rather small sulfide liquids at the base of the Merensky Reef sequence. A possible explanation for the offset patterns may be Rayleigh fractionation. © 2012 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.c3geoc.platin
Keywords: Base-metal sulfides; Bushveld Complex; LA-ICP-MS; Merensky Reef; Platinum-group elements; South Africa; Trace element distribution patterns

Platinum-group element distribution in base-metal sulfides of the UG2 chromitite, Bushveld Complex, South Africaa reconnaissance study - Osbahr, Inga; Oberthuer, Thomas; Klemd, Reiner; Josties, Anja (Mineralium Deposita, 2014)
Two drill cores of the UG2 chromitite from the eastern and western Bushveld Complex were studied by whole-rock analysis, ore microscopy, SEM/Mineral Liberation Analysis (MLA), and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) analysis. The top and base of the UG2 main seam have the highest bulk-rock Pd and Pt concentrations. Sulfides mostly occur as aggregates of pentlandite, chalcopyrite, and rare pyrrhotite and pyrite or as individual grains associated mostly with chromite grains. In situ LA-ICP-MS analyses reveal that pentlandite carries distinctly elevated platinum-group element (PGE) contents. In contrast, pyrrhotite and chalcopyrite contain very low PGE concentrations. Pentlandite shows average maximum values of 350-1,000 ppm Pd, 200 ppm Rh, 130-175 ppm Ru, 20 ppm Os, and 150 ppm Ir, and is the principal host of Pd and Rh in the studied ores of the UG2. Mass balance calculations were conducted for samples representing the UG2 main seam of the drill core DT46, eastern Bushveld. Pentlandite consistently hosts elevated contents of the whole-rock Pd (up to 55 %) and Rh (up to 46 %), and erratic contents of Os (up to 50 %), Ir (2 to 17 %), and Ru (1-39 %). Platinum-group mineral (PGM) investigations support these mass balance results; most of the PGM are Pt-dominant such as braggite/cooperite and Pt-Fe alloys or laurite (carrying elevated concentrations of Os and Ir). Palladium and Rh-bearing PGM are rare. Both PGE concentrations and their distribution in base-metal sulfides (BMS) in the UG2 largely resemble that of the Merensky Reef, as most of the Pd and Rh are incorporated in pentlandite, whereas pyrrhotite, chalcopyrite, and pyrite are almost devoid of PGE. © 2014 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.platin
Keywords: Bushveld Complex; LA-ICP-MS; MLA; Platinum-group elements (PGE); South Africa; UG2

Poly-cyclic Metamorphic Evolution of Eclogite: Evidence for Multistage Burial–Exhumation Cycling in a Subduction Channel - Li, Jilei; Klemd, Reiner; Gao, Jun; John, Timm (Journal of Petrology, 2016)
(Ultra-)high-pressure [(U)HP] eclogites provide direct evidence for metamorphic processes at mantle depths in subduction zones. Textural evidence and pressure–temperature ( P – T ) path reconstruction allow a unique opportunity to constrain the geodynamic processes along the plate interface. To better understand the dynamics of subduction channels, we present a detailed petrographical, petrological and pseudosection modeling study of a metamorphically complex HP eclogite sample from a tectonic block of the Akeyazi (U)HP metamorphic terrane in the Chinese Tianshan. Mineral chemical variations and textural discontinuities show that all the major phases of the rock (garnet, epidote, clinopyroxene and amphibole) display multiple growth zones compatible with a poly-cyclic evolution including two burial–exhumation cycles. The precise P – T path derived from thermodynamic modeling based on effective bulk compositions suggests that the eclogite underwent complex burial–exhumation cycles with two P – Tloops indicated by the occurrence of polyphase garnet and mutually replaced and regrown amphibole. It is suggested that the eclogite sample, which represents a relic of tectonically detached oceanic crust, underwent two burial–exhumation cycles during convective flow in a subduction channel. This natural occurrence is consistent with numerical simulation studies showing that pressure cycling is to be expected for deeply subducted oceanic crust in a subduction channel. The modeled exhumation process for the eclogite sample corresponds to a previously suggested subduction channel exhumation model for the Akeyazi (U)HP rocks.<br
Keywords: subduction channel; Chinese Tianshan; eclogite; poly-cyclic metamorphism; polyphase mineral growth; pseudosection; P–T path

Porphyry and epithermal deposits in Greece: An overview, new discoveries, and mineralogical constraints on their genesis - Voudouris, P.; Mavrogonatos, C.; Spry, P. G.; Baker, T.; Melfos, V.; Klemd, Reiner; Haase, Karsten; Repstock, A.; Djiba, A.; Bismayer, U.; Tarantola, A.; Scheffer, C.; et al. (Ore Geology Reviews, 2019)
Greece hosts a variety of magmatic-hydrothermal ore deposits/prospects with porphyry- and epithermal styles playing a major role in its total gold endowment. These deposit types are mainly clustered in two areas, the Rhodope- and Attico-Cycladic massifs, and formed from about 33 Ma to the Pleistocene, as a result of back-arc extension in the Aegean Sea, metamorphic core complex formation, and contemporaneous post-subduction and arc magmatism. In the Serbo-Macedonian massif, porphyry Cu-Au deposits include Skouries, Fisoka, Tsikara, Vathi and Gerakario. Causative intrusives are Oligocene to Miocene granodiorites to monzonites. Gold and PGE mineralization is associated with potassic alteration of the intrusives. In the eastern Rhodope massif and the NE Aegean islands, porphyry prospects occur at Pagoni Rachi, Konos Hill, Myli, Melitena (west Thrace), Fakos, Sardes, and Kaspakas (Limnos island) and Stypsi (Lesvos island). Mineralization is associated with Oligocene to Miocene subvolcanics of calc-alkaline to shoshonitic affinity. Feature of these prospects, which they share in common with several porphyry Au-only systems, is their shallow depth of emplacement, the presence of potassic/sodic-calcic and/or phyllic alteration, a strong epithermal overprint, their low Cu content, an extreme Re-enrichment, the multistage introduction of Au, the presence of banded quartz veinlets, and the local presence of tourmaline. New discoveries of porphyry-style mineralization at King Arthur, St. Philippos and Aisymi, increases the gold potential in west Thrace. High-intermediate sulfidation epithermal Au-Ag polymetallic deposits/prospects overprint and/or occur laterally from porphyry-style mineralization, where they are spatially associated with lithocaps of advanced argillic alteration. High-intermediate sulfidation Au-Ag epithermal mineralization at Perama Hill, Mavrokoryfi and Pefka in west Thrace, and at Pterounda, Mesotopos and Megala Therma on Lesvos island is controlled by steeply-dipping extensional faults within volcanic rocks, without any obvious genetic relationship to spatially-related porphyry-style mineralization. Polymetallic epithermal deposits and prospects contain critical and energy critical metals (e.g., Te, Se, Bi, Sb, In, Ge and Ga), which may be considered as by-products. In the Attico-Cycladic area, porphyry Mo-W mineralization occurs as sheeted quartz veins and stockworks cutting a potassic- to sericitic-altered Miocene granodiorite stock in the Lavrion district. Bonanza grade Au- and/or Ag-rich veins with epithermal affinities crosscut metamorphic rocks at Lavrion, and on Syros, Tinos, Antiparos and Anafi islands. Milos island is characterized by shallow submarine volcanic-hosted IS-HS epithermal Au-Ag-Te and base metal deposits. Antimony-As-Ag-Au deposits/prospects on Chios, Samos and Kos islands in the eastern Aegean Sea, indicate the potential for Carlin-style mineralization in Greece. Several factors played a role to the metal endowment of the Aegean porphyry-epithermal systems: magma fertility in the source regions, depth of emplacement of causative intrusives, relative contribution of mantle versus crustal material, redox state of subduction-related magmas, and physico-chemical fluid conditions at the site of ore deposition.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Alteration; Epithermal; Greece; Ore mineralogy; Porphyry

Precambrian gold mineralization at Djamgyr in the Kyrgyz Tien Shan: Tectonic and metallogenic implications - Konopelko, Dmitry; Klemd, Reiner; Petrov, S.V.; Apayarov, F.; Nazaraliev, B.; Vokueva, O.; Scherstén, A.; Sergeev, S. (Ore Geology Reviews, 2017)
The Djamgyr gold deposit is located within the Neoproterozoic basement of the Middle Tien Shan terrane immediately west of the Talas-Fergana fault. The deposit comprises a system of auriferous quartz veins cross-cutting the Beshtor plagiogranite. The veins are surrounded by hydrothermal alteration aureoles and are oriented parallel to the Talas-Fergana fault. The Beshtor granite sampled in the vicinity of the deposit yielded a Neoproterozoic (Tonian) U-Pb zircon age of 815 ± 6 Ma, which is the first single grain zircon age of the Middle Tien Shan basement west of the Talas-Fergana fault. Ar-Ar dating of two muscovite fractions from the alteration aureoles of the auriferous quartz veins yielded ages of 804 ± 3 and 805 ± 3 Ma suggesting that the mineralization in the Djamgyr deposit occurred during the Neoproterozoic ca. 10 m.y. after emplacement of the Beshtor granite. The structural pattern of the auriferous quartz veins and the new geochronological data, combined with the results of previous structural studies, may tentatively constrain the age of pre-existing major fault possibly marking an inherited terrane boundary in the northern part of the present-day Talas-Fergana strike-slip fault. The discovery of Precambrian gold mineralization in the Middle Tien Shan suggests re-evaluation of the metallogenic potential of its Precambrian basement that occupies significant areas west and east of the Talas-Fergana fault.
Keywords: Tien Shan (Tian Shan); Talas-Fergana fault; Djamgyr (Jamgyr) Au deposit; Neoproterozoic

Pressure-temperature evolution during two granulite-facies metamorphic events (2.62 and 2.02 Ga) in rocks from the Central Zone of the Limpopo Belt, South Africa - Brandt, Sönke; Klemd, Reiner; Li, Qiuli; Kröner, Alfred; Brandl, Guenther; Fischer, Andreas; Bobek, Patrick; Zhou, Tian (Precambrian Research, 2018)
The Central Zone of the Limpopo Belt in southern Africa is a classical example of a polymetamorphic terrane that experienced three metamorphic events at 3.22 Ga (M1), 2.66–2.61 Ga (M2) and 2.02 (M3). However, the geodynamic significance of these events is controversial as their P-T evolution was poorly constrained. We present new petrological and geochronological data for the M2 and M3 events. The Neoarchean M2 event is well-preserved in samples from a newly discovered enclave of supracrustal and magmatic rocks in the 2.612 Ga Bulai pluton that shielded the enclave against a Paleoproterozoic M3 overprint, which is dominant in rocks exposed outside the pluton. P-T pseudosection modelling for migmatitic Grt-Crd metapelites from the enclave and the rock sequence outside the pluton indicates an opposite metamorphic evolution, a counterclockwise P-T path for M2 but a clockwise path for M3. Spinel-quartz assemblages in the enclave metapelites record early heating to UHT conditions (ca. 930 °C, 5.5 kbar) at intermediate crustal levels. The peak-pressure M2-assemblage garnet-cordierite-sillimanite-K-feldspar-plagioclase-quartz ± rutile formed at ca. 860 °C and 7.5 kbar during a moderate pressure increase. Cordierite coronas around garnet record subsequent decompression. We interpret the counterclockwise P-T evolution during M2 to result from convergence of the Zimbabwe and Kaapvaal Cratons, which has led to subduction of oceanic lithosphere beneath the Zimbabwe Craton. Subsequent slab retreat has caused asthenosphere upwelling, thereby inducing delamination of the lithospheric mantle. Intrusion of hot asthenospheric material beneath the crust induced early UHT metamorphism at mid-crustal levels. The subsequent moderate pressure increase was related to the ensuing collision of the cratons. Post-peak decompression records incorporation of the enclave into the Bulai pluton melt and uplift in the ascending granitoid melt. The peak M3-assemblage garnet-cordierite-sillimanite-K-feldspar-rutile-plagioclase-quartz formed in metapelites occurring outside the pluton during near-UHT conditions (ca. 880 °C, 7.5 kbar). Cordierite coronas around garnet record subsequent decompression. New growth of garnet and sillimanite at the expense of cordierite documents late near-isobaric cooling to <700 °C. The resulting clockwise P-T path for M3 granulite-facies metamorphism is interpreted to record an intracontinental Paleoproterozoic transpressional orogeny within the consolidated Kaapvaal-Zimbabwe Craton, which was induced by far-field tectonic processe
Keywords: Limpopo Belt; Pseudosection; P-T path; Granulite; Neoarchean; Delamination

Pyrite trace element proxies for magmatic volatile influx in submarine subduction-related hydrothermal systems - Falkenberg, Jan; Keith, Manuel; Haase, Karsten; Klemd, Reiner; Kutzschbach, Martin; Grosche, Anna; Scicchitano, Maria Rosa; Strauss, Harald; Kim, Jonguk (Geochimica Et Cosmochimica Acta, 2024)
Seafloor massive sulfides are modern analogues to ancient volcanogenic massive sulfide deposits, which are particularly enriched in volatile and precious metals (e.g., Te, Au, Ag, Cu, Bi, Se) in subduction-related settings. However, the sources of metals are still poorly constrained, and it remains elusive, whether magmatic volatile influx controls their distribution in submarine hydrothermal systems on the plate tectonic-scale. Here, we demonstrate, for the first time, that Te, As, and Sb contents as well as related Te/As and Te/Sb ratios vary systematically with the δ34S composition of pyrite and native S, as reported by high-resolution coupled SIMS δ34S and trace element LA-ICP-MS micro-analysis. The better correlation of element ratios (Te/As, Te/Sb) opposed to trace element contents (e.g., Te) with δ34S in pyrite demonstrates that element ratios provide a more robust record of magmatic volatile influx than their absolute contents. On this basis, we define a quantitative threshold of high Te/As (>0.004) and Te/Sb (>0.6) ratios in pyrite that are indicative of magmatic volatile influx to submarine subduction-related hydrothermal systems. Two-component fluid mixing simulations further revealed that <5 % of magmatic volatile influx drastically changes the Te/As (and Te/Sb) ratio of the modelled fluid, but only slightly changes its δ34S composition. This suggests that Te/As and Te/Sb ratios are more sensitive to a magmatic volatile influx into seawater-dominated hydrothermal systems than δ34S signatures if the magmatic volatile influx was low. Beyond this, our results demonstrate that magma-derived fluid mixing with seawater only has a negligible effect on the magmatic volatile record of Te/As and Te/Sb, while the S isotope system is prone for seawater overprinting leading to commonly ambiguous source signatures. Thus, Te/As and Te/Sb systematics in pyrite provide a robust proxy to evaluate the contribution of magmatic volatiles to submarine hydrothermal systems from the grain- to plate tectonic-scale.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Black smokers; coupled SIMS δ; In-situ sulfide chemistry; Magmatic fluids; Magmatic volatile phase; Pyrite; Submarine hydrothermal systems

Record of assembly and breakup of Rodinia in the Southwestern Altaids: Evidence from Neoproterozoic magmatism in the Chinese Western Tianshan Orogen - Gao, Jun; Wang, Xin-Shui; Klemd, Reiner; Jiang, Tuo; Qian, Qing; Mu, Li-Xiu; Ma, Yu-Zhou (Journal of Asian Earth Sciences, 2015)
Neoproterozoic gneissic granitoid rocks and a bimodal intrusive complex exposed in the Chinese Western Tianshan Orogen were geochemically and geochronologically studied in order to evaluate the assembly and breakup of Rodinia in the Southwestern Altaids. Zircon U–Pb ages of 903.5 ± 2.2 Ma and 933.6 ± 1.2 Ma were obtained for the Huoshaoqiao and the Wulasutanwutuaiken gneissic granitoid plutons, respectively. Both intrusions have a calcic to calci-alkalic composition and display an enrichment of LREE and LILE and a depletion of HREE and HFSE resembling the geochemical characteristics of Andean arc granites. Their in-situ zircon εHf(t) values of −1.7 to +1.9 and −2.2 to +4.5 further suggest a Late Paleoproterozoic crustal source with limited input of juvenile materials. The Wuwamen bimodal intrusive complex consists of meta-gabbro host rocks and crosscutting granitic dykes. Zircon U–Pb ages of 733 ± 5 Ma and 730 ± 5 Ma were determined for the meta-gabbros and the granitic dykes, respectively. The relative depletion of Nb, Ta and Ti, the Nd isotopic value (εNd(t) = −4.3) of the meta-gabbros, and the Hf isotopic values of gabbroic zircon grains (εHf(t) = +0.4 to +2.8) suggest that the protolithic mafic magma originated from a sub-continental fertilized lithospheric mantle source. Furthermore, the Nd isotopic value (εNd(t) = −11.2) of the granitic dykes and the Hf isotopic values of granitic zircon grains (εHf(t) = −14.3 to −5.6) indicate that the acidic magma originated from lower crustal melting. The dataset presented here in conjunction with previously published data suggest that the ∼900 Ma plutons originated from remelting of older crust in an Andean-type active continental arc setting associated with the assembly of Rodinia, whereas the development of the ∼730 Ma bimodal intrusive magmatism is interpreted as a result of the Rodinia breakup. Thus, the Neoproterozoic magmatism is believed to be a direct consequence of the geodynamic process related to the assembly and breakup of Rodinia in the Southwestern Altaids.<br
Keywords: Altaids; Tianshan; Rodinia; Neoproterozoic magmatism

Redox processes in subducting oceanic crust recorded by sulfide-bearing high-pressure rocks and veins (SW Tianshan, China) - Li, Jilei; Gao, Jun; Klemd, Reiner; John, Timm; Wang, Xin-Shui (Contributions To Mineralogy and Petrology, 2016)
The oxidized nature of the sub-arc mantle and hence arc magmas is generally interpreted as a result of the migration of subduction-related oxidizing fluids or melts from the descending slab into the mantle wedge. This is of particular importance seeing that the oxidization state of sub-arc magmas seems to play a key role in the formations of arc-related ore deposits. However, direct constraints on the redox state of subducted oceanic crust are sparse. Here, we provide a detailed petrological investigation on sulfide- and oxide-bearing eclogites, blueschists, micaschists, eclogite-facies and retrograde veins from the Akeyazi high-pressure (HP) terrane (NW China) in order to gain insight into the redox processes recorded in a subducting oceanic slab. Sulfides in these rocks are mainly pyrite and minor pyrrhotite, chalcopyrite, bornite, molybdenite, sphalerite and chalcocite, including exsolution textures of bornite–chalcopyrite intergrowth. Magnetite, ilmenite and pyrite occur as inclusions in garnet, whereas sulfides are dominant in the matrix. Large pyrite grains in the matrix contain inclusions of garnet, omphacite and other HP index minerals. However, magnetite replacing pyrite textures are commonly observed in the retrograded samples. The eclogite-facies and retrograde veins display two fluid events, which are characterized by an early sulfide-bearing and a later magnetite-bearing mineral assemblage, respectively. Textural and petrological evidences show that the sulfides were mainly formed during HP metamorphism. Mineral assemblage transitions reveal that the relative oxygen fugacity of subducted oceanic crust decreases slightly with increasing depths. However, according to oxygen mass balance calculations, based on the oxygen molar quantities (nO2), the redox conditions remain constant during HP metamorphism. At shallow levels (<60 km) in the subduction channel, interaction with oxidized fluid seems to have caused an increase of the oxygen fugacity and the oxidation state of exhuming HP rocks. This study suggests that oxygen components are not released in significant amounts during HP metamorphism of subducted oceanic crust and, thus, cannot be responsible for oxidizing the mantle wedge and increasing the oxidation state of sub-arc mantle melts.<br
Keywords: Subducted oceanic crust; Fluids; Oxygen fugacity; Eclogite; Sulfides; Magnetite

REE investigation of the Plattkopf fluorite mineralization an extension of the Vergenoeg fluorite deposit (South Africa) - Günther, Thomas; Klemd, Reiner (BGR-Jahrestagung2014, 2014)
Plattekop hill with its concordant hematite-fluorite ore body represents an extension of the Vergenoeg pipe, one of South Africa's world-class fluorite deposits located in the Bushveld Complex. The pipe-shaped body of Vergenoeg strikes discordantly with a minimum depth of circa 650 meters through the rhyolitic bedrocks of the Palaeoproterozoic Rooiberg Group and accommodates different Fe-mineral dominated rock types, which are enriched in fluorite. Both deposits host an additional commodity in terms of Rare-Earth-Element (REE) minerals in their Fe-oxide (hematite or magnetite) and fluorite rich rocks. These are represented by the fluorocarbonate bastnaesite-(Ce) and the REE-phosphates monazite-(Ce) and xenotime-(Y). Combined whole rock and single grain analyses via XRF and LA-ICP-MS and EMP, respectively show the high REE-potential of the sampled rocks from the uppermost gossan ores of Plattekop and Vergenoeg as well as from their deeper unweathered equivalent rock type with whole rock contents of REEs <4.5 wt. %. Thereby, C1-chondrite normalized REE-patterns show on average (La/Lu)CNratios of <5.3 with a relatively flat trend. The major rock forming minerals contain 100 ppm to 2500 ppm REEs/Fe-oxide and 3000 ppm to 7000 ppm REEs/fluorite on average. The minerals bastnaesite, monazite and xenotime are intercalated between Fe-minerals and fluorites with an abundance of <4 vol. % per sample. The light rare earth elements (LREE) are preferentially incorporated into bastnaesite and monazite with an order of abundance of Ce > La > Nd > Pr in contrast to xenotime, which exhibits enriched concentrations of heavy rare earth elements (HREE) and an order of abundance of Y > Er > Dy > Gd. Average concentrations are between 50 and 60 wt. % REEs/REE-mineral. Petrological and geochemical evidences of sampled rocks suggest a hydrothermal origin for the REE-minerals after the primary mineralization of Vergenoeg and Plattekop precipitated. Secondary fluid inclusions within fluorite record temperatures between 150 °C and 500 °C for late stage hydrothermal events (Borroket al., 1998) from which bastnaesite may have crystallized at intermediate to basic pH conditions. Their alteration to monazite and xenotime marks a change of the hydrothermal conditions to a more acidic and phosphate rich environment. Thereby, balance calculations indicate a renewed REE-enrichment by the P-rich fluids. The remarkable enrichment of fluorite and REE-minerals within the upper 200 meters of Vergenoeg is probably a result of changes in temperature, pressure, and pH of the fluid system due to the channelized upward migration of the hydrothermal solutions towards the top of the pipe and the interaction to the adjacent bedrocks in contact. Regarding the origin of the primary mineralization of Vergenoeg and Plattekop and the mineralizing fluids, negative Eu anomalies (Eu/Eu*) ranging from 0.08 to 0.57 for the Fe-oxides and 0.05 to 0.08 for the fluorites display the influence of reduced conditions in a possible felsic igneous-related source like the Lebowa Granite Suite of the Bushveld Complex. Furthermore, the chemical signature of the Vergenoeg magnetites correlates well with those of igneous Climax-Mo deposits (enriched in Al, Ga, Sn and depleted in Cr, Mg) and therefore, indicates a genetic relationship to the porphyry deposit type.<br

REY and Trace Element Chemistry of Fluorite from Post-Variscan Hydrothermal Veins in Paleozoic Units of the North German Basin - Nadoll, Patrick; Rehm, Meike; Duschl, Florian; Klemd, Reiner; Kraemer, Dennis; Sosnicka, Marta (Geosciences, 2018)
Hydrothermal fluorites from Paleozoic sedimentary rocks and volcanic units in the North German Basin (NGB) have been investigated to create a petrographic and geochemical inventory—with particular focus on strategic elements such as rare earth elements (REE)—and to uncover possible links between the post-Variscan hydrothermal mineralization in the NGB and bordering areas such as the Harz Mountains and Flechtingen Calvörde Block (FCB). Fluorites from ten localities underwent a detailed petrographic examination, including SEM-BSE/CL imagery, and were compositionally analysed using LA-ICP-MS. Overall, REY concentrations are comparatively low in fluorite from all investigated areas—the median sum of REY ranges from 0.3 to 176 ppm. EuropiumCN anomalies are slightly negative or absent, indicating that either the formation fluid experienced temperatures above 250 °C or that fluid-rock interactions and REE enrichment was likely controlled by the source rock (i.e., volcanic) composition and complexation processes. Fluorites from the Altmark-Brandenburg Basin (ABB) and the Lower Saxony Basin (LSB) display distinctly different REYCN signatures, suggesting that fluid compositions and genetic processes such as fluid-rock interaction differed significantly between the two areas. Complex growth zones and REYCN signatures in fluorite from the ABB and the FCB reflect geochemical variability due to adsorption processes and intrinsic crystallographic controls and imply that they are genetically related. Two petrographically and geochemically distinct generations are observed: Fluorite I—light SEM shades, relatively enriched in LREE; Fluorite II—darker SEM shades, comparatively depleted LREE, slightly higher HREE concentrations. These fluorite generations represent zoned (or cyclical) growth within a single progressive hydrothermal event and do not reflect a secondary remobilization process. We demonstrate that increasing Tb/La ratios and decreasing La/Ho ratios can be the result of continuous zoned growth during a single mineralizing event, with significant compositional variations on a micron-scale. This has implications for the interpretation of such trends and hence the inferred genetic evolution of fluorite that displays such geochemical patterns. The complex micro-scale intergrowth of these generations stresses the need for detailed petrographic investigations when geochemical data are collected and interpreted for mineral exploration.<br
Keywords: Remobilization; Trace elements; North German Basin; Rare earth elements; Zoned growth; Hydrothermal veins; Fluorite

Seismic Anisotropy in Subduction Zones: Evaluating the Role of Chloritoid - Lee, Jungjin; Mookherjee, Mainak; Kim, Taehwan; Jung, Haemyeong; Klemd, Reiner (Frontiers in Earth Science, 2021)
Subduction zones are often characterized by the presence of strong trench-parallel seismic anisotropy and large delay times. Hydrous minerals, owing to their large elastic anisotropy and strong lattice preferred orientations (LPOs), are often invoked to explain these observations. However, the elasticity and the LPO of chloritoid, which is one of such hydrous phases relevant in subduction zone settings, are poorly understood. In this study, we measured the LPO of polycrystalline chloritoid in natural rock samples, obtained the LPO-induced seismic anisotropy, and evaluated the thermodynamic stability field of chloritoid in subduction zones. The LPO of chloritoid aggregates displayed a strong alignment of the [001] axes subnormal to the rock foliation, with a girdle distribution of the [100] axes and the (010) poles subparallel to the foliation. New elasticity data of single-crystal chloritoid showed a strong elastic anisotropy of chloritoid with 47% for S-waves (VS) and 22% for P-waves (VP), respectively. The combination of the LPO and the elastic anisotropy of the chloritoid aggregates produced a strong S-wave anisotropy with a maximum AVS of 18% and a P-wave anisotropy with an AVP of 10%. The role of chloritoid LPO in seismic anisotropy was evaluated in natural rock samples and a hypothetical blueschist. Our results indicate that the strong LPO of chloritoid along the subduction interface and in subducting slabs can influence the trench-parallel seismic anisotropy in subduction zones with “cold” geotherms.
CRIS-Team Scopus Importer:2021-04-16
Keywords: chloritoid; EBSD; lattice preferred orientation; seismic anisotropy; subduction zone

Sources, transport, and deposition of metal(loid)s recorded by sulfide and rock geochemistry: constraints from a vertical profile through the epithermal Profitis Ilias Au prospect, Milos Island, Greece - Grosche, Anna; Klemd, Reiner; Denkel, Katja; Keith, Manuel; Haase, Karsten; Voudouris, Panagiotis C.; Alfieris, Dimitrios; Wiedenbeck, Michael (Mineralium Deposita, 2023)
Drill core samples from the Profitis Ilias Pb-Zn-Cu-Ag-Au vein mineralization on Milos Island, Greece provide new insights into (i) the metal sources, (ii) the primary vertical metal(loid) distribution, and (iii) the supergene enrichment processes in a transitional shallow-marine to subaerial hydrothermal environment. Metal contents of unaltered and altered host rocks combined with Pb isotope analyses of hydrothermal sulfides suggest that most metal(loid)s were derived by leaching of basement rocks, whereas the distinct enrichment of Te is related to the addition of Te by a magmatic fluid. The trace element contents of base metal sulfides record decreasing Au, Te, Se, and Co, but increasing Ag, Sb, and Tl concentrations with increasing elevation that can be related to progressive cooling and fluid boiling during the hypogene stage. The formation of base metal veins with porous pyrite hosting hessite inclusions at 400 m below the surface was triggered by vigorous fluid boiling. By contrast, the enrichment of native Au associated with oxidized Fe and Cu phases in the shallower part of the hydrothermal system resulted from supergene remobilization of trace Au by oxidizing meteoric water after tectonic exhumation to subaerial levels. Disseminated pyrite with higher Tl/Pb ratios and locally elevated Hg concentrations relative to vein pyrite reflects infiltration of the host rocks by boiled liquids and condensed vapor fluids. The vertical and temporal evolution of the Profitis Ilias mineralization, therefore, provides unique insights into the transport and precipitation of Au, Ag, Te, and related metal(loid)s by multiple fluid processes.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Boiling; Epithermal deposits; Gold; Supergene enrichment; Tellurium

Spatial Variations in Magmatic Volatile Influx and Fluid Boiling in the Submarine Hydrothermal Systems of Niuatahi Caldera, Tonga Rear-Arc - Falkenberg, Jan; Keith, Manuel; Haase, Karsten; Sporer, Christian; Bach, Wolfgang; Klemd, Reiner; Strauss, Harald; Storch, Bettina; Peters, Christian; Rubin, Kenneth H.; Anderson, Melissa O. (Geochemistry Geophysics Geosystems, 2022)
Submarine caldera volcanoes may host several hydrothermal systems along the caldera wall and related to volcanic cones. Fluid boiling and magmatic volatile influx are common processes in shallow (<2,000 mbsl) subduction zone-related environments causing variations in the mineralogical and chemical composition of seafloor hydrothermal mineralizations that remain poorly constrained. The submarine caldera of Niuatahi volcano, Tonga rear-arc, hosts four active vent sites discharging high temperature fluids (<334 degrees C) with variable salinities (369-583 mM Cl) that are indicative of fluid boiling, recorded by distinct Te/As and Te/Au in pyrite, sphalerite, and chalcopyrite. High sulfidation mineral assemblages (e.g., enargite), stable S isotope data and similar trace element signatures in sulfides and native S condensates suggest a minor and/or infrequent contribution of magmatic SO2 to the hydrothermal systems located proximal to the caldera center causing a volatile element (e.g., Se, Bi, Te) enrichment. The hydrothermal system at the northern caldera wall is decoupled from the magmatic SO2 source, as revealed by radiogenic Pb isotopes. Instead, S isotope and trace element constraints propose a host rock-dominated hydrothermal system, lacking a magmatic volatile influx. The observed hydrothermal fractionation processes (fluid boiling) and the distinct metal (loid) sources (magmatic volatiles vs. host rock) represent a continuum from magmatic volatile- to host rock-dominated hydrothermal systems within the Niuatahi caldera. This leads to seafloor mineralizations with spatially selective trace element enrichments, like Te, Se, and Bi (+/- Au, Ag) in the caldera center compared to Au, Ag, Zn, Cd, and Pb at the northern caldera wall.
CRIS-Team WoS Importer:2022-04-29

Stability conditions and compositional variations of deerite in high-pressure meta-ironstone during subduction–exhumation processes (SW Tianshan, China) - Li, Ji Lei; Klemd, Reiner; Höfer, Heidi E.; Gao, Jun (Lithos, 2021)
Index minerals in metamorphic rocks, such as coesite, glaucophane, or lawsonite, are of great importance to understand high-pressure (HP) to ultrahigh-pressure (UHP) metamorphism, the thermal gradient, and the geodynamics of subduction zones. Deerite is thought to be diagnostic for blueschist-facies metamorphism in cold subduction environments and a sensitive indicator of the oxygen fugacity (fO2) in Fe-rich rocks. However, little is known concerning its stability and compositional variation during subduction and exhumation cycles. In this study, we provide the first detailed investigation of deerite in eclogite-facies meta‑ironstones (deerite–garnet riebeckitite) from the Southwestern Tianshan (U)HP metamorphic belt. Petrological observation and textural evidence suggest that the meta‑ironstones –enclosing eclogite blocks– form part of an initially coherent volcano-sedimentary sequence that underwent a common tectono-metamorphic evolution, including HP metamorphism and subsequent exhumation. Two types of deerite, which display a different texture (inclusion vs. matrix) and composition (TiO2 content), occur in the deerite–garnet riebeckitite. Dee_1 and aegirine–augite appear exclusively as fine-grained inclusions in garnet, and together with garnet, riebeckite, quartz and magnetite form the peak metamorphic mineral assemblages at P–T conditions of 510 °C and 2.6 GPa. Matrix deerite (Dee_2), on the other hand, mainly occurs as coarse-grained rods and acicular needle-like grains in quartz, and rarely as inclusions in riebeckite and garnet intimately in the riebeckitite, representing the blueschist-facies retrogression of the meta‑ironstones during exhumation. The garnet–clinopyroxene oxybarometer and thermodynamic calculations show that the fO2 of the deerite–garnet riebeckitite increases from ΔFMQ–0.64 at the peak eclogite-facies stage to ΔFMQ+1.5 at the blueschist-facies retrogression. This fO2 variation corresponds to the chemical variation of deerite, whereby the TiO2 content increases gradually from <0.1 wt% in the Dee_1 in garnet to about 5 wt% in the matrix Dee_2. Our study reveals the detailed metamorphic P–T–fO2 evolution of the prograde eclogite- and retrograde blueschist-facies deerite-bearing meta‑ironstones during subduction–exhumation processes. This study further emphasizes the potential of deerite to reveal the P–T–fO2 evolution of subduction-related high-pressure rocks.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Deerite; Eclogite; Oxygen fugacity; P–T evolution; Subduction zone; Tianshan

Subduction and exhumation mechanisms of ultra-high and high-P oceanic and continental crust at Makbal (Tianshan, Kazakhstan and Kyrgyzstan) - Meyer, Melanie; Klemd, Reiner; Hegner, E.; Konopelko, Dmitry (Journal of Metamorphic Geology, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.subduc

Subduction channel fluid–rock interaction and mass transfer: Constraints from a retrograde vein in blueschist (SW Tianshan, China) - Li, Jilei; John, Timm; Gao, Jun; Klemd, Reiner; Wang, Xin-Shui (Chemical Geology, 2017)
One widely neglected part of the subduction zone fluid cycle is the retrograde fluid flow along the plate interface. This fluid flow may facilitate the exhumation of slab-derived rocks within the subduction channel. However, our understanding on the nature and behavior of these retrograde fluids is still insufficient. Retrograde veins preserved in HP–UHP rocks can provide valuable information about fluid activities and mass transfer at the plate interface and exhumation processes. In this study, we present a petrological and geochemical investigation of a typical retrograde vein and its blueschist host rock, which occurs throughout the whole Akeyazi (U)HP terrane in the Chinese southwestern Tianshan. The magnetite-bearing albite–calcite vein, representing an external fluid pathway, crosscuts the host blueschist that mainly consists of glaucophane, garnet, epidote and titanite. Along the fluid conduit the immediate wall-rock experienced greenschist-facies overprinting as displayed by an albite-rich selvage that grades into a chlorite–biotite selvage towards the host rock. The replacements of garnet by chlorite and glaucophane by albite are thought to have occurred due to an interface-coupled dissolution-precipitation mechanism. Mass balance calculations show that during fluid–rock interaction large amounts of LILE (K–Rb–Ba–Cs and Pb), Cu and CO2 were added to the selvages (mass gain > 200%), whereas the altered wall-rock released significant amounts of Ca, Li, Sr, REE and transition metal elements (V–Mn–Co–Ni–Zn) (mass loss mainly between 40 and 100%) due to the dissolution of glaucophane, garnet and epidote. The chlorite–biotite selvage experienced additional SiO2 and Na2O mass losses as well as FeO, MgO and H2O mass gains, whereas the albite-rich selvage underwent exactly the opposite mass transfer with respect to these components. The Al, Ti, Nb, Ta and Cr contents were constant during the alteration. Therefore, the retrograde fluid causing greenschist-facies overprinting of the blueschist host in the subduction channel (at ca. 30 km depth) is proposed to be oxidized and enriched in LILE, Cu and CO2components, whereas Ca, Li, Sr, REE, Y and transition metal elements (V–Mn–Co–Ni–Zn) are thought to have been mobilized during fluid-rock interaction. In addition, the main fluid sources (sediments, oceanic crust or serpentinites) diversely contribute to retrograde fluids at different depths in the subduction channel.<br
Keywords: Element mobility; Fluid–rock interaction; Retrograde fluid flow; Albite vein; Blueschist; Tianshan

Subduction initiation of the Neo-Tethys oceanic lithosphere by collision‐induced subduction transference - Wang, Xuhui; Lang, Xinghai; Klemd, Reiner; Deng, Yulin; Tang, Juxing (Gondwana Research, 2022)
Collision-induced subduction transference may have triggered subduction of the Neo-Tethys oceanic lithosphere. To verify this proposition, we present an integrated geochemical and geochronological studies of new and published data of the Permian-Triassic magmatism in the Lhasa Terrane. The newly identified Chongni mafic intrusions (gabbros and diorites) in the North Lhasa Terrane (NLT) were emplaced during the Early Permian (ca. 275 Ma). The mafic rocks have (87Sr/86Sr)t ratios between 0.7037 and 0.7042, and εNd(t) values between + 5.2 and + 5.8. The zircons of the Chongni mafic rock samples have εHf(t) values from + 9.1 to + 12.9. The isotopic data in conjunction with trace element features suggest that the Chongni mafic intrusions have been derived mainly by partial melting of a metasomatized mantle wedge source. The newly identified Quxu granodiorites and hornblende gabbros in the South Lhasa Terrane (SLT) were emplaced in the Late Triassic (ca. 228–203 Ma). The granodiorites are characterized by (87Sr/86Sr)t ratios of 0.7036–0.7037 and εNd(t) values of +6.6 to +6.7, while the hornblende gabbro samples have (87Sr/86Sr)t ratios of 0.7033–0.7035 and εNd(t) values of +7.3 to +7.4. The zircons of the granodiorite and hornblende gabbro samples revealed εHf(t) values of +10.3 to +14.0 and +10.8 to +16.4, respectively. The isotopic data in combination with trace element signatures suggest that the granodiorites were derived from a juvenile basaltic lower crust with a minor input of mantle components, while the hornblende gabbros are interpreted to have formed during partial melting of a formerly metasomatized depleted mantle wedge source. The Early Permian and Late Triassic magmatic rocks consistently show arc-related signatures, which probably record the northward subduction of the Sumdo Paleo-Tethys and the Neo-Tethys oceanic slabs, respectively. This evidence, in combination with that of other studies on the Permian-Triassic magmatism across the Lhasa Terrane, indicates that arc magmatism within the NLT switched to collisional magmatism at ca. 260 Ma due to the collision of oceanic islands/plateaus and, further on, the collision of the SLT with the NLT. Furthermore, the change from ca. 265–255 Ma alkaline magmatism to ca. 240–200 Ma calc‐alkaline magmatism within the SLT may reflect the geodynamic transition from lithospheric extension to Andean-style orogenesis. Therefore, we propose that subduction initiation of the Neo-Tethys oceanic lithosphere in the Tibetan Plateau resulted from the southward transference of the Sumdo Paleo-Tethys subduction zone, involving the collision of oceanic islands/plateaus and, subsequently, the collision of the SLT with the NLT. Additionally, the geological records of the Tethyan orogenic system suggest that the subduction initiation of the Neo-Tethys oceanic lithosphere is a uniform response to the collision between Cimmeria and Eurasia.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Lhasa Terrane; Neo-Tethys; Plate tectonics; Subduction initiation; Subduction transference

Subsurface Microbial Colonization at Mineral-Filled Veins in 2-Billion-Year-Old Mafic Rock from the Bushveld Igneous Complex, South Africa - Suzuki, Yohey; Webb, Susan J.; Kouduka, Mariko; Kobayashi, Hanae; Castillo, Julio; Kallmeyer, Jens; Moganedi, Kgabo; Allwright, Amy J.; Klemd, Reiner; Roelofse, Frederick; Mapiloko, Mabatho; Hill, Stuart J.; et al. (Microbial Ecology, 2024)
Recent advances in subsurface microbiology have demonstrated the habitability of multi-million-year-old igneous rocks, despite the scarce energy supply from rock-water interactions. Given the minimal evolution coupled with exceedingly slow metabolic rates in subsurface ecosystems, spatiotemporally stable igneous rocks can sustain microbes over geological time scales. This study investigated a 2-billion-year-old mafic rock in the Bushveld Igneous Complex, South Africa, where ultradeep drilling is being executed by the International Continental Scientific Drilling Program (ICDP). New procedures were successfully developed to simultaneously detect indigenous and contaminant microbial cells in a drill core sample. Precision rock sectioning coupled with infrared, fluorescence, and electron microscopy imaging of the rock section with submicron resolution revealed microbial colonization in veins filled with clay minerals. The entry and exit of microbial cells in the veins are severely limited by tight packing with clay minerals, the formation of which supplies energy sources for long-term habitability. Further microbiological characterization of drilled rock cores from the Bushveld Igneous Complex will expand the understanding of microbial evolution in deep igneous rocks over 2 billion years.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Bushveld Drilling Project (BVDP); Deep biosphere; Life detection; Rock-hosted life; Subsurface microbes

Systematic variations in magmatic sulphide chemistry from mid-ocean ridges, back-arc basins and island arcs - Keith, Manuel; Haase, Karsten; Klemd, Reiner; Schwarz-Schampera, Ulrich; Franke, Henrike (Chemical Geology, 2017)
Immiscible sulphide liquids preserved as magmatic sulphide globules are hosted in igneous rocks of highly variable composition formed during magmatic processes at different tectonic settings. Here we report on compositional in situ data of magmatic sulphides from mid-ocean ridge, back-arc and island arc magmatic systems. Iron-Ni-rich monosulphide solid solutions (mss) that mainly consist of pyrrhotite and pentlandite are the dominant phases in magmatic sulphide globules. In subduction-related magmas mss are most abundant in relatively evolved melts and characterised by low Ni and high Fe contents, as well as low Ni/Cu ratios (< 1). In contrast, mss from mid-ocean ridges and back-arcs without subduction input occur in mafic rocks and have high Ni/Cu ratios (> 1). Thus, mss chemistry varies systematically in lavas from the different tectonic settings in terms of their Fe-Ni distribution and Ni/Cu ratio. The observed mineralogical and chemical variations between mss from the different settings reflect early S saturation accompanied by olivine fractionation along mid-ocean ridges compared to later stage S saturation in arc systems associated with Fe-Ti oxide fractionation. These systematics are probably related to the relatively oxidised character of subduction zone magmas opposed to more reduced mid-ocean ridge melts. Large Ni/Cu variations in mss from the same locality and in individual samples suggest that S saturation is a multistage or continuous process leading to inclusions of magmatic sulphides that represent different fractionation stages in the ascending magm
Keywords: Chalcophile elements; Magmatic sulphides; Monosulphide solid solutions; Oxygen fugacity; Sulphur saturation

Systematic variations of trace element and sulfur isotope compositions in pyrite with stratigraphic depth in the Skouriotissa volcanic-hosted massive sulfide deposit, Troodos ophiolite, Cyprus - Keith, Manuel; Haase, Karsten; Klemd, Reiner; Krumm, Stefan; Strauss, Harald (Chemical Geology, 2016)

Temperature-controlled Se-S isotope fractionation during seawater mixing and sulfide precipitation in black smoker chimneys - Grosche, Anna; Keith, Manuel; Klemd, Reiner; Strauss, Harald; Rosca, Carolina; König, Stephan (Geochimica Et Cosmochimica Acta, 2024)
Submarine hydrothermal venting leads to the formation of black smoker chimneys with complex internal zoning. These emerge through mineral precipitation under changing fluid conditions caused by variable degrees of fluid-seawater mixing. This study explores the potential of selenium (Se) isotopes as a novel tool to understand the enrichment processes and identify the sources of chalcophile elements in seafloor hydrothermal systems. In-situ trace element analysis of hydrothermal sulfides combined with high-precision Se and S isotope analysis of micro-domains through the wall of black smoker chimneys from the Nifonea vent field (New Hebrides back-arc, SW Pacific) revealed variations in sulfide chemistry at small spatial resolution. The δ82/76Se values (deviation of 82Se/76Se relative to NIST SRM 3149) of the sulfide micro-domains range from +0.6 to −3.7 ‰ ± 0.2 ‰ (2 s.d.) with a general decrease from the inner chalcopyrite lining towards the outer chimney wall. The highest δ82/76Se values overlap with the mean value of fresh basaltic glass from Nifonea caldera (+0.6 ± 0.4 ‰, n = 4), indicating that Se is primarily leached from the surrounding back-arc basalts. The trace element contents of sulfides revealed systematic variations between vent sites, linked to differences in fluid vapor content induced by sub-seafloor boiling, which did not cause any Se isotope fractionation. Instead, decreasing Se/Tl ratios of pyrite together with decreasing δ82/76Se values of sulfide micro-domains and calculated δ34SH2S fluid values towards the outer chimney wall are indicative of temperature-dependent Se and S isotope fractionation at 370 to <200 °C during fluid-seawater mixing within the chimney wall. This study presents Se isotopes as a new robust instrument to unravel the sources of chalcophile elements and related fluid processes in seawater-diluted hydrothermal systems, enhancing our understanding of their geochemical complexities.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Black smoker; Hydrothermal vent; Metal sources; Selenium; Stable isotopes

The assembly of Rodinia: The correlation of early Neoproterozoic (ca. 900 Ma) high-grade metamorphism and continental arc formation in the southern Beishan Orogen, southern Central Asian Orogenic Belt (CAOB) - Zong, Keqing; Klemd, Reiner; Yuan, Yu; He, Zhenyu; Guo, Jingliang; Shi, Xiaoli; Liu, Yongsheng; Hu, Zhaochu; Zhang, Zeming (Precambrian Research, 2017)
An early extensive Neoproterozoic (ca. 900 Ma) continental magmatic arc system covering hundreds of kilometers has been reported to occur in the South Beishan Orogenic Belt (SBOB) and the Central Tianshan (CTA) in the southern Central Asian Orogenic Belt (CAOB). However, evidence for coeval high-grade metamorphism and thus the formation of an accretionary orogen in the framework of Rodinia is ambiguous or absent. This study provides new petrological, geochemical and geochronological data for garnet-bearing schists (quartz + garnet + biotite + plagioclase ± muscovite) from the SBOB in order to constrain its Neoproterozoic metamorphic history. The metamorphic zircon rims are either unzoned or display sector zoning in CL-images and reveal REE patterns with flat HREE patterns and negative Eu anomalies, which are interpreted to be in chemical equilibrium with garnet and plagioclase. The zircon U-Pb dating yields concordant U-Pb ages of 900 ± 3 Ma, 897 ± 2 Ma and 898 ± 4 Ma for the metamorphic zircon rims. The inherited detrital zircon cores of one sample display a concordant U-Pb age of 1397 ± 5 Ma that is consistent with the timing of formation for the extensive Mesoproterozoic continental arc in the SBOB and CTA. Based on phase equilibrium geothermobarometry and average P-T thermobarometric calculations, minimum amphibolite-facies P-T conditions are estimated to be >600 °C at pressure >0.6 GPa, which is thought to have been overprinted by subsequent Paleozoic metamorphism. However, the Ti-in-zircon thermometer still reveals temperatures of up to 840 °C using the composition of metamorphic zircon rims, suggesting former ca. 900 Ma granulite-facies peak metamorphic temperatures. The combined petrological and geochronological evidence in conjunction with the continental affinity of the regional metamorphic rocks suggests that the SBOB and the eastern CTA experienced an early Neoproterozoic accretionary orogenesis during the final assembly stage of Rodinia.<br
Keywords: South Beishan Orogenic Belt (SBOB); Central Asian Orogenic Belt (CAOB); Early Neoproterozoic; Continental magmatic arc; Rodinia assembly

The Central-Sudetic ophiolites – Remnants of the SSZ-type Devonian oceanic lithosphere in the European part of the Variscan Orogen - Wojtulek, Piotr Marian; Schulz, Bernhard; Klemd, Reiner; Gil, Grzegorz; Dajek, Michał; Delura, Katarzyna (Gondwana Research, 2021)
The Variscan Central-Sudetic Ophiolites (CSO) are located in the Sudetes, the NE segment of the Bohemian Massif. The Devonian CSO display highly depleted, harzburgite mantle sections containing gabbroic dykes and local occurrences of mostly isotropic, large gabbroic bodies as well as volcanic rocks. The ultramafic rocks locally show melt percolation-derived clinopyroxene-olivine aggregates and chromitites. The low REE composition and depletion in LREE relative to HREE of the clinopyroxene as well as the chromite Cr# and Mg# values are typical for phases formed from refractory melts occurring in the supra-subduction zone environment. The gabbroic bodies consist of differently evolved, mostly cumulate rocks, while the volcanic rocks form a relatively monotonous basalt sequence. The trace element compositions of both the plutonic and volcanic rocks display depleted N-MORB affinities, their derivation from a refractory mantle source is further reflected by previously published depleted mantle-like Sr-Nd isotopic compositions. The ultramafic and mafic members of the CSO show greenschist- to lower amphibolite-facies metamorphic overprints. The occurrence of depleted harzburgites and isotropic gabbros forming the mantle and the crustal sections of the CSO, respectively, indicate intermediate- to slow-spreading conditions and a heterogeneous structure of the oceanic lithosphere, untypical for layered ophiolites. The geochemical characteristics of the melt-percolation phases of the ultramafic rocks, the bulk-rock compositions of the mafic rocks and the homogeneous volcanic sequences suggest a formation of the CSO in a mature back-arc basin setting, lacking subduction-derived contamination. Spreading rate conditions and geochemical affinities of the CSO are similar to those of other Devonian ophiolites localized along the Variscan Belt, for instance the Upper Ophiolitic Units in the NW Iberian Massif (Spain), thereby confirming the general absence of N-MORB type lithosphere in the European Variscan Orogen.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Bohemian Massif; Oceanic lithosphere; Ophiolite; Sudetes; Supra-subduction zone; Variscan Orogen

The Central Tianshan Block: A microcontinent with a Neoarchean-Paleoproterozoic basement in the southwestern Central Asian Orogenic Belt - Wang, Xin-Shui; Gao, Jun; Klemd, Reiner; Jiang, Tuo; Li, Jilei; Zhang, Xi; Xue, Shengchao (Precambrian Research, 2017)
The Central Tianshan Block (CTB) is one of the major continental constituents of the western Central Asian Orogenic Belt (CAOB). Its nature and origin is essential for understanding the accretionary processes and the reconstruction of the architectural framework of the CAOB. The Wuwamen Metamorphic Complex (WMC), which is believed to represent the basement of the CTB, was incorporated into the Wuwamen ophiolitic mélange during the Paleozoic evolution of the South Tianshan Ocean. The WMC is mainly composed of amphibolite-facies volcano-sedimentary rocks, including migmatites, orthogneisses, amphibolites, schists and locally marbles. Zircon U–Pb geochronology suggests that the protoliths of the interlayered biotite-two feldspar and biotite-plagioclase-hornblende gneisses in the Yangjuan area were formed between 2529 and 2513 Ma and overprinted by amphibolite-facies metamorphism between 1815 and 1809 Ma. Subsequently, the gneisses were intruded by ∼1724 Ma meta-mafic dykes and ∼787 Ma leucogranite dykes/veins. Geochemical data reveal that the biotite-two feldspar gneisses have high-silica adakite affinities with high SiO2 and Na2O contents as well as high Sr/Y ratios (61–117) and slightly evolved zircon Hf isotopic compositions. Consequently, they are interpreted to be the products of partial melting of relatively old subducted oceanic crust. In contrast, the interlayered biotite-plagioclase-hornblende gneisses have high MgO, Cr, Co and Ni contents and prominent negative Nb–Ta–Ti anomalies, indicating derivation from partial melting of an ancient sub-continental lithospheric mantle in a continental arc setting. The ∼1.72 Ga meta-mafic dykes have geochemical similarities of typical Fe-Ti basalts and are characterized by incompatible element enrichments and primitive Sr–Nd–Hf isotopic signatures ((87Sr/86Sr)i = 0.703446 − 0.703535); ɛNd(t) = +6.49 to +6.90; zircon ɛHf(t) = +0.57 to +10.6), which is consistent with partial melting of a relatively fertile, isotopically depleted asthenospheric mantle in a post-collisional extensional setting. In addition, the ∼787 Ma leucogranites are trondhjemitic in composition and display extremely low total REE contents and highly evolved Nd–Hf isotopic signatures (ɛNd(t) = −4.71 to −4.53; zircon ɛHf(t) = −19.4 to −13.0). They are thought to have no petrogenetic relationship with the host orthogneisses and to be products of a foreign melt injection. Our new data provide robust evidence for a Neoarchean–Paleoproterozoic basement of the CTB. Comparison of the tectono-thermal-magmatic events reveals that the CTB and the Tarim Craton have a partly overlapping Precambrian crustal evolution, and thus the CTB could have originated from the Tarim Craton. However, a major difference between both is the presence of juvenile Mesoproterozoic magmatism in the CTB and its absence in the Tarim Craton and, therefore, further geological and geochronological research is required to determine the precise origin of the CTB and its tectonic affinity with adjacent terranes in the western CAOB.<br
Keywords: Central Tianshan Block; Crustal evolution; Precambrian basement; Tarim Craton; Central Asian Orogenic Belt

The collision between the Yili and Tarim blocks of the Southwestern Altaids: Geochemical and age constraints of a leucogranite dike crosscutting the HP-LT metamorphic belt in the Chinese Tianshan Orogen. - Gao, Jun; Klemd, Reiner; Qian, Qing; Zhang, Xi; Li, Jilei; Jiang, Tuo; Yang, Yongqiang (Tectonophysics, 2011)
A ca. 600m-long, 0.5-20m-wide NW-SE trending granite dike crosscuts the high pressure-low temperature (HP-LT) Tianshan metamorphic belt, the foliation of which is parallel to the main ENE regional trend in the Chinese South Tianshan Orogen. It is mainly composed of plagioclase, K-feldspar, quartz, muscovite, biotite and secondary chlorite, while fluorite, zircon and xenotime occur as accessories. The immediate country rock is a quartz-biotite-plagioclase schist, which grades several tens of meters away from the granite dike into a chlorite-mica-albite schist. The latter schist is intimately intercalated with blueschist layers and boudins. The A/CNK value of the granite dike samples varies from 1.15 to 1.27 indicating a strongly peraluminous composition. CaO/Na2O ranges from 0.06 to 0.17 and Al2O3/TiO2 from 240 to 525, similar to the ratios of strongly peraluminous (SP) granites exposed in 'high-pressure' collision zones such as the Himalayas. A zircon U-Pb age of 285Ma was obtained for the granite dike, thus constraining the upper limit for the age of HP-LT metamorphism. The petrological and geochemical data suggest that the SP leucogranite dike intruded during the exhumation of overthickened crust in the post-collisional setting between the Yili (-Central Tianshan) and Tarim blocks. The dataset presented here in conjunction with previously published data corroborate that the HP-LT metamorphism must have occurred earlier than the Permian in the Tianshan Orogen. Therefore, the collision between the Yili (-Central Tianshan) and Tarim blocks and the final amalgamation of the Southwestern Altaids must have been terminated in Late Paleozoic and not in Triassic times as previously suggested. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.c3geoc.thecol
Keywords: Collision; Leucogranite dike; Southwestern Altaids; Tarim block; Tianshan; Yili block

The formation of a giant post-collision porphyry copper system: A case study of the Jiama deposit, Tibet - Sun, Miao; Tang, Ju Xing; Klemd, Reiner; Lin, Bin; Tang, Pan; Zhang, Ze bin; Chen, Wei; Li, Fa Qiao; Qi, Jing; Chen, Han; Gu, Feng hua (Geological Society of America Bulletin, 2024)
The large magma reservoirs underlying world-class porphyry deposits are one of the key factors in their formation, which thus led to the present study focusing on the unmineralized intrusive rocks underlying the porphyry molybdenum-copper orebody of the post-collisional Jiama porphyry-skarn copper-polymetallic deposit in southern Tibet. The Jiama porphyry intrusion comprises intermediate-silica quartz diorite, monzogranite, and granodiorite porphyries, as well a high-silica granite porphyry. The intrusive rocks suite exhibits similar whole-rock Sr-Nd isotopic compositions [εNd(t) = −3.9 to −0.8], suggesting a common, non-radiogenic magma source. Yet, these rocks have distinct geochemical characteristics. The intermediate- silica rocks are relatively enriched in Ba and Sr with minor Eu anomalies, and show adakite-like geochemical characteristics. In contrast, the high-silica granite porphyry is strongly depleted in Ba, Sr, and Eu, and lacks adakite-like geochemical characteristics. We propose that the high-silica granite porphyry represents highly fractionated melt extracted from a silicic mush reservoir (crystallinity of ∼40%–65%), and that the monzogranite and granodiorite porphyries constitute the complementary residual silicic cumulates. High crystallinity facilitates the formation of connected fluid pathways, allowing the efficient removal of volatiles from the remaining silicic melt and a rapid flux of the ore-forming fluids toward the apical parts of the large magma reservoir. Less-evolved mafic melt is believed to have repeatedly intruded the base of the magma reservoir, thereby releasing volatiles and water into the silicic mush systems. The volatiles migrated upward through the fluid channels and accumulated in the apical part of the magma reservoir, subsequently, as a result of the overpressure in the roof zone, ore-forming fluids and successive batches of magma were expelled together, thereby forming the Jiama porphyry-skarn deposit.
CRIS-Team Scopus Importer:2024-03-29

The formation of shoshonitic magma and its relationship to porphyry-type mineralisation: the Maronia pluton in NE Greece - Schaarschmidt, Anna; Klemd, Reiner; Regelous, Marcel; Voudouris, Panagiotis C.; Melfos, Vasilios; Haase, Karsten (Lithos, 2021)
The Oligocene shoshonitic Maronia pluton in NE Greece is part of an age-progressive belt of calc-alkaline intrusions and associated with a porphyry Cu-Mo±Re±Au mineralisation. We present new data on mineral and whole rock compositions as well as Sr, Nd and Pb isotopes of the monzodioritic to granitic rocks from Maronia, including the mineralised microgranite, which crosscuts the main intrusion. The age progression of the plutons in NE Greece follows the southward-directed trench retreat implying that the magmas formed during subduction of continental lithosphere after the closure of the Pindos ocean. The shoshonitic magmas of Maronia were generated by hydrous melting of a phlogopite-bearing mantle that was enriched by 3-5% of slab-derived sediment melts. A lower degree of melting controls the higher K, LILE and incompatible element contents of the shoshonitic magmas in comparison to the neighbouring calc-alkaline magmas. The mafic shoshonitic rocks in NE Greece contain much higher P2O5 contents than the associated calc-alkaline magmas, which probably reflects subducted phosphate-rich sediments in their source. Constant Sr- and Nd-isotopes with increasing SiO2 contents imply minimal crustal assimilation and that felsic magmas including the mineralised porphyritic granite were generated by fractional crystallisation of mafic magmas. Amphibole and apatite analyses provide evidence for the intrusion of S-poor, Cl-rich magmas at 5 to 6 km depths, followed by rapid uplift and exsolution of magmatic fluids. Late granitic dikes at Maronia indicate that volatiles, sulphur and metals became enriched during the late stages of the magma evolution.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Magmatic sulphur; Metal budget; Porphyry copper deposits; Sediment subduction; Shoshonitic magmatism

The origin and crustal evolution of microcontinents in the Beishan orogen of the southern Central Asian Orogenic Belt - He, Zhenyu; Klemd, Reiner; Yan, Lili; Zhang, Zeming (Earth-Science Reviews, 2018)
Microcontinents with Precambrian basement have played an important role in the accretionary and amalgamation history of the Central Asian Orogenic Belt (CAOB). However, their geological evolution is only poorly constrained due to restricted exposure of the Precambrian rocks, which were extensively overprinted mainly by Paleozoic tectonic, metamorphic and magmatic events. In the present study, in situ zircon U–Pb age and Hf isotopic data of 64 Paleozoic and early Mesozoic (from 499 to 217 Ma) as well as 14 Mesoproterozoic and Neoproterozoic (from 1555 to 871 Ma) granitic samples from four major arc terranes of the Beishan orogen (southernmost CAOB) were compiled in order to assess the nature of their crustal basement as well as the subsequent Paleozoic tectonic evolution. Zircon εHf(t) values and calculated Hf model ages are similar for all arc terranes with Hf model age peaks at approximately 1.0–0.8 Ga and 2.0–1.8 Ga. We suggest that all of these Paleozoic arc terranes formed on a single, uniform Precambrian continental terrane. Furthermore, this continental terrane shows typical characteristics of Mesoproterozoic ( 1.4 Ga) juvenile crustal growth, which may have been part of an extensive Mesoproterozoic continental terrane, now tectonically fragmented and located over a distance of more than a thousand kilometers in the southern CAOB. Among the cratons bordering the CAOB, Balticadisplays most similarities with this continental terrane, while a Mesoproterozoic correlation with the Tarim Craton is rather questionable.<br
Keywords: Zircon Hf–O isotope; Mesoproterozoic crustal growth; Beishan orogen; Southern Central Asian Orogenic Belt; Granitoids

The subduction-zone fluid: Evidence from (ultra-) high-pressure metamorphic rocks - Gao, Jun; Li, Jilei; Ma, Zhipei; Klemd, Reiner (Acta Geologica Sinica, 2024)
The oceanic subduction zone is the locality where the magmatic activity, the high-to ultra-highpressure metamorphism, the intermediate-depth earthquake, mass transfer between crust and mantle, the element recycling and the large-scale mineralization of copper and gold occur concentratedly on the earth. The H2O-rich fluid not only controls these geological processes but also deeply influences the global recycling of volatiles such as carbon, sulfur and etc. After the altered oceanic lithosphere and the overlying sediments are subducted into the intermediate to the deep depth to a subduction zone (15-300 km), the fluid is continuously released by the breakdown of hydrous minerals at different depths, accompanied by the prograde metamorphism from the prehnite-pumpellyite facies to ultra-high-pressure eclogite facies. The fluid released by the subducted oceanic crust is mainly aqueous in most subduction zones, except in an ultra-high geothermal environment. However, the characteristics of fluids obviously vary with the depth at which the fluid is generated. The high-pressure to ultra-high-pressure terranes exposed in global orogens have preserved robust evidence of the fluid activity, such as segregations, veins, hydro-breccias and etc. The primary fluid inclusion entrapped in omphacite, garnet, epidote and other minerals is a direct record of fluids. This fluid is a type of chloride-bearing dilute aqueous solution containing the components, such as CO23-, SO24-, HS- and etc. at the intermediate depth (<65 km) in a subduction zone. Furthermore, the major element solute (Si, Al, Ca, Mg, Fe, Na) content of fluids has two to three times the total dissolved solids of seawater and the trace element concentration displays the enrichment of large ion lithophileelements (LILEs) and light elements (B and Li), and the depletion of high field strength elements (HFSEs). Moreover, the fluid will change to the volatile (CH4, C2H6, H2S and etc.)-bearing solution with a character resembling the supercritical fluid when the subduction depth is over 65 km. The content of major element solutes has remarkably increased and has also loaded considerable concentrations of HFSEs and transitional metallogenic elements besides LILEs. The depth between 65-100 km in a subduction zone is the interval where the aqueous fluid has been gradually transformed to the supercritical one. This fluid displays a "sub-supercritical" character. The redox property and the element dissolving capacity have transformed gradually, accompanied by the final consumption of lawsonites and amphiboles. The O, Sr, Nd and metal isotopic tracking studies of high-pressure metamorphic rocks and related veins indicate that the various fluid sources have included altered basic oceanic crusts, altered mantle peridotites and sediments and have also preserved the imprint of seafloor hydrothermal alterations. The channelized fluid is transferred and episodically transported along the networking fractures. The scale of fluid flow can reach up to a km-scale. The duration time of fluid activity varies from several months to several hundred years. Although considerable understanding of subduction-zone fluids has been achieved up to now, many controversies and scientific problems remain to be explored in the future.
CRIS-Team Scopus Importer:2024-05-10
Keywords: character of fluid phase; chemical composition; geological evidence; recycle of C and S; subduction-zone fluid

The tectonic evolution of the Irtysh tectonic belt: New zircon U–Pb ages of arc-related and collisional granitoids in the Kalaxiangar tectonic belt, NW China - Hong, Tao; Klemd, Reiner; Gao, Jun; Xiang, Peng; Xu, Xing-Wang; You, Jun; Wang, Xin-Shui; Wu, Chu; Li, Hao; Ke, Qiang (Lithos, 2017)
Precise geochronological constraints of the Irtysh tectonic belt situated between the Saur Island Arc and the Altay Terrane are crucial to a better understanding of the tectonic evolution of the Central Asian Orogenic Belt (CAOB). Recently, we discovered repeatedly deformed arc-related and collisional granitoids in the Kalaxiangar tectonic belt (KTB), which is located in the eastern part of the Irtysh tectonic belt. In this study, we report new whole-rock geochemical, zircon U–Pb and Hf isotopic data of the arc-related and collisional granitoids. Our data reveal that 1) arc-related granodioritic porphyries formed at ca. 382–374 Ma. Recrystallized zircon grains from a (ultra-)mylonitic granodiorite of the Laoshankou zone in the southern KTB display a U–Pb age of ca. 360 Ma; 2) syn-collisional granodioritic porphyries, which distribute along faults and parallel to the cleavage, were emplaced at ca. 367–356 Ma, with εHf(t) values varying from + 7.8 to + 14.2 and Hf model ages from 873 to 459 Ma; 3) a post-collisional A-type granodioritic porphyry, which crosscuts the NW-NNW trending schistosity of the metasedimentary country rocks at a low angle, has an age of ca. 324–320 Ma, while the εHf(t)values range from + 7.6 to + 14.4 with Hf model ages from 850 to 416 Ma; 4) post-collisional strike-slip A-type granite dykes, exposed along strike-slip faults, gave ages between 287 and 279 Ma, whereas the εHf(t) values range from + 4.9 to + 12.7 and the Hf model ages from 995 to 500 Ma; and 5) A-type biotite granite dykes, which intruded along conjugate tension joints, have ages of 274–271 Ma, and εHf(t) values from + 1.5 to + 13.2 with Hf model ages from 1196 to 454 Ma. Consequently, we propose that the collision between the Saur Island Arc and the Altay Terrane occurred in the Early Carboniferous (ca. 367–356 Ma) and the subsequent post-collisional tectonic process continued to the Late Carboniferous (ca. 324–320 Ma). It is further suggested that the Irtysh tectonic belt underwent large-scale strike-slip deformation during the mid-Permian between 287 and 279 Ma. The termination of the Irtysh tectonic belt orogeny is thought to have also occurred during the mid-Permian between 274 and 271 Ma.
Keywords: Zircon U–Pb age; Arc-related and collisional granitoids; Tectonic evolution; Irtysh tectonic belt

Three episodes of Precambrian mafic magmatism in the southern Central Tianshan Block (NW China): Insight into an evolving geodynamic model - Wang, Xin Shui; Klemd, Reiner; Gao, Jun; Jiang, Tuo (Precambrian Research, 2020)
Precambrian microcontinents are an essential component in the tectonic evolution and architecture of the Central Asian Orogenic Belt (CAOB). However, the early crustal evolution and origin of Precambrian microcontinents remain poorly constrained due to the scarcity of early Precambrian rocks. The Chinese Central Tianshan Block (CTB) constitutes a microcontinent in the western CAOB with Precambrian basement rocks along its southern margin. The basement rocks, comprising amphibolite-facies supracrustal assemblages of possible volcano-sedimentary origin, are exposed in the Wuwamen Complex, which occurs as tectonic slivers in the late Paleozoic Wuwamen ophiolitic mélange. Here we present in situ zircon U–Pb and Lu–Hf isotopic data and the whole-rock geochemistry of three suites of (meta-)mafic rocks from the Wuwamen Complex and an associated Neoproterozoic gabbro body. The zircon dating revealed that the Wuwamen Complex contains two suites of meta-mafic rocks with protolith formation at ca. 2.55 Ga and 2.21 Ga followed by an amphibolite-facies metamorphic overprint at ca. 1.83 Ga. In addition, an individual gabbro body adjacent to the Wuwamen Complex yielded an emplacement age of ca. 0.69 Ga, reflecting a mid-Neoproterozoic mafic magmatic event in the CTB. Furthermore, zircon U–Pb dating of a crosscutting diorite dyke and a gneissic diorite sourced from a composite batholith in the CTB yielded weighted mean intrusive ages of ca. 320 Ma and 454 Ma, respectively. In conjunction with the field observation, the emplacement ages suggest that the Wuwamen Complex represents a part of the continental arc basement of the CTB. The three suites of (meta-)mafic rocks show geochemical characteristics similar to typical arc-related basalts. Along with the evolved zircon Hf isotopic compositions, it is suggested that these rocks originated from partial melting of a metasomatized sub-continental lithospheric mantle during different events. In conjunction with previous studies, the here presented new data further suggest that the CTB and other microcontinents in the western CAOB record similar Precambrian magmatic and metamorphic episodes, which are comparable to those of the northern Tarim during Proterozoic times. The here outlined new model indicates that the microcontinents of the western CAOB and the Tarim Craton may have shared a common geodynamic evolution.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Accretionary processes; CAOB; Central Tianshan; Mafic magmatism; Microcontinent

Timing and duration of discrete tectono-metamorphic events of the polymetamorphic high-grade Central zone of the Limpopo Belt (South Africa): Insight from in situ geochronology of monazite and zircon - Zhou, Tian; Klemd, Reiner; Brandt, Sönke; Liu, Yu; Li, Qiu Li (Precambrian Research, 2022)
The Central Zone of the Limpopo Belt in southern Africa is a complex polymetamorphic terrane that has experienced three metamorphic events, at 3.22 Ga (M1), 2.71–2.56 Ga (M2) and 2.02 Ga (M3). On the basis of a previous detailed petrological and geothermobarometrical study of a newly discovered supracrustal enclave within the Bulai Pluton (ca. 2.61 Ga granitoid gneiss in the Central Zone), we conducted a geochronological in situ study of texturally and chemically different monazite and zircon grains, which occur respectively as inclusions in garnet, in decompressional cordierite coronas around garnet and as matrix grains in polymetamorphic granulite-facies metapelites. Secondary-ion mass spectrometry (SIMS) in situ analyses of the monazite and zircon grains in thin sections, complemented by analyses of separated zircon grains, allowed the texturally-controlled direct determination of U-Pb and 207Pb/206Pb ages at a scale of < 10 μm. A concordant age of ca. 2.71 Ga derived from zircon included in garnet is interpreted to reflect the age of initial garnet growth during the prograde M2 metamorphism. Zircons in the cordierite coronas around garnet revealed a slightly younger concordant age of ca. 2.56 Ga. Zircon growth in the coronas is related to the retrograde breakdown of garnet (Zr-bearing) through to the decompression reaction garnet + sillimanite + quartz → cordierite + zircon and hence the ca. 2.56 Ga zircon age is interpreted to reflect the timing of post-peak decompressional uplift. The zircon ages constrain the duration of M2 metamorphism to approximately 145 Myr. A concordant 2.71 Ga age of large monazite inclusions in garnet cores corroborates the 2.71 Ga zircon age of initial garnet growth during the prograde M2 metamorphism. Core domains of the largest monazite in cordierite corona revealed ages between 2.5 and 2.0 Ga that are interpreted to reflect (multiple) Pb-loss during the M3 granulite-facies metamorphism. Other monazites in cordierite coronas and matrix showed an age of ca. 2.0 Ga, reflecting complete re-equilibration or new growth during M3 overprinting. Owing to the preservation of the original micro-textures related to the growth of zircon and monazite we were able to link the age data with the P-T record, and refine the timing and duration of the M2 granulite-facies metamorphism (approximately 2.71–2.56 Ga) in the Limpopo Belt that was previously dated at ca. 2.62 Ga by zircon separation techniques. The ca. 145 Ma duration of granulite-facies metamorphism is consistent with a tectonic model of long-lasting asthenosphere upwelling and subsequent continent–continent collision in the late Neoarchean. Decompression triggered by post-collisional extension occurred at 2.56 Ga. Paleoproterozoic M3 granulite-facies metamorphism at ca. 2.0 Ga caused the widespread re-setting of the U-Pb and Pb-Pb data that also affected most zircon and monazite grains. This study reveals that precise dating of the timing and duration of distinct tectono-metamorphic events by texturally-controlled in situ geochronology allows a much better insight into the complex geodynamic evolution of high-grade polymetamorphic terranes.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Duration of metamorphic events; Limpopo Belt; Monazite; Polymetamorphism; Secondary ion mass spectrometry; U-Pb dating; Zircon

Trace Element and Isotope Systematics in Vent Fluids and Sulphides From Maka Volcano, North Eastern Lau Spreading Centre: Insights Into Three-Component Fluid Mixing - Klose, Lukas; Keith, Manuel; Hafermaas, Daniel; Kleint, Charlotte; Bach, Wolfgang; Diehl, Alexander; Wilckens, Frederike; Peters, Christian; Strauss, Harald; Klemd, Reiner; van Geldern, Robert; Haase, Karsten; et al. (Frontiers in Earth Science, 2021)
Back-arc spreading centres and related volcanic structures are known for their intense hydrothermal activity. The axial volcanic edifice of Maka at the North Eastern Lau Spreading Centre is such an example, where fluids of distinct composition are emitted at the Maka hydrothermal field (HF) and at Maka South in 1,525–1,543 m water depth. At Maka HF black smoker-type fluids are actively discharged at temperatures of 329°C and are characterized by low pH values (2.79–3.03) and a depletion in Mg (5.5 mmol/kg) and SO4 (0.5 mmol/L) relative to seawater. High metal (e.g., Fe up to ∼6 mmol/kg) and rare Earth element (REE) contents in the fluids, are indicative for a rock-buffered hydrothermal system at low water/rock ratios (2–3). At Maka South, venting of white smoke with temperatures up to 301°C occurs at chimneys and flanges. Measured pH values range from 4.53 to 5.42 and Mg (31.0 mmol/kg), SO4 (8.2 mmol/L), Cl (309 mmol/kg), Br (0.50 mmol/kg) and Na (230 mmol/kg) are depleted compared to seawater, whereas metals like Li and Mn are typically enriched together with H2S. We propose a three-component mixing model with respect to the fluid composition at Maka South including seawater, a boiling-induced low-Cl vapour and a black smoker-type fluid similar to that of Maka HF, which is also preserved by the trace element signature of hydrothermal pyrite. At Maka South, high As/Co (>10–100) and Sb/Pb (>0.1) in pyrite are suggested to be related to a boiling-induced element fractionation between vapour (As, Sb) and liquid (Co, Pb). By contrast, lower As/Co (<100) and a tendency to higher Co/Ni values in pyrite from Maka HF likely reflect the black smoker-type fluid. The Se/Ge ratio in pyrite provides evidence for fluid-seawater mixing, where lower values (<10) are the result of a seawater contribution at the seafloor or during fluid upflow. Sulphur and Pb isotopes in hydrothermal sulphides indicate a common metal (loid) source at the two vent sites by host rock leaching in the reaction zone, as also reflected by the REE patterns in the vent fluids.
Keywords: hydrothermal systems in back-arc basins; three-component fluid mixing; vent fluids; hydrothermal sulphides; Northeast Lau basin; trace elements; isotopes

Trace element and oxygen isotope study of eclogites and associated rocks from the Münchberg Massif (Germany) with implications on the protolith origin and fluid-rock interactions - Pohlner, Johannes E.; El Korh, Afifé; Klemd, Reiner; Grobéty, Bernard; Pettke, Thomas; Chiaradia, Massimo (Chemical Geology, 2021)
Eclogites, metagabbros, and paragneisses from the Variscan Münchberg Massif record a complex succession of igneous, hydrothermal and metamorphic processes. The geodynamic setting related to the protolith formation and the impact of different types of fluid-rock interactions have been uncertain up to now. We use major and trace element chemistry as well as oxygen isotopes to disentangle the geochemical signatures related to the different stages of the rocks' history. In the Münchberg Massif, dark eclogites (kyanite-free; Fe-Ti-MORB signature) are distinguished from light eclogites (kyanite-bearing; higher Mg#, Al2O3, and Cr; lower incompatible element contents; positive Eu anomalies; MORB to arc basalt signature). The δ18O values for both types (+5.0 to +10.8‰) are equal to, or higher than those of MORB. Amphibolite facies metagabbros have a more enriched, almost OIB-like trace element signature and high δ18O values (+9.4 to +10.3‰). Good linear correlations between fluid-immobile elements throughout the eclogite types confirm their derivation from a common, N-MORB to E-MORB-like parental magma. We interpret the light eclogites as former plagioclase-rich cumulates and the dark eclogites as their complementary differentiates. This relationship is partly obscured by variable degrees of magma contamination by sediments, which also affected the metagabbros. However, the metagabbros originated from a more enriched mantle source than the eclogites. Following intrusion, the eclogites were subjected to hydrothermal alteration under the influence of seawater, as indicated by positive correlations between Li, B, Sb, and δ18O. Metamorphic fluid-rock interactions appear to be mostly of limited extent, probably due to the lack of lawsonite dehydration as a fluid source. Nevertheless, the contents at least of some fluid-mobile elements, such as LILE, Li, and Pb, were probably modified during the subduction-exhumation cycle of the eclogites. The crustal contamination of the protolith magmas argues against derivation of the eclogites and metagabbros from typical oceanic crust. Instead, a rift-drift transition setting related to the opening of the Rheic or Saxothuringian Ocean seems most likely. The eclogites and metagabbros, alongside with similar rocks in the Mariánské Lázně complex and other resembling high-pressure massifs, may record different stages of this rift-drift transition.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Eclogites; Fluid-rock interactions; Subduction; Variscan Orogeny

Trace-element composition of minerals and rocks in the Belaya Zima carbonatite complex (Russia): Implications for the mechanisms of magma evolution and carbonatite formation - Doroshkevich, Anna G.; Veksler, Ilya V.; Klemd, Reiner; Khromova, Elena A.; Izbrodin, Ivan A. (Lithos, 2017)
The nature of petrogenetic links between carbonatites and associated silicaterocks is a matter of discussion for several decades and still remains controversial among igneous petrologists. The Belaya Zima plutonic complex in southern Siberia is a typical intrusion, in which carbonatites are spatially and temporally associated with the ijolite series rocks and nepheline syenites. In this study we use whole-rock compositions and trace element characteristics of the major and accessory minerals for reconstructing the magmatic evolution of the complex and clarifying the origin of carbonatites. We conclude that the observed gradual increase of Zr, Nb and REE concentrations in the magma is consistent with the process of extensive fractional crystallization and gradual transition from silicate rocks to carbonatites, and inconsistent with the formation of carbonatites by liquid immiscibility. Magma differentiation by fractional crystallization continued during the carbonatite formation. The textural and analytical evidence indicates that the early calcitic carbonatites evolved to dolomitic and ankeritic carbonatites. In addition, maximum Nb and Zr concentrations occur in the calcitic carbonatite, whereas the REE content increases in the dolomitic and ankeritic facies.<br
Keywords: REE and Nb; Carbonatites; Alkaline silicate rocks; Evolution

Trace element fractionation and precipitation in submarine back-arc hydrothermal systems, Nifonea caldera, New Hebrides subduction zone - Keith, Manuel; Haase, Karsten; Häckel, Florian; Schwarz-Schampera, Ulrich; Klemd, Reiner; Hannington, Mark; Strauss, Harald; McConachy, Timothy; Anderson, Melissa (Ore Geology Reviews, 2021)
Hydrothermal activity is abundant at volcanic structures in subduction zones, including those associated with young volcanism in back-arc regions. Fluid boiling is a common process in these environments, but its fractionation and precipitation effects on trace metals and metalloids are still poorly constrained. The submarine back-arc hydrothermal system of Nifonea caldera hosts two recently discovered active vent sites with sulphide-sulphate chimneys showing a diverse mineralogy and chemistry. The focused discharge of fluids with temperatures (up to 368 °C) near the seawater boiling curve at 1860 m water depth and “jets of steam” emitted from the chimney structures suggest fluid boiling. Fluid processes, as well as metal and metalloid deposition vary on a relatively small spatial-scale (<0.5 km2) and coincide with changes in sulphide-sulphate mineralogy and texture between different chimneys with zoning and dendritic intergrowths, indicating temperature gradients and fluid boiling. Boiling-induced precipitation, together with seawater mixing in the sub-seafloor led to a depletion of Zn, Ga, Ge, Ag, Cd, Sb, Au and Pb in the discharging fluids and their precipitates at the main compared to the northern vent site, also resulting in a depleted trace element signature with respect to most other back-arc hydrothermal systems in the Pacific Ocean. A magmatic-hydrothermal signature (high ) in some of the discharging fluids propose a weak magmatic volatile influx to the Nifonea caldera hydrothermal system. However, S isotope data provides no evidence for a magmatic volatile component and rather suggests, in combination with the sulphide-sulphate (Zn, Ge, Se, Ag, Cd, Sb, Ba, Au and Pb) and fluid data (high K) that the Nifonea caldera hydrothermal system is dominantly controlled by a combination of boiling, mixing and water–rock interaction.<br

Trace elements and textures of hydrothermal sphalerite and pyrite in Upper Permian (Zechstein) carbonates of the North German Basin - Knorsch, Manuel; Nadoll, Patrick; Klemd, Reiner (Journal of Geochemical Exploration, 2020)
Deeply buried Upper Permian (Zechstein) carbonates in the southwestern North German Basin host widespread Zn-Fe-Pb sulfide mineralization. The spatial extent of the sediment-hosted mineralization, the geochemical formation conditions, and the number of mineralizing events that are manifested in the Permian sedimentary rocks are an ongoing matter of debate and interest for mineral exploration efforts in the North German Basin. We present detailed petrographic and geochemical data of ore minerals from drill core samples from the Lower Saxony Basin that forms the southwestern part of the North German Basin. Based on these data, we propose and discuss a genetic model for the ore-forming processes. Of particular interest are the sources of metals and sulfur and the timing and temperature at which the sulfides formed. The main sulfide minerals are sphalerite, pyrite, and galena, which commonly occupy mm- to m-scale open space fillings and fractures. Petrographic observations further suggest hydrothermal replacement of the Zechstein Ca2 carbonates, by sulfides, secondary calcite, and anhydrite. Early diagenetic pyrite occurs disseminated in the Zechstein Ca2 carbonates. Scanning electron microscopy, electron microprobe, laser ablation ICP-MS, and sulfur isotope analyses were used to collect petrographic and compositional data on the sphalerite and pyrite. Hydrothermal sphalerite displays cyclical growth patterns and sectoral zoning characterized by colors varying from colorless to black and corresponding indicative variations in their minor and trace element concentrations, e.g., Fe concentrations ranging between below the limit of detection (7.7 ppm) to a maximum of 2.8 wt%. A detailed LA-ICP-MS multielement map illustrates the observed growth patterns and reveals that Mn, Co, Fe, Cu, Ge, Ag, Cd, Hg, Tl, and Pb are the elements that control the distinct color variations. Sectoral zoning is reflected in comparatively high Cu, Ag, and Pb contents, whereas the cyclical growth banding can be retraced by variations in Fe, Co, Cd, Hg, and Tl contents. Calculated temperatures from the trace element signatures using the GGIMFis geothermometer indicate a formation temperature of 148 ± 55 °C for sphalerite. Although the investigated mineralization bears many trademarks of a Mississippi Valley-type (MVT) deposit, the elevated temperatures, a burial depth of around 3.2 km, low concentrations of common strategic elements such as Ga, Ge, and In (< median of 1.3 ppm in sphalerite), as well as the abundance of pyrite represent the unique nature of the Ca2-hosted mineralization. The observed epigenetic ore zones are therefore best described as carbonate replacement mineralization and present an intriguing case study of geochemical exploration in a deeply covered terrane.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Ca2 Zechstein carbonate; LA-ICP-MS; Lower Saxony Basin; North German Basin; Pyrite; Sphalerite

Trace Element Signatures in Pyrite and Marcasite From Shallow Marine Island Arc-Related Hydrothermal Vents, Calypso Vents, New Zealand, and Paleochori Bay, Greece - Nestmeyer, Mark; Keith, Manuel; Haase, Karsten; Klemd, Reiner; Voudouris, Panagiotis; Schwarz-Schampera, Ulrich; Strauss, Harald; Kati, Marianna; Magganas, Andreas (Frontiers in Earth Science, 2021)
Fluid conditions of shallow marine hydrothermal vent sites (<200 mbsl) in island arcs resemble those of subaerial epithermal systems. This leads to a distinct mineralization-style compared to deeper arc/back-arc (>200 mbsl) and mid-ocean ridge-related environments (>2000 mbsl). At Calypso Vents in the Bay of Plenty and Paleochori Bay at the coast of Milos Island, fluids with temperatures <200°C are emitted through volcaniclastic sediments in water depths <200 mbsl. The hydrothermal mineralization from these fluids is dominated by pyrite and marcasite showing diverse textures, including colloform alternations, semi-massive occurrences surrounding detrital grains, vein-type pyrite, and disseminated fine-grained assemblages. Pyrite and marcasite from Calypso SE show elevated concentrations of volatile elements (e.g., As, Sb, Tl, Hg) implying a vapor-rich fluid phase. By contrast, elements like Zn, Ag, and Pb are enriched in hydrothermal pyrite and marcasite from Calypso SW, indicating a high-Cl liquid-dominated fluid discharge. Hence, vapor-liquid element fractionation induced by fluid boiling is preserved in the seafloor mineralization at Calypso Vents. Hydrothermal mineralization at very shallow vent sites (<10 mbsl), like Paleochori Bay, are affected by wave action causing a seasonal migration of the seawater-fluid interface in the sediment cover. The δ34S composition of native S crusts and crystalline S (0.7–6.7‰) is indicative for host rock leaching and thermochemical reduction of seawater sulphate. By contrast, the highly negative δ34S signature of native S globules in sediments (−7.6 to −9.1‰) is related to microbial sulphate reduction or a subordinate magmatic fluid influx. Alunite-jarosite alteration (Paleochori Bay) and a mineral assemblage consisting of orpiment, realgar, and native S (Calypso Vents) may also suggest a contribution by an oxidised (sulphate-rich) low pH fluid of potential magmatic origin. However, fluid boiling is pervasive at Calypso Vents and Paleochori Bay, and the condensation of vapor-rich fluids in a steam-heated environment may produce a similar alteration and mineralization assemblage without a significant magmatic fluid influx, as known from some subaerial epithermal systems.<br

Trace elements in magnetite from the pagoni rachi porphyry prospect, NE Greece: Implications for ore genesis and exploration - Mavrogonatos, Constantinos; Voudouris, Panagiotis; Berndt, Jasper; Klemme, Stephan; Zaccarini, Federica; Spry, Paul G.; Melfos, Vasilios; Tarantola, Alexandre; Keith, Manuel; Klemd, Reiner; Haase, Karsten (Minerals, 2019)
Magnetite is a common accessory phase in various types of ore deposits. Its trace element content has proven to have critical implications regarding petrogenesis and as guides in the exploration for ore deposits in general. In this study we use LA-ICP-MS (laser ablation-inductively coupled plasma-mass spectrometry) analyses of trace elements to chemically characterize magnetite from the Pagoni Rachi Cu–Mo–Re–Au porphyry-style prospect, Thrace, northern Greece. Igneous magnetite mostly occurs as euhedral grains, which are commonly replaced by hematite in fresh to propylitic-altered granodiorite porphyry, whereas, hydrothermal magnetite forms narrow veinlets or is disseminated in sodic/potassic-calcic altered (albite + K-feldspar + actinolite + biotite + chlorite) granodiorite porphyry. Magnetite is commonly associated with chalcopyrite and pyrite and locally exhibits martitization. Laser ablation ICP-MS analyses of hydrothermal magnetite yielded elevated concentrations in several trace elements (e.g., V, Pb, W, Mo, Ta, Zn, Cu, and Nb) whereas Ti, Cr, Ni, and Sn display higher concentration in its magmatic counterpart. A noteworthy enrichment in Mo, Pb, and Zn is an unusual feature of hydrothermal magnetite from Pagoni Rachi. High Si, Al, and Ca values in a few analyses of hydrothermal magnetite imply the presence of submicroscopic or nano-inclusions (e.g., chlorite, and titanite). The trace element patterns of the hydrothermal magnetite and especially the decrease in its Ti content reflect an evolution from the magmatic towards the hydrothermal conditions under decreasing temperatures, which is consistent with findings from analogous porphyry-style deposits elsewhere.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Exploration; Hydrothermal; LA-ICP-MS; Magmatic; Magnetite; Porphyry; Trace elements

Trace element systematics and ore-forming processes in mafic VMS deposits: Evidence from the Troodos ophiolite, Cyprus - Martin, Andrew J.; Keith, Manuel; Mcdonald, Iain; Haase, Karsten; Mcfall, Katie A.; Klemd, Reiner; Macleod, Christopher J. (Ore Geology Reviews, 2019)
The volcanogenic massive sulfide (VMS) deposits in the Troodos ophiolite (Cyprus) are ancient analogues for modern day seafloor massive sulfide mineralisation formed in a supra-subduction zone environment. In this study we present the first detailed in situ study of trace elements in sulfides from twenty VMS deposits hosted in the Troodos ophiolite to better understand factors that influence the distribution, enrichment and incorporation of trace elements in different sulfide minerals.
CRIS-Team WoS Importer:2019-04-09

Trace element systematics of pyrite from submarine hydrothermal vents - Keith, Manuel; Häckel, Florian; Haase, Karsten; Schwarz-Schampera, Ulrich; Klemd, Reiner (Ore Geology Reviews, 2016)
Submarine hydrothermal sulfide ores occur at mid-ocean ridges, intra-oceanic arcs and in back-arc basins associated with host rocks of highly variable composition. Pyrite is the dominant sulfide mineral in most samples presented within this study, and thus the trace element composition of pyrite may reflect the different metal sources and precipitation processes. Here, we report on a systematic study of minor and trace element contents in pyrite from active and inactive submarine hydrothermal vent fields at different plate-tectonic settings including the Indian and Mid-Atlantic Ridges, the Tonga-Kermadec intra-oceanic arc, the Lau back-arc and the central Okinawa Trough. Our results show that the trace element contents of pyrite from different locations vary significantly but for most elements without any systematic correlation to the concentration in the magmatic host rocks. Only As appears to be depleted in pyrite from ultramafic-hosted vent systems that are affected by serpentinization. These As depleted pyrites preferentially host Au micro- or nano-particles. Bismuth is enriched in pyrite from hydrothermal systems that contain a sedimentary component and micro-inclusions of sphalerite are either due to fluid-sediment interaction or phase-separated fluid venting. Pyrites from individual locations have highly variable concentrations of elements like Au, Co, Cu, Se, Mo, Ag and Sb that are most likely related to fluid evolution and changes in fluid composition. Sub-seafloor hydrothermal fluid-seawater mixing influences the distribution of Au, Co, Cu, Se and Mo in pyrite. Elements like Au, Ag, Sb and Pb often have a characteristic affinity to As, while Cd correlates closely with Zn. A magmatic volatile contribution to the Hine Hina hydrothermal system may result in the precipitation of Cu-enriched pyrite. Our results show that the concentrations of most trace metals in pyrite are a function of the physicochemical parameters of the fluid phase rather than a reflection of the magmatic host rock compositio
Keywords: Hydrothermal sulfides; Laser ablation ICP-MS; Pyrite; Trace elements; VHMS

Tracking crystal-melt segregation and magma recharge using zircon trace element data - Yan, Li Li; He, Zhen Yu; Klemd, Reiner; Beier, Christoph; Xu, Xi Sheng (Chemical Geology, 2020)
The Cretaceous Yunshan caldera complex in SE China consists of an unusual coexisting assemblage of peraluminous and peralkaline rhyolites and a resurgent intra-caldera porphyritic quartz monzonite. In this study, we use zircon trace element data to study the compositional differences of zircons from cogenetic magmas and to track the evolution of the entire magmatic system. Our results indicate that the zircons from the peraluminous and peralkaline rhyolites formed from highly evolved compositions with high Hf concentrations and low Ti contents, and low Th/U and Zr/Hf ratios, which are distinct from those of the intrusive porphyritic quartz monzonite. Zircons from the peraluminous and peralkaline rhyolites display overlapping Zr/Hf and Hf, but the zircons from the peralkaline rhyolites have extremely low Eu/Eu* ratios (<0.1) and Ti contents (2.26–13.3 ppm). The lack of overlapping zircon trace element compositions between the volcanic and intrusive caldera units is interpreted to represent crystal–melt segregation processes. In addition, zircon grains from the porphyritic quartz monzonite and a few zircon grains from the peraluminous rhyolite display distinctly bright rims and whole grains in cathodoluminescence imaging, which have high Ti, Zr/Hf, and Eu/Eu*, and are similar to those of zircons from the mafic microgranular enclave within the porphyritic quartz monzonite. We interpret these signatures to reflect crystallization from a relatively hot and less evolved magma indicating a magma chamber recharge event. We further developed a model in which the magmas of the peraluminous and peralkaline rhyolites were successively extracted from a primitive crystal mush by crystal–melt segregation with a rejuvenation of the crystal mush after the extraction of the peraluminous rhyolitic melt, leaving behind residual mushes solidified as porphyritic quartz monzonite. Our study shows that trace element analyses of zircons can effectively be used to pinpoint multiple crystal–melt segregation and melt extraction events as well as magma recharge processes in silicic magmatic systems.
CRIS-Team Scopus Importer:2020-04-07
Keywords: Crystal–melt segregation; Magma differentiation; Magma recharge; SE China; Yunshan caldera complex

Two phases of post-onset collision adakitic magmatism in the southern Lhasa subterrane, Tibet, and their tectonic implications - Lu, Tianyu; He, Zhen-Yu; Klemd, Reiner (Geological Society of America Bulletin, 2020)
Abundant Neogene adakitic magmatism occurred in the southern Lhasa subterrane after the onset of the India-Asia collision while convergence continued. However, the tectonic setting and magmatic evolution of the adakitic rocks are still under discussion. This study includes new mineral chemical and whole-rock geochemical data as well as zircon U-Pb and Lu-Hf isotopes of adakitic intrusive rocks from the Gyaca and Nyemo locations in the southern Lhasa subterrane. Laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) zircon U-Pb dating yielded crystallization ages of ca. 30 Ma for the Gyaca and Nyemo monzogranite and ca. 15 Ma for the Nyemo granodiorite. Both have common chemical signatures such as low MgO and heavy rare earth element contents as well as low compatible element abundances, indicating that these rocks result from partial melting of thickened lower crust with residual eclogite and garnet amphibolite. Furthermore, these rocks are characterized by variable positive zircon εHf(t) values, suggesting a juvenile magma source with variable ancient crustal contributions. Taking previous data into account, the adakitic magmatism concurs with an early late Eocene to Oligocene (ca. 38-25 Ma) and a late Miocene (ca. 20-10 Ma) phase. The adakitic rocks of the two phases are characterized by different fractionation evolutions of light and medium rare earth elements. We propose that the early-phase adakitic rocks were generated by the anatexis of Lhasa terrane lower crust owing to crustal shortening and thickening subsequent to the onset of the India-Asia collision and the upwelling of hot asthenosphere beneath the Lhasa terrane caused by the break-off of the Neo-Tethyan oceanic slab. The latest phase of adakitic rocks, however, relates to upwelling asthenosphere following the delamination and/or break-off of the subducting Indian continental slab.
CRIS-Team Scopus Importer:2020-08-07

Uncovering and quantifying the subduction zone sulfur cycle from the slab perspective - Li, Ji Lei; Schwarzenbach, Esther M.; John, Timm; Ague, Jay J.; Huang, Fang; Gao, Jun; Klemd, Reiner; Whitehouse, Martin J.; Wang, Xin Shui (Nature Communications, 2020)
Sulfur belongs among H2O, CO2, and Cl as one of the key volatiles in Earth’s chemical cycles. High oxygen fugacity, sulfur concentration, and δ34S values in volcanic arc rocks have been attributed to significant sulfate addition by slab fluids. However, sulfur speciation, flux, and isotope composition in slab-dehydrated fluids remain unclear. Here, we use high-pressure rocks and enclosed veins to provide direct constraints on subduction zone sulfur recycling for a typical oceanic lithosphere. Textural and thermodynamic evidence indicates the predominance of reduced sulfur species in slab fluids; those derived from metasediments, altered oceanic crust, and serpentinite have δ34S values of approximately −8‰, −1‰, and +8‰, respectively. Mass-balance calculations demonstrate that 6.4% (up to 20% maximum) of total subducted sulfur is released between 30–230 km depth, and the predominant sulfur loss takes place at 70–100 km with a net δ34S composition of −2.5 ± 3‰. We conclude that modest slab-to-wedge sulfur transport occurs, but that slab-derived fluids provide negligible sulfate to oxidize the sub-arc mantle and cannot deliver 34S-enriched sulfur to produce the positive δ34S signature in arc settings. Most sulfur has negative δ34S and is subducted into the deep mantle, which could cause a long-term increase in the δ34S of Earth surface reservoirs.
CRIS-Team Scopus Importer:2020-02-04

Unravelling slab δ34S compositions from in-situ sulphide δ34S studies of high-pressure metamorphic rocks - Li, Ji-Lei; Klemd, Reiner; Huang, Gao-Feng; Ague, Jay J.; Gao, Jun (International Geology Review, 2020)
Sulphur is of particular importance in the subduction zone system, as it is thought to be intimately related to the arc redox state and metallogenesis above the slab. Knowing the sulphur isotope compositions of the subducted slab, and identifying the δ34S variations between the pre-subduction oceanic lithosphere and its high-pressure (HP) equivalents is of great importance for understanding the sulphur behaviour in subduction zones and the long-term sulphur recycling of the Earth. In this study, we undertook secondary ion mass spectroscopy (SIMS) in-situ δ34S analyses of sulphides from metasediments, mafic blueschists/eclogites, and ultramafic slab serpentinites from the Southwestern Tianshan HP–UHP metamorphic belt, which represents one of the deepest fossil subduction zones on Earth. By integrating the in-situ δ34S compositions of sulphides studied here and those reported from worldwide HP–UHP metamorphic terranes, we found that prograde to peak metamorphic sulphides of metasediments, metabasites/metagabbros, and slab HP serpentinites have δ34S values ranging from –33 to –6‰, –4 to +4‰, and +2 to +18‰, respectively. However, retrograde metasomatism of HP rocks during exhumation may alter the δ34S compositions of sulphides. The integrated dataset proposes that sulphides in subducting slab sequences retain their protolith’s δ34S signatures during HP metamorphism. The δ34S inheritance indicates that no large isotope fractionation is expected to occur in subduction zones. It further suggests that evaluations of slab subduction effects on the δ34S signature of arc magmatism and the deep mantle should consider pre-subduction processes such as ridge geodynamic setting and hydrothermal alteration.
CRIS-Team Scopus Importer:2020-10-23
Keywords: eclogite; high-pressure metamorphism; subduction zone; sulphide; sulphur isotope

Unravelling the P-T-t history of three high-grade metamorphic events in the Epupa Complex, NW Namibia: Implications for the paleoproterozoic to mesoproterozoic evolution of the Congo Craton - Brandt, Sönke; Klemd, Reiner; Xie, Hanqiang; Bobek, Patrick (American Journal of Science, 2021)
The Epupa Complex of northern Namibia constitutes the south-western margin of the Archean Congo Craton of central Africa. We present new petrological and geochronological data for metasedimentary migmatites that decode the poorly-known Paleoproterozoic to Mesoproterozoic evolution of this remote part of the craton. Detrital magmatic zircons with concordant 207Pb/206Pb ages between 1898 and 1774 Ma are interpreted to demonstrate the formation of the metasedimentary protoliths through reworking of Paleoproterozoic granitoids of a magmatic arc in a back-arc basin. SHRIMP U-Pb zircon analyses of metamorphic rims around the detrital grains linked with constraints from pseudosection modelling revealed three distinct high-grade metamorphic events in the migmatites. Late Paleoproterozoic regional HT-LP metamorphism between 1740 and 1720 Ma constitutes the oldest event and only affected the rocks of the northernmost part of the Epupa Complex (Eyao Unit). Heating to mid-amphibolite facies peak P-T conditions of 720 °C and 4 kbar caused the partial replacement of early biotite-sillimanite by garnet-cordierite assemblages during melt-producing reactions in metapelites. The near-isobaric heating-cooling P-T paths and the high geothermal gradient (60 °C/km) are consistent with HP-LP metamorphism in a back-arc basin setting with up-rising basic melt as heat source. Early Mesoproterozoic (1530 Ma) HT-LP metamorphism is recorded by rare Mg-rich Opx-Crd rocks that are restricted to the westernmost part of the Eyao Unit. Near-isobaric P-T paths culminate at granulite facies peak-conditions of 830 °C and 2 kbar. This local HP-LP event is interpreted to record contact metamorphism related to the coeval emplacement of early-Mesoproterozoic granitoids or the emplacement of intimately associated gabbros. Metapelitic Grt-Bt-Sil migmatites record the third high-grade metamorphic event that was active at ca. 1330 Ma and is restricted to the southern part of the Epupa Complex (Orue Unit). Sillimanite pseudomorphs after kyanite and late cordierite coronas around garnet indicate a clockwise P-T path during regional upper-amphibolite facies metamorphism that peaks at lower crustal conditions of 770 °C and 7.5 kbar. The clockwise P-T path is interpreted to reflect crustal thickening through magmatic accretion of basic melts that produced the coeval Kunene Intrusive Complex, the largest massif-type anorthosite in the world. The metamorphic events detected in the migmatites record a change of the geotectonic position of the Epupa Complex from a convergent continental margin during the late Paleoproterozoic to an intracratonic position in the Mesoproterozoic. The migmatites of the Eyao Unit were affected by an intense hydrothermal alteration during the Pan-African orogeny (ca. 520 Ma) that also caused the partial re-setting of the U-Pb zircon isotope system.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Amphibolite facies; Congo Craton; Epupa Complex; HT-LP metamorphism; Migmatite; P-T-t path; Paleoproterozoic; Pseudosections

U-Pb zircon ages and (isotope) geochemical signatures of the Kamanjab Inlier (NW Namibia): constraints on Palaeoproterozoic crustal evolution along the southern Congo craton. - Kleinhanns, I. C.; Fullgraf, T.; Wilsky, F.; Nolte, N.; Fliegel, D.; Klemd, Reiner; Hansen, B. T. (Continent Formation Through Time, 2015)
The formation of the Kamanjab Inlier (KI) in NW Namibia is poorly known and constrained to Palaeoproterozoic times. With the Epupa complex (EC) and Grootfontein Inlier (GI), the KI marks the southwestern Congo craton margin. Our new geochemical data for granitoids and orthogneisses indicate formation along an active continental margin. Single zircon ages frame granitoid emplacement to 1.86–1.83 Ga, roughly 75 myr older than ages from the northern EC and approximately 100 myr younger than from the GI. The southern EC is the only known Archaean Namibian basement with ɛNd1.85 Ga of −10.2 to −6.3, in contrast to northern EC (−1.8 to 4.4) and KI (−6.2 to 2.6). Thus, earlier speculation that the southern EC is an exotic terrane, among the Namibian basement complexes, is supported by our data. In contrast, the KI is geochemically comparable to the northern EC and GI. The c. 2.0 Ga Lufubu metamorphic complex roughly 1000 km further east shows similar geochemistry, and a common evolution in the Kamanjab–Bangeweulu magmatic arc has already been proposed. Therefore, our new data point to a major Palaeoproterozoic crustal growth event at the southwestern margin of the Congo Craton starting in the present east and gradually moving towards the present NW.

U-Pb zircon ages and (isotope) geochemical signatures of the Kamanjab Inlier (NW-Namibia): constraints on Paleoproterozoic crustal evolution along the southern Congo craton - Kleinhanns, I. C.; Fullgraf, T.; Wilsky, F.; Nolte, N.; Fliegel, D.; Klemd, Reiner; Hansen, Bent (Continent Formation Through Time., 2013)
The formation of the Kamanjab Inlier (KI) in NW Namibia is poorly known and constrained to alaeoproterozoic times. With the Epupa complex (EC) and Grootfontein Inlier (GI), the KI marks the southwestern Congo craton margin. Our new geochemical data for granitoids and orthogneisses indicate formation along an active continental margin. Single zircon ages frame granitoid emplacement to 1.86–1.83 Ga, roughly 75 myr older than ages from the northern EC and approximately 100 myr younger than from the GI. The southern EC is the only known Archaean Namibian basement with 1Nd1.85 Ga of 210.2 to 26.3, in contrast to northern EC (21.8 to 4.4) and KI (26.2 to 2.6). Thus, earlier speculation that the southern EC is an exotic terrane, among the Namibian basement complexes, is supported by our data. In contrast, the KI is geochemically comparable to the northern EC and GI. The c. 2.0 Ga Lufubu metamorphic complex roughly 1000 km further east shows similar geochemistry, and a common evolution in the Kamanjab–Bangeweulu magmatic arc has already been proposed. Therefore, our new data point to a major Palaeoproterozoic crustal growth event at the southwestern margin of the Congo Craton starting in the present east and gradually moving towards the present NW.<br
UnivIS-Import:2015-04-20:Pub.2013.nat.dgeo.IGM.c3geoc.upbzir

Volcanic arcs fed by rapid pulsed fluid flow through subducting slabs - John, Timm; Gussone, Nikolaus; Podladchikov, Yuri Y.; Bebout, Gray E.; Dohmen, Ralf; Halama, Ralf; Klemd, Reiner; Magna, Tomas; Seitz, Hans-Michael (Nature Geoscience, 2012)
At subduction zones, oceanic lithosphere that has interacted with sea water is returned to the mantle, heats up during descent and releases fluids by devolatilization of hydrous minerals. Models for the formation of magmas feeding volcanoes above subduction zones require largescale transport of these fluids into overlying mantle wedges 1-3. Fluid flow also seems to be linked to seismicity in subducting slabs. However, the spatial and temporal scales of this fluid flow remain largely unknown, with suggested timescales ranging from tens to tens of thousands of years 3-5. Here we use the Li-Ca-Sr isotope systems to consider fluid sources and quantitatively constrain the duration of subduction-zone fluid release at ∼ 70 km depth within subducting oceanic lithosphere, now exhumed in the Chinese Tianshan Mountains. Using lithium-diffusion modelling, we find that the wall-rock porosity adjacent to the flowpath of the fluids increased ten times above the background level. We show that fluids released by devolatilization travelled through the slab along major conduits in pulses with durations of about ∼ 200 years. Thus, although the overall slab dehydration process is continuous over millions of years and over a wide range of pressures and temperatures, we conclude that the fluids produced by dehydration in subducting slabs are mobilized in short-lived, channelized fluid-flow events. © 2012 Macmillan Publishers Limited. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.c3geoc.volcan

Zircon Ages of Metasedimentary Rocks in the Wuwamen Ophiolitic Mélange, Chinese South Tianshan: Implications for the Paleozoic Subduction-Accretion in the Southern Central Asian Orogenic Belt - Wang, Xin Shui; Yang, Fei; Klemd, Reiner; Jiang, Tuo; Gao, Jun (Journal of Earth Science, 2022)
High-temperature and high-pressure (high-grade) metamorphic complexes of variable ages are common in the Central Asian orogenic belt (CAOB), and their precise geochronology and origin are essential to unravel the orogenic architecture and crust-production rate of the CAOB. Hereby it is essential to differentiate between pre-orogenic Precambrian basement and Paleozoic arc-accretionary complexes. This study provides precise in situ zircon U−Pb ages for the metasedimentary rocks in the Wuwamen ophiolitic mélange, which is traditionally thought to represent the pre-orogenic basement of the southwestern CAOB. A meta-sandstone from the meta-flysch sequence revealed a widespread ca. 1.8 Ga high-grade metamorphic overprint similar to that of the underlying orthogneisses and, thus, was interpreted to represent pre-orogenic basement fragments that occur as tectonic blocks in the Paleozoic ophiolitic mélange. In contrast, a schist from the mélange matrix is characterized by a ca. 333 Ma high-grade metamorphic overprint, indicating that the northward subduction of the South Tianshan Ocean was still active at this time. The thrust-imbricated high-grade metamorphic rocks of contrasting origins in an accretionary complex have important implications for the understanding the accretionary history and crustal growth of the CAOB. Furthermore, the strongly deformed ophiolitic mélange was intruded by an undeformed granite dyke with an emplacement age younger than ca. 294 Ma, thus providing a minimum age limit for the final closure of the South Tianshan Ocean.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CAOB; geochemistry; high-temperature/high-pressure metamorphism; ophiolitic mélange; subduction; Tianshan; Zircon U−Pb

Zircon trace element constrains on the link between volcanism and plutonism in SE-China - Yan, Lili Li; He, Zhenyu; Beier, Christoph; Klemd, Reiner (Lithos, 2018)
Trace elements in igneous zircon crystals are variable within single crystals or amongst populations of crystals and are particularly sensitive to changes in melt composition. In this study, we present zircon trace element data from both volcanic and plutonic rocks of the Yandangshan caldera complex from SEChina. The erupted rhyolitic rocks are interpreted to represent the most differentiated magma, whereas the intruded porphyritic quartz syenites are thought to be representative of the residual crystal mush. The zircon crystals of both lithologies are subdivided into two types based on their internal structures: type A with a distinct oscillatory growth zoning and type B crystals are bright in cathodoluminescence (CL-bright). Type B zircon occurs as rims of type A zircon or as individual grains. Compared to type A, type B zircons commonly show lower Hf, U, Th and Y concentrations and higher Ti and Zr/Hf and Eu/Eu* ratios. The zircon trace element compositions of the volcanic samples generally overlap those of the intracaldera porphyritic quartz syenite and mafic microgranular enclaves that contain both type A and type B zircons. Despite a general overlap, zircon grains from the volcanic rocks show relatively higher Hf contents and Y/Dy ratios, lower Ti contents and Th/U ratios and larger negative Eu anomalies than the plutonic samples. We suggest that the inter- and intragrain compositional variability of zircon crystals can be used to track the evolution of magmatic systems. We show that in our case, the volcanic and plutonic rocks crystallized continuously during the magmatic evolution in a common magma system and that the magmas of these rocks may be linked by fractional crystallization. Furthermore, the type B zircon grains are inferred to have crystalized in relatively hot and less evolved magma indicating a magma recharge event. Consequently, the geochemical variability of igneous zircon crystals can be used to infer on the magmatic evolution of single volcanic system which may also be applicable in other geodynamic environments.<br
Keywords: Zircon trace elements; Magma differentiation; Volcanic–plutonic connection; Yandangshan caldera complex; SE China